Evaluation of antimicrobial efficacy of tailored chitosan-based cationic carbon quantum dots against multidrug-resistant bovine mastitis pathogens - Basavaprabhu Haranahalli Nataraj; Shubham Vishwakarma; Vineet Manjunath; Vandana Kamanahalli Venkataramanareddy; Rashmi Hogarehalli Mallappa; Heartwin Amaladhas Pushpadass; Avanish Singh Parmar; Raghu Hirikyathanahalli Vishweswaraiah (Food Control, 2027)

Generation of miR-141/200c conditional knockout mice from knockout-first, reporter-tagged parent and functional validation of the floxed allele - Sanjeev Kumar Yadav; Rashmi Srivastava; Mary-Katherine Cormier; Katie Lowther; Siu-Pok Yee; Rajkumar Verma (Mammalian Genome, 2026)

Global nutraceutical governance and nutrivigilance: A systematic review and regulatory maturity framework - Mohammad Nadeem Khan; Anuja Jha; Ashok Kumar; Rashmi Mahajan; Pooja Reddy (Food and Humanity, 2026)

A novel homozygous C15ORF41 variant (c.251T > A; p.Val84Glu) causing congenital dyserythropoietic anemia type Ib in an Indian patient: molecular and structural evidence - Prachi Kamble; Rashmi Dongerdiye; Tejashree More; Arati Saptarshi; Prashant Warang; Girish Subramaniam; Manisha Madkaikar; Prabhakar S. Kedar (Molecular Biology Reports, 2026)

Long non-coding RNAs as modulators of endocrine therapy response in hormone receptor-positive breast cancer - Supriya Shukla; Manika P. Sharma; Rashmi Rashmi; Gauri Misra (Molecular Biology Reports, 2026)

ROR1 protein: a pseudokinase at the crossroads of cancer progression and therapy - Shradheya R. R. Gupta; Rashmi Rameshwari; Indrakant Kumar Singh (Molecular Biology Reports, 2026)

SynerGel: Ciprofloxacin–Borneol Dual‑Loaded Stimuli-Triggered In-Situ Gel for Precision Ocular Delivery in Conjunctivitis - Maha Alsunbul; Rashmi Singh; Md Habban Akhter; Bjad K. Almutairy; M Yasmin Begum; Md Sajid Ali; Sarfaraz Ahmad; Nawazish Alam; Gyas Khan; Syeda Ayesha Farhana; Shalam M. Hussain; Imran Shahid; et al. (Journal of Pharmaceutical Innovation, 2026)

Seasonality of isoprene emission from sixteen dominant tropical tree species in Central India - Tanzil Gaffar Malik; Sudhir Kumar Pandey; Wan Shafrina Wan Mohd Jaafar; Andrea Clavijo McCormick; Lokesh Kumar Sahu; Ankesh Tiwari; Rashmi Dubey; Bilal Ahmad Mir; Khalid Rehman Hakeem; Annisa Utami Rauf (Journal of Atmospheric Chemistry, 2026)

Drive or breathe? Information-aware mode choice under real-time exposure using ICLV-CMXL approach - Rashmi Choudhary; Amit Agarwal (Transportation Research Part D: Transport and Environment, 2026)

Fitting the pieces into a whole picture: physiology and pathogenesis in huanglongbing disease - Maryam Khalilzadeh; Rashmi Kumari; Dorcas Olufunke Alade; Amit Levy; Christopher Vincent (Physiological and Molecular Plant Pathology, 2026)

Sulfur-driven adaptive succession of denitrifiers enables coordinated autotrophic–heterotrophic deep denitrification - Yu Cheng; Renke Wei; Dongyang Duan; Zhiwei Fang; Rashmi Koju; Chengzhi Hu (Water Research, 2026)

Wireless sensing for intelligent monitoring and condition assessment in distributed infrastructure systems - Hadi Salehi; Nazila Jamshidighadikolaei; Rashmi Bhaila; John Matthews; Pengcheng Jiao (Tunnelling and Underground Space Technology, 2026)

Protective effects of curcumin on short and long-term particulate matter (PM10/2.5) induced lung damage severity via modulation of neutrophil extracellular traps (NETs) formation in mouse model - Diksha Sharma; Vandana Soni; Shalini Singh; Prashant Kumar Chauhan; Abhay Kumar Singh; Rashmi Singh (Tissue and Cell, 2026)

Acetamide inducible expression vectors are not suitable for studying the functions of genes involved in mycobacterial survival in acidic environment - Rupal Rai; Rashmi Chourasia; Anirudh K. Singh; Shivendra K. Chaurasiya (Next Research, 2026)

Laser-induced graphene integrated polyamide electroconductive reverse osmosis membrane with enhanced anti-fouling and electro-cleaning properties - Rupam Nandan; Rashmi Ranjan; Swatantra P. Singh (Journal of Environmental Chemical Engineering, 2026)

Epitope-targeted anti-internalin A and Internalin B antibodies enable lateral flow immune-chromatographic detection of Listeria monocytogenes in milk - Mariya Divanshi; Jitesh Tarak; Shreya Saha; Namita Narwal; Rashmi Hogarehalli Mallappa; Diwas Pradhan; Sachinandan De; Varij Nayan; Anuradha Bhardwaj; Arun Kumar Bhunia; Raghu Hirikyathanahalli Vishweswaraiah (International Dairy Journal, 2026)

A comprehensive multi-approach study of MG132: Integration of in vitro-in vivo metabolism, metabolic stability, molecular docking, in silico toxicity, and UHPLC-QToF-MS/MS analysis - Rashmi Deshpande; Rushikesh Biradar; Anupam Jaiswal; Vaibhav Deshmukh; Sukhendu Nandi (Food and Chemical Toxicology, 2026)

Metal-Organic Framework-Engineered Electro-Assisted Nanofiltration for Multi-contaminant Groundwater Treatment - K. Rashmi; D. Sreenivasulu; M. Nagaraj; H. T. Avinash (International Journal of Environmental Research, 2026)

Linking Derivative Absorption Spectra and HPLC Pigments to Satellite Observations for Phytoplankton Typing in Coastal India - Aswathy Vijaya Krishna; B. Srijith; Anima Tirkey; Syed Moosa Ali; Debojyoti Ganguly; Anurag Gupta; Mini Raman; Sanjib Kumar Deb; Rashmi Sharma (Journal of the Indian Society of Remote Sensing, 2026)

An analytical model for subsurface ground motions due to kinematic shear dislocation sources in layered media - Jahnabi Basu; B Shree Rashmi; S.T.G. Raghukanth; Varun Kumar Singla (Soil Dynamics and Earthquake Engineering, 2026)

The function of enzymes in the detergent industry: Improving cleaning efficacy and environmental sustainability - Naveen Kumar; Rashmi Tyagi; Geetha Das; Ranjit Singh (Next Research, 2026)

Prospector enables defined enriched consortium selection for PFAS degradation via defluorination and Chain-Shortening - Esaú De la Vega-Camarillo; Jorge Arreola-Vargas; Saurav Kumar Mathur; Rashmi Singla; Smriti Shankar; Cory Klemasevich; Joshua Andrew Santos; Sanjay Antony-Babu; Won Bo Shim (Bioresource Technology, 2026)

Introgression of teosinte branched1 gene from wild-progenitor enhances prolificacy in subtropically-adapted maize - Firoz Hossain; Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Irum Gul; Amitkumar D. Kyada; Elizabeth Mathew; Ravindra K. Kasana; Nitish R. Prakash; Vinay Bhatt; Sunil Neelam; Vignesh Muthusamy (Planta, 2026)

Observing Ocean Conditions: Prior and Post Cyclone ‘Tauktae’ Using Satellite and In-situ Data - Kesavakumar Balakrishnan; Suchandra Aich Bhowmick; Venkatesan Ramasamy; Shanmugam Palanisamy; Ram Kumar Giri; M. Jishad; Anup Kumar Mandal; M. Seemanth; Rishi Gangwar; Neeraj Agarwal; Rashmi Sharma; Sundar Ranganathan; et al. (Journal of the Indian Society of Remote Sensing, 2026)

Cover crops influence above- and belowground invertebrates in a northern grain field - Paula Thitz; Mikko Tiusanen; Seraina Lisa Cappelli; Stephanie Gerin; Rashmi Shrestha; Marleena Hagner; Jussi Heinonsalo; Anna-Liisa Laine; Juha Mikola (Agriculture, Ecosystems & Environment, 2026)

Unravelling Novel Polymorphism and Developing a Breeder-Friendly Functional Marker in Dwarf8 Gene Associated with Dwarfism in Zea mays - Govinda Rai Sarma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Amitkumar D. Kyada; Vinay Bhatt; Botta Thandava Ganesh; Vinay Rojaria; Viswanathan Chinnusamy; Firoz Hossain (Journal of Plant Growth Regulation, 2026)

A novel integrative in silico approach reveals the intricacies underlying early host defense responses and pathogenic establishment during Magnaporthe oryzae-Oryza sativa interactions - S. L. Vaishnavi; Rashmi Hosamani; R. G. Sharathchandra; H. S. Santosh Kumar; C. R. Chandrashekar (Indian Phytopathology, 2026)

Late Archaean (~2.6 Ga) crustal reworking in the Western Dharwar Craton: Zircon U-Pb ages and trace element constraints from the Narasiparvatha pluton, Western Ghats (Kudremukh) belt - Chandan Kumar Boraiaha; Sarbartha Shankar Mishra; Jiří Sláma; Rashmi Chandan (International Geology Review, 2026)

Identification of selective bioactive compounds from Fenugreek seed extracts by GC-MS analysis and their anti-tumoral potential via modulation of Parkin in oral cancer - Rashmi Kumari; Madhu Rani; M. Amarendar Reddy; Siya Ram; Imran Khan; M. Moshahid Alam Rizvi (In Silico Pharmacology, 2026)

Structure-based discovery of novel ROCK2 inhibitors using integrated virtual screening, molecular dynamics, metadynamics and absolute binding free energy calculations - Shradheya R. R. Gupta; Rashmi Rameshwari; Indrakant K. Singh; Vanshika Rustagi (In Silico Pharmacology, 2026)

Integrated in silico screening and biophysical evaluation of three plant flavonoids interacting with Newcastle disease virus proteins - Rashmi Singh; Sachin Kumar; Latha Rangan (Virus Genes, 2026)

Efficient in vitro regeneration and phytochemical characterization of medicinal plant Barleria prionitis L. - Rashmi Ranade; Neelu Joshi (In Vitro Cellular & Developmental Biology - Plant, 2026)

Retraction notice to “Biotechnological potential of rumen microbiota for sustainable bioconversion of lignocellulosic waste to biofuels and value-added products” [Sci. Total Environ. 814 (2022) 152773] - Sachin Krushna Bhujbal; Pooja Ghosh; Virendra Kumar Vijay; Rashmi Rathour; Manish Kumar; Lal Singh; Atya Kapley (Science of The Total Environment, 2026)

Phage mediated disruption of methicillin-resistant Staphylococcus aureus biofilms on stainless steel under dairy conditions - Kavitha Parachalil; Muskaan Garg; Rushikesh Deshmuk; Mansi Sahu; Adrija Renupriya; Diwas Pradhan; Rashmi Hgarehalli Mallappa; Shilpa Vij; Raghu Hirikyathanahalli Vishweswaraiah (International Dairy Journal, 2026)

Development of subtropically-adapted indeterminate gametophyte1 (ig1) gene-based paternal haploid inducer lines in maize through molecular breeding - Amitkumar D. Kyada; Vignesh Muthusamy; Rashmi Chhabra; Botta T. Ganesh; Gulab Chand; Gaurav Sharma; Hriipulou Duo; Govinda R. Sarma; Ravindra K. Kasana; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (Planta, 2026)

Lagrangian reconstruction of fine-grid sea surface salinity from SMAP and altimetry in the Bay of Bengal - Jai Kumar; Neeraj Agarwal; Rashmi Sharma (Ocean Dynamics, 2026)

Oral Administration of Different Forms of Exogenous Tau Protein Induces Multi-Organ Defects Across Developmental Stages in Drosophila melanogaster - Surajita Sahu; Hariharakrishnan Chidamabaram; Vaishnavi Ananthanarayanan; Tazeen Qureshi; SmitaEknath Desale; Madhura Chandrashekar; Rashmi Santhoshkumar; Monalisa Mishra; Subashchandrabose Chinnathambi (Neurotoxicity Research, 2026)

Phytochemical profiling and GC–MS analysis of leaf extracts of Cleisocentron pallens, a rare epiphytic orchid of Assam, India - Jharna Bharali; Rashmi Gaur; Dharitri Borgohain (Plant Biosystems, 2026)

Multidrug-resistant tuberculosis: a comprehensive review of pathogenesis, drug resistance, current treatment and future prospects - Shweta Tiwari; Ankit Kumar Singh; Aarshu Acharya; Joyabroto Ghosh; Rashmi Prabha Singh (Archives of Microbiology, 2026)

Isolation, identification, and characterization of low-density polyethylene (LDPE) degrading bacterial isolates from a river water ecosystem - Maniket Chauhan; Rashmi Singh; Ankit Rohilla; Rakhi Nagar; Rajeev Kaul (Archives of Microbiology, 2026)

Food availability impacts oxygen isotope composition in freshwater snail shells - Tom de Vries; Rashmi T. Bopitiya; Sophia Weise; H. Jeroen L. van der Lubbe; Brendan Oerlemans; Frank J. C. Peeters; Suzan Warmerdam‐Verdegaal; Joris M. Koene; Niels J. de Winter (Limnology and Oceanography, 2026)
Freshwater mollusk shells serve as valuable archives for the reconstruction of past environmental conditions as they record water temperatures in their stable isotopic compositions during biomineralization. Yet, the impact of food availability on these isotopic records has never been fully explored. This study addresses that gap by investigating the effects of both temperature and food regime on the stable carbon (δ 13 C) and oxygen (δ 18 O) isotope compositions in the shells of the freshwater gastropod Lymnaea stagnalis . Under controlled laboratory conditions, snails were reared at six distinct temperatures and two food regimes (limited and unlimited). The results reveal strong but significantly different negative relationships between the δ 18 O fractionation factor and water temperature per food regime. The relationship for the limited food regime is expressed as: T (°C) = (19.99 ± 0.16) − (4.30 ± 0.16) × (δ 18 O a−w ) + (0.20 ± 0.09) × (δ 18 O a−w ) 2 . For the unlimited food regime as follows: T (°C) = (21.60 ± 0.24) − (4.33 ± 0.14) × (δ 18 O a−w ) + (0.20 ± 0.09) × (δ 18 O a−w ) 2 . This study identified a 1.63°C ± 0.03°C offset in predicted temperatures between the two food regimes likely due to metabolically induced changes to carbonate δ 18 O fractionation. This offset introduces a previously unrecognized source of uncertainty in paleotemperature reconstructions and underscores the need to account for food availability when interpreting δ 18 O data. In addition, δ 13 C values exhibit high variability and no significant correlation with temperature for both food regimes, probably because the effect of temperature is overprinted by that of metabolism.

A systematic review of global control and management strategies for water hyacinth (Pontederia crassipes) - Umar Saeed; Rashmi Das; Ashish Thapliyal; Ruchi Badola; Syed Ainul Hussain (Environmental Science and Pollution Research, 2026)

Comparative evaluation of direct in situ transesterification of wet and dry biomass for biodiesel production from a high-lipid-yielding Aspergillus terreus variant TB21 - Rashmi Karamchand Bed; V. Ravi Kumar; Ameeta RaviKumar (World Journal of Microbiology and Biotechnology, 2026)

Review of key diseases affecting temperate fruit crops and their sustainable management - E. R. Rashmi; Sajad Un Nabi; Arun Kishor; Chandni (Indian Phytopathology, 2026)

Unravelling the temporal accumulation of provitamin-A carotenoids and tocopherols during kernel development in biofortified sweet corn hybrids - Hema S. Chauhan; Vignesh Muthusamy; Tuhin Rashmi; Brijesh K. Mehta; Subhra J. Mishra; Abhijit K. Das; Rajkumar U. Zunjare; Ashok K. Singh; Hari S. Gupta; Firoz Hossain (Journal of Plant Biochemistry and Biotechnology, 2026)

Development and evaluation of sub-tropically adapted sweet corn hybrids for dual-purpose utilization with emphasis on yield and fodder quality traits - Puja Mandal; Babu Chakrapani; Vignesh Muthusamy; Brijesh Kumar Mehta; Parameshwaran Mathavaraj; Rashmi Chhabra; Senthil Natesan; Chandrakumar Kalichamy; Kumari Vinodhana Natarajan; Rajkumar Uttamrao Zunjare; Javaji Chandra Sekhar; Ravikesavan Rajasekaran; et al. (The Nucleus, 2026)

Antimicrobial resistance in Escherichia coli isolated from ready-to-eat indigenous dairy products - Ayantika Das; Manisha Behera; Rashmi Hogarehalli Mallappa; Mariya Divanshi; Shreya Saha; Jitesh Tarak; Pushpa Devi; Diwas Pradhan; Sachinandan De; Raghu Hirikyathanahalli Vishweswaraiah (International Dairy Journal, 2026)

Valorization of cashew nut processing residue for coloration, pest repellence, and UV protection of textiles - Ritu Pandey; Rashmi Dubey; Damini Saroj; Arpana Kamboj; Pramila Sheoran; Seiko Jose (Food and Bioproducts Processing, 2026)

Resistance-guided isolation and identification of antibiotic-resistant bacteria from bull semen: exploring alternatives to antibiotics in semen extenders - Dileep Kumar Yadav; H. M. Rashmi; Manisha Sethi; Ramasamy Arunkumar; Pawan Singh; Nishant Kumar (Tropical Animal Health and Production, 2026)

Toxicity evaluation of ultra-diluted methotrexate (12c and 30c): an acute and subacute oral toxicity study in animals - Pranjal Gujarathi; Rashmi Korat; Piyush Gujarathi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Soft computing framework-optimized ZIF-8 mixed matrix membrane for integrated CO2 capture and industrial wastewater mineralization - K. Rashmi; D. Sreenivasulu; M. Nagaraj; H. T. Avinash (Clean Technologies and Environmental Policy, 2026)

Novel Mannich based derivatives of isoliquiritigenin and liquiritigenin, bioactive constituents of Glycyrrhiza glabra , as potent antimalarial agents - Jyoti; Sana Khan; Subhasundar Maji; Harveer Singh Cheema; Feroz Khan; Rashmi Gaur; Rajendra Singh Bhakuni (Natural Product Research, 2026)

Abiotic Stress-Mediated Modulation of the tncRNome: Unraveling tRNA-Derived RNA Networks in Plant Adaptive Responses - Shafaque Zahra; Rashmi Gangwar; Sneha Tiwari; Dipul Kumar Biswas; Amarjeet Singh; Shailesh Kumar (Journal of Plant Growth Regulation, 2026)

Correction: Tailoring treatments: pharmacogenomics in the management of neurodegenerative diseases - Kishor Kumar Roy; Rashmi Kumari; Abhay Kumar Upadhyay; Satyajit Mohanty (Acta Neurologica Belgica, 2026)

Amphotericin B-cholesterol Co-encapsulated Polymeric Nanoparticles in Protein Hydrogel-based Injectable Depot System for Long-acting Drug Delivery - Sanat Kumar Dash; Rashmi Ghosh; Anil B. Jindal (AAPS PharmSciTech, 2026)

Rare-earth substituted Ni–Zn spinel ferrites for visible-light photocatalysis and environmental remediation: A comprehensive review - Rashmi Parmeshwar Ritapure; Bajarang Laxman Shinde (Next Research, 2026)

Is perioperative hypotension a risk factor for developing postoperative delirium in elderly patients after elective lumbar spine surgery? - Andrew Bisenius; Linder Wendt; Patrick Ten Eyck; Elyana Wohl; Yasser El-Hattab; Rashmi N. Mueller; Elena Garrido (Next Research, 2026)

Biochar as an adsorbent for microplastics present in aquatic environments: A comparative review between batch and column adsorption - Rohit Chandravanshi; Aradhana Tiwari; Ankesh Tiwari; Rashmi Dubey; Sudhir Kumar Pandey (Journal of Environmental Chemical Engineering, 2026)

Monitoring the morpho dynamics of nearshore environment utilizing a cost-effective video beach monitoring system - Madipally Ramesh; Chintam Venkateswarlu; Surisetty V.V. Arun Kumar; Baggu Gireesh; Chennu V. Naidu V.; L. Sheela Nair; Rashmi Sharma (Estuarine, Coastal and Shelf Science, 2026)

Geothermal heat flow in the Princess Elizabeth Land sector, East Antarctica - Devsamridhi Arora; Naresh Chandra Pant; Tobias Stål; Aditya Naik; Mayuri Pandey; Rashmi Gupta (Earth-Science Reviews, 2026)

Remarkable performance of flexible thermoelectric devices with inorganic chalcogenides and FC-CVD driven CNT sheets - Aarti Bisht; Vaishali Taneja; Manoj Sehrawat; Rashmi Rani; Hemant Sharma; Pankaj Kumar; Bhasker Gahtori; Bhanu Pratap Singh (Chemical Engineering Journal, 2026)

Prospects of biopolyester production from extremophiles using sustainable feedstocks - Aman Nanavaty; Vishal Kaushik; E. Hema Prasanth; Rohit Ruhal; Rashmi Kataria (Bioresource Technology Reports, 2026)

Structural Designing of FRP-Strengthened Resin-Infilled Flawed Sandstone Rock Against Adhesively Bonded Joint Region Interface Failure - Somanath Mohanty; Rashmi Ranjan Das (Rock Mechanics and Rock Engineering, 2026)

Monitoring and Projecting Land Use and Land Cover Dynamics Using Dual-Polarimetric SAR Data: A Case Study from 2016 to 2056 - Vijayasurya Krishnan; A. Rajesh; Rashmi Gopalan (Journal of the Indian Society of Remote Sensing, 2026)

Kernel-based 3-D coda (QC−1) mapping of the Eastern part of Kutch Rift Basin, NW India - Rashmi Singh; Uppala Srinu; Santosh Kumar; Sumer Chopra (Journal of Seismology, 2026)

Computational investigation of structural and functional impacts of L163G and W235K mutations in LRR-PGIP of Raphanus sativus: insights into host–pathogen interaction dynamics - Soumya Sharma; Mayank Rashmi; Mahender Kumar Singh; Sarika Sahu; Raja Shankar; Anurag Chaurasia; Girish Kumar Jha; Sunil Kumar (Journal of Plant Biochemistry and Biotechnology, 2026)

Biological Approaches to Carbon Sequestration and Bioenergy Production - Rashmi S. Dhanwar; Rupali Thakur; Ujjwala Waghmare; Adarsh K. Singh; Namita Singh; Gaurav Nahar; Andrew Ross; Munira Alateeqi; Om Prakash (Indian Journal of Microbiology, 2026)

Bioactive based formulations as an upcoming alternate to synthetic fungicides for postharvest management of Kinnow - Rashmi; Ritu Tandon; Anu Kalia; J. Nagendra Babu; Anjali (Indian Phytopathology, 2026)

Functional validation of OsRPM1 as a positive regulator of bacterial blight resistance in rice via virus-induced gene silencing - M Amrutha Lakshmi; Aditya Kulshreshtha; Kalyan K. Mondal; Indranil Dasgupta; Aditya Tyagi; Sanjeev Kumar; NS Kalaivanan; S Mrutyunjaya; B Sreenayana; ER Rashmi; Thungri Ghoshal; Neelam Jagram; et al. (Folia Microbiologica, 2026)

Advancing Second-Life Lithium-Ion Batteries for a Circular Energy Economy through Diagnostic Economic and Policy Pathways - Ritesh Kumar Upadhyay; Rashmi Kumari; Sutapa Mondal; Abinash Jena; Shatrudhan Pandey (Circular Economy and Sustainability, 2026)

Exploring Thematic Diversity and Evolution of Circular Economy using BERTopic Modeling - Sneha Jitendrabhai Kamani; Bhumi Vyas; Debidutta Pattnaik; Rashmi Kumari; Shatrudhan Pandey (Circular Economy and Sustainability, 2026)

Initial verification of OCM-3 Derived Results and Expectations for Essential Climate Variables - Anurag Gupta; Debojyoti Ganguly; Syed Moosa Ali; K. N. Babu; Mini Raman; Pradeep Thapliyal; Rashmi Sharma (Remote Sensing in Earth Systems Sciences, 2026)

Transcriptome analysis of Bipolaris sorokiniana-wheat reveals mechanisms of interaction - Malkhan Singh Gurjar; Shweta Agarwal; Sapna Sharma; Aditya Tyagi; Poulami Basak; Mahender Singh Saharan; Rashmi Aggarwal (Physiological and Molecular Plant Pathology, 2026)

tca-miR-137-5p modulates phosphine resistance by targeting CYP346B3 in Tribolium castaneum - Sheung Taek Oh; Rashmi Manohar Mahalle; Jun Won Shin; Keon Mook Seong (Journal of Stored Products Research, 2026)

24-Epibrassinolide Protects Against Sclerotia Stem Rot and Alternaria Leaf Spot in Brassica juncea L - Shashi Shekhar; Rashmi Chaudhary; Deepak Kumar; Prashasti Pandey; Ravi Rajwanshi; Anjana Rustagi (Journal of Plant Growth Regulation, 2026)

Barley intercropped with undersown species in northern Europe: a modest yet positive impact on carbon dioxide uptake during the shoulder seasons - Stephanie Gerin; Liisa Kulmala; Mika Korkiakoski; Rashmi Shrestha; Helena Rautakoski; Paula Thitz; Jari Liski; Jussi Heinonsalo; Annalea Lohila (Agriculture, Ecosystems & Environment, 2026)

Recent Progress in the Microbial Production and Applications of Indole Alkaloids - Chrisbel Ponmudiraj; June Susan Abraham; Rashmi Ramakrishnan; Jameel M. Al-Khayri; Praveen Nagella (Indian Journal of Microbiology, 2026)

Occurrence and characterization of multidrug resistant Shigella spp. in a dairy farm environment: a one health perspective - Aishwarya Muniraju; Namita Narwal; Shreya Saha; Harshitha Ponnachettira Ramesh; Rushikesh Deshmukh; Pradeep Jaybhaye; Diwas Pradhan; Shilpa Vij; Rashmi Hogarehalli Mallappa; Raghu Hirikyathanahalli Vishweswaraiah (Environmental Monitoring and Assessment, 2026)

Emerging technologies for urine wastewater recycling in space exploration: A comprehensive review - Rashmi Ranjan; Swatantra P. Singh (Journal of Environmental Chemical Engineering, 2026)

Intranasal curcumin mitigates paraquat-induced oxidative lung damage via involvement of neutrophil extracellular traps (NETs) in mice model - Shalini Singh; Diksha Sharma; D. Dash; Rashmi Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Potential Toxic Elements Pollution, Fractionation, and Associated Ecological Risks in Sediments of the Punpun River: A Tributary of the River Ganga, India - Rashmi Ranjan; Avinash Dass; Alok Kumar; Rajesh Kumar Ranjan (International Journal of Environmental Research, 2026)

Chemical characterization of air and soil contaminants associated with menstrual hygiene products - Pavithra Shankarappa; Rashmi Shenoy; Sangeeta Amaravati; Savithri Bhat (Environmental Science and Pollution Research, 2026)

A Socio Technical Framework for Integrating Industry 4.0 and Green HRM Through AI for Sustainable Circular Economy Transitions - Rashmi Kumari; Sujata Priyambada Dash; Saileja Mohanty; Shatrudhan Pandey (Circular Economy and Sustainability, 2026)

Review on bioactive compounds of medicinal plants with antiviral properties against Newcastle disease virus (NDV) - Rashmi Singh; S. S. Sonu; Latha Rangan (Archives of Virology, 2026)

Optimization of Yield and Quality Through Foliar Application of Water-Soluble Fertilizers in Strawberry (Fragaria × Ananassa Duch.) Cv. Camarosa - Latesh Kumar; B. P. Bisen; Amul Yadav; Rashmi Bhumarkar; Anil Chouhan; Homeshvari (Applied Fruit Science, 2026)

Environmental and Lifestyle Exposures and Male Factor Subfertility Proportion Among Infertile Couples: A Clinic-Based Multicenter Cross-Sectional Analysis from Indian Male Factor Subfertility Evaluation (IM-FaST) Study - Naina Kumar; Neha Gangane; Shikha Seth; Lajya Devi Goyal; Vijayan Sharmila; Priyanka Rai; Sarita Agrawal; Anupama Bahadur; Kubera Siddappa Nichanahalli; Pratibha Singh; Vaibhav Kanti; Sayanti Paul; et al. (Environmental Science and Pollution Research, 2026)

Calibration of TIGGE ensemble precipitation forecasts using Bayesian model averaging for a semi-arid river basin - Rashmi Yadav; Sanjaykumar M. Yadav (Acta Geophysica, 2026)

In vitro antibacterial activity and in silico validation of phytocompound Emodin from Rheum Emodi Wall. Ex Meissn. against Staphylococcus aureus and Enterobacter cloacae - Rashmi Ramesh; Aditya Chandrashekar; Monnanda Somaiah Nalini; Shubha Gopal (World Journal of Microbiology and Biotechnology, 2026)

Unveiling the Link Between Expression of Aspartate Kinase2 (ask2) Gene and Accumulation of Methionine in Developing Maize Kernels - Hriipulou Duo; Rashmi Chhabra; Rajkumar U. Zunjare; Gaurav Sharma; Subhra J. Mishra; Vignesh Muthusamy; Firoz Hossain (Biochemical Genetics, 2026)

Shoreline dynamics and beach topography analysis using video beach monitoring and CoastSnap tools at a blue flag beach on India’s east coast - Baggu Gireesh; Madipally Ramesh; Surisetty V.V. Arun Kumar; Chintam Venkateswarlu; Chennu V. Naidu; Leela Sheela Nair; Rashmi Sharma (Regional Studies in Marine Science, 2026)

Synergistic role of biopriming in boosting legume crop performance: A review - Rashmi Jha; V. Manonmani; K. Sundaralingam; S. Vanitha; M. Gnanachitra; T. Kalaiselvi (Physiological and Molecular Plant Pathology, 2026)

Efficacy of a tebuconazole-copper-boron formulation against termites and wood borers in Ailanthus excelsa and Mangifera indica - Jyoti Papola; Rashmi Ramesh Shanbhag; R. Sundararaj; Anil Kumar Sethy; Rakesh Kumar (Journal of Asia-Pacific Entomology, 2026)

Optimizing the rice yield under future climate: joint insights for India and Sri Lanka - Ankit Balvanshi; Rashmi Patil; Harikumar Mohanan; Hari Lal Tiwari; K. V. Jayakumar; Venkappayya R. Desai (Regional Environmental Change, 2026)

Development of an efficient in vitro apical meristem-based regeneration system in tomato (Solanum lycopersicum L.) - Rashmi Kaul; Arulprakash Thangaraj; Jyotsna Bharti; Rachana Verma; Puja Chakraborty; Isha Gupta; R. Shubhra Maithreyi; Sugyan Preet; Shivani Sharda; Tanushri Kaul (Plant Physiology Reports, 2026)

Enhanced ocular delivery of brinzolamide via β-cyclodextrin-based micelles for glaucoma management - Rashmi Maurya; Akash Vikal; Raj Kumar Narang; Preeti Patel; Balak Das Kurmi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Terminal high temperature stress implications in wheat development: superior thermotolerance is linked to water status and antioxidant efficiency - Rashpal Kumar; Rashmi Saini; Arindam Adhikary; Sanjeev Kumar (Journal of Plant Biochemistry and Biotechnology, 2026)

Representation of flavours of El Niño in CMIP6-DCPP lead year-1 hindcasts - Rashmi Kakatkar; C. Gnanaseelan (Climate Dynamics, 2026)

Taxonomic and Phylogenetic Contributions to Bambusicolous Mycobiota: A Novel Species and a New Record of Dictyoarthrinium (Didymosphaeriaceae, Pleosporales, Dothideomycetes) from India - Rashmi Dubey; Sayantan Jash; Amit D. Pandey (New Zealand Journal of Botany, 2026)
Bamboo species serve as hosts to diverse microfungi, with the genus Dictyoarthrinium being a prevalent member. This paper introduces Dictyoarthrinium bambusae as a new species and reports D. thailandicum as a new record for India, both identified from bamboo species in Goa. These taxa were identified based on phylogenetic analyses of nuclear ribosomal DNA (LSU, SSU, and ITS) and protein‐coding genes (TEF1‐ α ), plus morphological comparisons. This finding contributes to the growing knowledge on the microfungal diversity associated with bamboo species, emphasising the role of bamboos as distinctive habitats for fungal communities.

Exogenous 28-Homobrassinolide as a key ameliorative agent in shielding Vigna radiata seedlings against Pb stress - Isha Madaan; Gurvarinder Kaur; Palampreet Singh; Shruti Kaushik; Rashmi Mishra; Renu Bhardwaj; Geetika Sirhindi (Biologia, 2026)

Tailoring treatments: pharmacogenomics in the management of neurodegenerative diseases - Kishor Kumar Roy; Rashmi Kumari; Abhay Kumar Upadhyay; Satyajit Mohanty (Acta Neurologica Belgica, 2026)

Dual action of N-acetyl cysteine as antimicrobial and anti-inflammatory agent for bovine mastitis management - V. Mounica; H.M. Rashmi; A. Manimaran; S. Komala; Mamta Chauhan (Next Research, 2026)

Targeted mutagenesis in glutamine synthetase for improved herbicide resistance and nitrogen utilization in maize - Sneha Murmu; Mayank Rashmi; Santosh Kumar Behera; Sunil Kumar; Girish Kumar Jha; Jyoti Kumari; Gyan Prakash Mishra; P.V. Vara Prasad (Biocatalysis and Agricultural Biotechnology, 2026)

Vulvovaginal candidiasis in rural pregnant populations from Uttar Pradesh, India: species shift, biofilm formation, and resistance trends - Soha Abdallah Moursi; Rashmi Saxena; Fareya Haider; Mohd Shahid Khan; Mohd Saleem; Irfan Ahmad; Nadeem Ahmad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of subtropical breeding lines for ideal plant architecture in maize through multiple selection indices - Govinda Rai Sarma; Rajkumar U. Zunjare; Vignesh Muthusamy; Ravindra K. Kasana; Ikkurti Gopinath; Bhavna Singh; Godawari S. Pawar; Neha Sharma; Hriipulou Duo; Rashmi Chhabra; Rakesh K. Devlash; Satish K. Guleria; et al. (Journal of Applied Genetics, 2026)

Arsenic Bioaccumulation in Cattle Naturally Exposed to Geogenic Groundwater Contamination in the Middle Indo-Gangetic Plains of Bihar - Ravi Kumar; Rashmi Rekha Kumari; Nirbhay Kumar; Archana; Ramesh K. Nirala; Kumari Anjana; Govind Kumar Choudhary; Tapan Kumar Mandal; Pankaj Kumar (Bulletin of Environmental Contamination and Toxicology, 2026)

Association of Interleukins 17A and 17F Gene Polymorphism with Asthma: A Case Control Study in North Indian Population - Rashmi Pandey; Ved Prakash (Indian Journal of Clinical Biochemistry, 2026)

Hesperidin Supplementation During Alternate Day Fasting Provides Synergistic Effect in Conferring Neuroprotection to Aging Rats - Sukanya Bhoumik; Rashmi Kesherwani; Syed Ibrahim Rizvi (Indian Journal of Clinical Biochemistry, 2026)

Sustainable removal of arsenic and mercury via integrated phytoremediation and biomass valorization of Eichhornia crassipes - Rashmi Ranjan Mandal; Deep Raj (Applied Geochemistry, 2026)

Elucidating the Effect of Ocimum Viride Essential Oil and Eugenol Based Nanoemulsions On the Postharvest Quality and Shelf Life of Kinnow Mandarin - Manjinder Kaur; Ritu Tandon; Anu Kalia; Rashmi; Bal Vipan Chander Mahajan (Applied Fruit Science, 2026)

A multidimensional approach to manage rip current danger and enhancing safety at beaches - Surisetty V V Arun Kumar; Madipally Ramesh; Chintam Venkateswarlu; B Gireesh; T Sridevi; L Sheela Nair; Sanjib Kumar Deb; C V Naidu; Rashmi Sharma (Journal of Earth System Science, 2026)

Metagenomics Approach for Identification of Relationship Between Gut Microbiome and Milk Productivity in Dairy Cattle - Harmeet Singh Dhillon; Pradip Vishnu Behare; Hogarehalli Mallapa Rashmi; Jai Kumar Kaushik; Sachinandan De; Sachin Kumar; Udeybir Chahal; Ratna Prabha; Anil Kumar Puniya (Indian Journal of Microbiology, 2026)

Green corrosion inhibition of mild steel in acidic media: electrochemical behavior and theoretical studies of Zingiber mioga essential oil - Lalrin Tluangi; Raj Kumar Mishra; Jay Prakash Rajan; Manisha Malviya; Raghvendu Pathak; Ashish Kumar Singh; Rashmi Sehrawat; Dinesh Kumar Sharma; Sunil Kumar Pandey; Bindu Mangla; Ved Prakash Singh (Environmental Science and Pollution Research, 2026)

Numerical analysis of rip currents at RK Beach, Visakhapatnam, India using XBeach model - Sivaiah B; Surisetty V.V. Arun Kumar; Muhammad Zahir Ramli; Mohd Shahrizal Ab Razak; K. Siva Srinivas; Pottapinjara V; T. Sridevi; Rashmi Sharma; B. Ajay Kumar; V. Raam Balaji; P.S.N. Acharyulu; K. Venkateswara Rao; et al. (Regional Studies in Marine Science, 2026)

Triumphing over hidden hunger: Redesigning rice (Oryza sativa L.) for enhanced nutraceutical grain composition utilizing multiplexed genome editing - Khaled Fathy; Jyotsna Bharti; Sonia Khan Sony; Mamta Nehra; Rashmi Kaul; Bhupendra Rawat; Sudhir K. Sopory; Pawan Kumar Agrawal; Arul Prakash; Tanushri Kaul (Journal of Plant Physiology, 2026)

Degraded land: Assessment, impact, restoration, and challenges - Gulshan Kumar Sharma; Dinesh Jinger; I. Rashmi; Manoj Kumar; Nandha Kumar Natrajan; Roomesh Kumar Jena; Raj Kumar; Suresh Kumar; Kavita Kumari; Rajesh Kaushal; Anupam Barh; Trisha Roy; et al. (Journal of Environmental Management, 2026)

Efficient activity of uracil DNA glycosylase (UNG2) in proliferating cells requires binding to proliferating cell nuclear antigen (PCNA) and replication protein A (RPA) - Rashmi S. Kulkarni; Brian P. Weiser (DNA Repair, 2026)

Unravelling the nutraceutical and therapeutic perspectives of corosolic acid: Journey so far and the road ahead - Sachin Kumar Singh; Pavankumar Chintamaneni; Vinoth Kumarasamy; M V N L Chaitanya; Rashmi Saxena Pal; Saranya Punniyakotti; Sukriti Vishwas; Avijit Mazumder; Prathiba Pandey; Smriti Arora; Amandeep Singh; Navneet Khurana; et al. (Phytochemistry Reviews, 2026)

Naringin alleviates fluoride-induced neurodevelopmental disorders by modulation of SIRT1, autophagy, mitochondrial fission, and ROS generation - Vishal Chhabra; Ravindra Shantakumar Swamy; Annem Ravi Teja Reddy; Rashmi Bhushan; Smita Shenoy; Shreya Maiti; Abubakar; Sarasa Meenakshi; Krishna Murti; Nitesh Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

PIWI–piRNA Axis in Epilepsy: Bridging Epigenetic Regulation, Neuroinflammation, and Neuronal Excitability - Mukul Shyam; Rashmi Rashmi; Vidhi Sharma; Rajendran Venkatesh; Aditi Jain; Yaazhini G; Abilash Valsala Gopalakrishnan; Prathap Srirangan; Sabina Evan Prince (Molecular Neurobiology, 2026)

NETosis in Alzheimer’s Disease: Understanding the Role of Neutrophil Extracellular Traps (NETs) in Neuroinflammation and Disease Pathogenesis - Rashmi Rao; Harkomal Verma; Prabhakar Gangwar; Anuradha Yadav; Bharti Yadav; Anushka Patel; Sharanjot Kaur; Monisha Dhiman; Anil Kumar Mantha (Molecular Neurobiology, 2026)

Salicylic Acid: A Key Player in the Regulation of Interactions Between Heat Stress and Plant Defense - Rashmi Banoriya; Maya Chandra; Zeba Quaiyum; Praful Mukund Damdar; Saurabh Pandey; Ashutosh Singh (Journal of Plant Growth Regulation, 2026)

QTL mapping in plants: challenges and opportunities in the genomic era - Anil Kumar Singh; Nandita Banerjee; Rashmi Rai; Kumari Shikha; Saurabh Singh; Ya-ping Lin; Ramakrishnan M. Nair; Sanjeev Kumar (Euphytica, 2026)

Source attribution and health risk assessment of potentially toxic elements in the vicinity of coal-fired thermal power plants: an extensive study to comprehend the pollution load on lentic and lotic ecosystems - Rashmi Ranjan Mandal; Deep Raj (Environmental Geochemistry and Health, 2026)

Comparison of ensemble prediction systems with reference to the hydrological response for a major flood event in Vishwamitri river basin - Rashmi Yadav; Sanjaykumar M. Yadav (Earth Science Informatics, 2026)

What goes down may come up: regurgitative behaviors and their underlying gut–brain axes—insights from genetic models and related pathologies - Rashmi Karunakaran; Neena Baburaj; Aditi Manjare; Gaurav Das (Journal of Comparative Physiology A, 2026)

Impact of spatial and temporal resolution of satellite sea surface salinity measurements on ocean state prediction in the Tropical Indian Ocean; an OSSE framework using SMOS - M. Jishad; Smitha Ratheesh; Neeraj Agarwal; Neerja Sharma; Rashmi Sharma (Advances in Space Research, 2026)

Redefining acne treatment: emerging role of probiotics in dermatology - Milind Umekar; Anis Chaudhary; Shreya Koche; Damini Dhule; Supriya Shidhaye; Ruchi Khobragade; Smita Bonde; Hassan Ahmed Rudayni; Mohamed A. M. Ali; Rashmi Trivedi (Archives of Microbiology, 2026)

Nano-boosted quercetin: A modern Chinese herb to overcome drug-resistant breast cancer - Akash Vikal; Rashmi Maurya (Next Research, 2025)

Subduction polarity reversals around the Solomon Island Arc associated with interaction of mantle domains in the Southwest Pacific - Rashmi Battan; Sun-Lin Chung; Tsuyoshi Komiya; Shigenori Maruyama; Truong Tai Nguyen; Hao-Yang Lee; Yoshiyuki Iizuka; Kwan-Nang Pang; Andrew Tien-Shun Lin (Lithos, 2025)

Harnessing the synergistic advantages of functional modified (defect generated, Ni and S co-doped) TiO2/NiS S-scheme photocatalyst and halloysite nanotube support for efficient photodegradation of several volatile organics - Dani S. Assi; Vaithinathan Karthikeyan; Padmanaban Radhakrishnan; Venkatramanan Kannan; Rashmi Mannu; Chongkol Sungoum; Vaskuri C.S. Theja; Gopalan Anantha Iyengar; Dong-Eun Lee; Vellaisamy A.L. Roy (Journal of Environmental Chemical Engineering, 2025)

Dynamics of carbon dioxide capture in two halotolerant strains of Chlorella vulgaris - Faqih Shuhaili; Mathumathy Srinivasan; Rashmi Vijayaraghavan; Mariona Segura-Noguera; Uma Lakshmanan; Dharmar Prabaharan; Seetharaman Vaidyanathan (Journal of Environmental Chemical Engineering, 2025)

Neuroprotection via gut microbiota: Role of curcumin and resveratrol: An updated systematic review - Rashmi Pauline; Karthikeyan Murugesan; Anjuna Radhakrishnan; Deepa Kandaswamy; Lali Growther; Priyanka Ganapathy; Gowtham Kumar Subbaraj (Food and Humanity, 2025)

Development of B cell medicine cryopreservation process - Mark Lalli; Jordan Smelker; Rashmi Kshirsagar (Cryobiology, 2025)

Harnessing the potential of invasive plants biomass for biochar production and coal-mine spoil reclamation: A review - Aradhana Tiwari; Mohineeta Pandey; Ankesh Tiwari; Astha Tirkey; Rohit Chandravanshi; Rashmi Dubey; Sudhir Kumar Pandey (Bioresource Technology Reports, 2025)

Long term (2003–2023) analysis of Black Carbon aerosols and its impact on cloud characteristics over a highly polluted Delhi mega city of India - Lakshmi; Rashmi Deshwal; Vijay Kumar Soni; Adarsh Kumar (Atmospheric Environment, 2025)

Molecular delineation, development and validation of functional markers for brachytic2 (br2) gene governing dwarfing plant height in maize - Govinda Rai Sarma; Rashmi Chhabra; Vignesh Muthusamy; Shanmugavadivel P. Subramaniam; Gaurav Sharma; Hriipulou Duo; Vinay Rojaria; Rajkumar U. Zunjare; Viswanathan Chinnusamy; Firoz Hossain (Physiology and Molecular Biology of Plants, 2025)

Fruit-specific expression of SlDREB3 enhances the post-harvest life of fruits in tomato and overcomes abnormalities in seed germination and vegetative growth - Rakhi Prabhakar; Rashmi Singh; Asmita Gupta; Rambir Singh; Aniruddha P. Sane (Physiology and Molecular Biology of Plants, 2025)

Investigating postbiotics as innovative adjuvants: deciphering the gut-breast connection in breast Cancer therapy, from gut microbiome to personalized medicine - Rashmi Ghosh; Debayan Sil; Rohit Sharma; Dinesh Kumar; Kumari Komal; Sourabh Kumar; Hitendra S Mahajan; Manu Sharma; Manish Kumar (Molecular Biology Reports, 2025)

Molecular characterization of T-, C- and S- specific cytoplasmic male sterile (CMS) maize inbreds using mitochondrial SSRs for its utilization in baby corn breeding - Saikat Pal; Rajkumar Uttamrao Zunjare; Vignesh Muthusamy; Munegowda Manoj Gowda; Hriipulou Duo; Rashmi Chhabra; Ravindra Kumar Kasana; Shalma Maman; Ashvinkumar Katral; Prolay Kumar Bhowmick; Firoz Hossain (Molecular Biology Reports, 2025)

Exploring the role of pomalidomide in androgen-dependent prostate cancer: a computational analysis - Shivani Pathak; Vipendra Kumar Singh; Prashant Kumar Gupta; Arun Kumar Mahapatra; Rajanish Giri; Rashmi Sahu; Rohit Sharma; Neha Garg (Molecular Diversity, 2025)

Mitochondrial disease management through phytochemical interventions - R. Prabhu Ramya; K. B. Megha; S. Reshma; M. J. Ajai Krishnan; S. Amir; Rashmi Sharma; P. V. Mohanan (Molecular and Cellular Biochemistry, 2025)

Evaluation of SWOT Beta Geophysical Products in the Indian Region During CAL-VAL Phase over the Land and Oceans - Aditya Chaudhary; Shard Chander; Arun Kumar Surisetty; Ritesh Agrawal; Neeraj Agarwal; Praveen Kumar Gupta; Raj Kumar; Rashmi Sharma; R. Venkat Shesu; T. V. S. Udaya Bhaskar; E. Pattabhi Rama Rao (Journal of the Indian Society of Remote Sensing, 2025)

Landslide Susceptibility Analysis of a Part of Western Ghats in South-Western India Using Geospatial Techniques: A Comparison of AHP and Logistic Regression Methods - Rashmi Chandan; Kizhur Sandeep; Chandan Kumar Boraiaha (Journal of the Indian Society of Remote Sensing, 2025)

Leaf spot in tissue culture banana caused by Pyricularia angulata: identification and control strategies - Alan C. Antony; Vimi Louis; C. R. Rashmi; R. Rahila; Sible George Varghese (Indian Phytopathology, 2025)

Enrichment of phytoglycogen in sweet corn kernels through genomics-assisted selection - Rashmi Chhabra; Rajkumar U. Zunjare; Irum Gul; Subhra J. Mishra; Hriipulou Duo; Vinay Bhatt; Nisrita Gain; Ravindra K. Kasana; Vignesh Muthusamy; Firoz Hossain (Functional & Integrative Genomics, 2025)

Genomics-assisted stacking of waxy1, opaque2, and crtRB1 genes for enhancing amylopectin in biofortified maize for industrial utilization and nutritional security - Subhra J. Mishra; Firoz Hossain; Rajkumar U. Zunjare; Rashmi Chhabra; Ashvinkumar Katral; Ikkurti Gopinath; Vinay Bhatt; Govinda Rai Sarma; Zahirul A. Talukder; Ravindra K. Kasana; Elangbam L. Devi; Konsam Sarika; et al. (Functional & Integrative Genomics, 2025)

Emerging Pollutants in Soil and Water: Sources, Risks, and Advances in Removal Technologies for Sustainable Management - Rashmi Singh; M. K. Harsha Varthan; R. S. Rejith Kumar; M. Rohinth; Z. H. Tawfeeq Ahmed; S. M. Indumathi; Suvarshitha Pusuluru; Sai Kumar Punna; Karrun Velmurugan; Melvin Samuel; Selvarajan Ethiraj (Environmental Management, 2025)

Msst-eegnet: multi-scale spatio-temporal feature extraction using inception and temporal pyramid pooling for motor imagery classification - Rashmi Mishra; R. K. Agrawal; Jyoti Singh Kirar (Cognitive Neurodynamics, 2025)

Energy and exergy analysis of a novel triple-tube-based organic Rankine cycle for combined heat and power generation - Rashmi Rekha Sahoo; Sunil Kumar Gaur (Clean Technologies and Environmental Policy, 2025)

Ergosterol Regulation of Plant Physiology; An Underlooked Perspective - Mittali Tyagi; Prabir Kumar Paul; Rashmi Rameshwari (The Botanical Review, 2025)

Molecular insights into GnRH3-associated peptide structure and reproductive responses in Channa striata stimulated with sGnRH analogue - Prachi Asgolkar; Kiran D. Rasal; Rajesh Kumar; Uday Udit; Arvind Sonwane; Manoj Brahmane; Sunil Kumar; Mayank Rashmi; Girish Kumar Jha; Jitendra Kumar Sundaray; Megha Bedekar; Mukunda Goswami (Aquaculture International, 2025)

Isolation and characterization of a potent anticancer fraction from Clinacanthus nutans targeting MCF-7 and A549 cells: an integrated in vitro and in silico study - Sushma Jahagirdar; Smitha S. Bhat; R. Sindhu; Sarana Rose Sommano; Rashmi Doddabassappa; Pradeep Matam; Nishanth Bhat; Shashanka K. Prasad (In Silico Pharmacology, 2025)

Synthesis, molecular modelling studies of artemisinin-chalcone derivatives and their antimalarial activity evaluation - Rashmi Gaur; Jyoti; Sana Khan; Harveer Singh Cheema; Feroz Khan; Mahendra Padurang Darokar; Rajendra Singh Bhakuni (Natural Product Research, 2025)

Genetic comparison of virulence and resistance factors in phylogenetically diverse Escherichia coli from dairy cattle - Namita Narwal; Chanchal Rana; Monica Rose Amarlapudi; Anil Kumar Puniya; Raghu Hirikyathanahalli Vishweswaraiah; Rashmi Hogarehalli Mallappa; Sachinandan De; Diwas Pradhan (Science of The Total Environment, 2025)

Soil surface management for enhanced morpho-physiological traits, yield and water use efficiency of chickpea: A sustainable and climate resilient strategy - Anita Kumawat; I. Rashmi; Shakir Ali; Kuldeep Kumar; Ashok Kumar; Devideen Yadav; M. Madhu; Rahul Sadhukhan; R.A. Jat; G.L. Meena; G.K. Sharma; S. Kala (Field Crops Research, 2025)

Short-term exposure to particulate matter (PM10/2.5) from Varanasi, India led to asthma aggravation and early fibrotic changes in mice model: Insights into its regulation - Diksha Sharma; Payal Singh; Prashant Kumar Chauhan; Vandana Soni; Abhay Kumar Singh; Rashmi Singh (Atmospheric Environment, 2025)

Oxidative stress and pancreatic cancer: a dual role in tumorigenesis and drug toxicity - Khem Raj Limbu; Rashmi Bhandari Chhetri; Yoon Sin Oh; Min-Ho Oak; Dong Jae Beak; Eun-Young Park (Toxicological Research, 2025)

Improving drought tolerance in rice seedlings through melatonin-induced alterations in root architecture, photosynthetic and antioxidant enzymes - Milan Kumar Lal; Ujala Rashmi Sahoo; Laxmipriya Behera; Bandana Mohapatra; Awadhesh Kumar; Rupak Jena; Koushik Chakraborty; Rahul Kumar Tiwari; Ravinder Kumar; M. J. Baig (Physiology and Molecular Biology of Plants, 2025)

Advancing nearshore wave monitoring: estimating parameters through video time stack imagery - Chintam Venkateswarlu; Baggu Gireesh; Madipally Ramesh; Surisetty VV ArunKumar; Chennu V. Naidu; Leela Sheela Nair; Rashmi Sharma (Ocean Dynamics, 2025)

Comprehensive advances in HER2-positive and HER2-negative breast cancer: unveiling molecular mechanisms and exploring cutting-edge targeted therapies for enhanced patient outcomes - Nayan Sood; Rashmi Maurya; Shreastha Gautam; Preeti Patel; Ghanshyam Das Gupta; Balak Das Kurmi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Impact of satellite derived wind and LULC on coastal inundation: a sensitivity study for the east coast of India - Anup Kumar Mandal; Pawan Tiwari; Ambarukhana D. Rao; Rashmi Sharma; Prasad K. Bhaskaran (Natural Hazards, 2025)

A broad climatology of very high latitude ( ∼ 75 ° ) substorms: An update - Anand K. Singh; Navin Parihar; Shailendra Saini; Sunil Kumar; Rashmi Rawat; Vladimir Belakhovsky; Wojciech J. Miloch; Gopi Seemala; A.K. Sinha (Advances in Space Research, 2025)

Inventory automation and sustainable supply chain performances: a systematic review on emerging countries - Rashmi Ranjan Panigrahi; Avinash K. Shrivastava (Environment, Development and Sustainability, 2025)

Evaluating the effectiveness of limestone and eggshell waste as cement replacements — a review - Maria Vanitha Rashmi Rakesh; Nandhini Kumar (Environmental Science and Pollution Research, 2025)

Towards sustainable battery recycling: Investigating ammonium-based deep eutectic solvents for NMC cathode material recovery - Rabiah Nizah Md Fahmy; Rashmi Walvekar; Foo Chuan Yi; Lai Yong Ler; Mohammad Khalid (Journal of Environmental Chemical Engineering, 2025)

Bifunctional Co0.75Fe0.25@C nanocomposite towards zero waste approach: Organic pollutants removal and OER electrocatalysis - Sai Rashmi Manippady; Sayali Ashok Patil; S. Akhila; Aditi Das; Velvita Dias; Akshaya Kumar Samal; Rupesh S. Devan; Manav Saxena (Journal of Environmental Chemical Engineering, 2025)

Development and evaluation of PANI-PecPaper strip sensor for detection of total plate count in milk and milk products - Shreya Saha; Mohit Singh; Maharshi Prajapathi; Rashmi Hogarehalli Mallappa; Naresh Kumar; Rajan Sharma; Anjali M. K; Raghu Hirikyathanahalli Vishweswaraiah (Food Control, 2025)

Optimizing jaggery mediated textile dyes treatment: Cost-effective process innovation and microbial community impact analysis - Rashmi S. Rokade; Ashvini U. Chaudhari; Swapnil M. Patil; Sanjay P. Govindwar; Jyoti P. Jadhav (Chemical Engineering Journal, 2025)

Accelerated development of MTL and DMP gene-based subtropically-adapted maternal haploid inducer lines in maize using molecular breeding - Nisrita Gain; Vignesh Muthusamy; Rashmi Chhabra; Amitkumar D. Kyada; Suman Dutta; Gulab Chand; Ravindra K. Kasana; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar Subramani; Rajkumar U. Zunjare; et al. (Planta, 2025)

Efficient induction of parthenogenetic haploids in African marigold (Tagetes erecta) L.) using Co60 gamma-irradiated pollen of French Marigold (Tagetes patula L.) - Eram Arzoo; Kavita Dubey; Rashmi Arora; Kanwar Pal Singh; Sapna Panwar; Akshay Talukdar; Bhupinder Singh; Mahesh Rao; Mariyam Firdous; Bharti Juneja; Reeta Bhatia (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

An In Vivo C57BL/6 Mouse Study Demonstrating Fine-Tuning of Serum and Brain-Derived Exosomes Reveal Therapeutic Potential of Phytochemical Ferulic Acid Against Alzheimer’s Disease - Harkomal Verma; Maanvi Dhureja; Anuradha Yadav; Bharti Yadav; Rashmi Rao; Monisha Dhiman; Puneet Kumar; Anil Kumar Mantha (Molecular Neurobiology, 2025)

SARAL/AltiKa–An Unprecedented Journey for Monitoring Global Sea Levels and Serving Ocean Applications - Suchandra A. Bhowmick; Aditya Chaudhary; M. Seemanth; Smitha Ratheesh; K. M. Sreejith; V. P. Krishna; P. G. Remya; Imranali M. Momin; Honey Gupta; J. V. Thomas; Neeraj Agarwal; Rashmi Sharma; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Examining factors influencing injury severity patterns and proposing safety strategies for long-haul truck drivers in India: an association rule mining approach - Balamurugan Shandhana Rashmi; Sankaran Marisamynathan (Innovative Infrastructure Solutions, 2025)

Split quadrant mosaic algorithm: a novel approach to develop multi-model ensemble for wind resource assessment - Garlapati Nagababu; Preksha Patwa; Harish Puppala; V. V. Arun Kumar Surisetty; Surendra Singh Kachhwaha; Rashmi Sharma (Climate Dynamics, 2025)

Allelic Diversity and Development of Breeder-Friendly Marker Specific to floury2 Gene Regulating the Accumulation of α-Zeins and Essential Amino Acids in Maize Kernel - Hriipulou Duo; Rashmi Chhabra; Vignesh Muthusamy; Suman Dutta; Ashvinkumar Katral; Govinda Rai Sarma; Gulab Chand; Subhra J. Mishra; Rajkumar U. Zunjare; Firoz Hossain (Biochemical Genetics, 2025)

Therapeutic potential of Andrographis paniculata against Monkeypox virus targets—a computational insight - Rashmi Sahu; Rajan Mariappan; Awanish Kumar; Arun Kumar Mahapatra; S. Rajagopala; Prashant Kumar Gupta (In Silico Pharmacology, 2025)

Adaptability of rice to different planting methods: A proof of cumulative transcriptional memory - Karishma Seem; Ayantika Ghosh; Rashmi Varshney; Rakesh Pandey; S. Gopala Krishnan; Trilochan Mohapatra; Suresh Kumar (Plant Gene, 2025)

Nafithromycin: a potential ketolide antibiotic for combating antimicrobial resistance in community-acquired bacterial pneumonia - Dinesh Kumar; Debayan Sil; Rashmi Ghosh; Kumari Komal; Prachi Pandey; Ghanshyam Das Gupta; Manish Kumar (Next Research, 2025)

Simulation study of effect of absorber layer thickness and ambient temperature on photovoltaic performance of CZTSe solar cells - Vikas Kumar Rajput; Rashmi; Sandhya Mann; A.S. Mathur; B.P. Singh (Next Research, 2025)

A case report on ayurvedic management of paraparesis with lumbar radiculopathy - Dr. Payal Rathod; Dr. Amit Nakanekar; Dr. Rashmi Jaiswal (Next Research, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Surface engineering ‘liquid-like’ solid surfaces with nitric oxide releasing polymers to combat biofouling - Arpita Shome; Rashmi Pandey; Isabel Martinez; Natalie Crutchfield; Elizabeth J. Brisbois; Hitesh Handa (Chemical Engineering Journal, 2025)

Promotion for deep denitrification and sludge minimization by enhancing sulfur-driven endogenous carbon release and electron transport - Yu Cheng; Huiling Ren; Rashmi Koju; Haiyan Li; Chengzhi Hu (Chemical Engineering Journal, 2025)

Comprehensive insights into pancreatic cancer treatment approaches and cutting-edge nanocarrier solutions: from pathology to nanomedicine - Rohit Sharma; Sourabh Kumar; Kumari Komal; Rashmi Ghosh; Shubham Thakur; Ravi Raj Pal; Manish Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Initial Vicarious Calibration of Ocean Colour Monitor Onboard EOS-06 Using Ocean Site, Kavaratti - K. N. Babu; Saurabh Tripathi; Moosa Ali; Anurag Gupta; Debojyoti Ganguly; Ankur Garg; Tushar Shukla; Pradeep Kumar Thapliyal; Rashmi Sharma; Mini Raman; M. Arul Muthiah (Journal of the Indian Society of Remote Sensing, 2025)

Synergistic Use of Scatterometer and Ocean Colour Monitor Onboard EOS-06 Satellite for Various Oceanographic Applications - Neeraj Agarwal; Jishad M; Jai Kumar; Sanjiba Kumar Baliarsingh; Naga Swetha; Smitha Ratheesh; Suchandra Aich Bhowmick; Ratheesh Ramakrishnan; Abhisek Chakraborty; Rajesh Shikakoli; Manche Shiva Shankar; Reema Mathew; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Role of Additional Bands in Ocean Colour Monitor (OCM) on Board EOS-06 in Arabian Sea Near Gujarat Coast - Anurag Gupta; Debojyoti Ganguly; K. N. Babu; Mini Raman; Pradeep Kumar Thapliyal; Rashmi Sharma (Journal of the Indian Society of Remote Sensing, 2025)

Harnessing microRNAs and their targets for salt stress tolerance in Pandanus odorifer - Deo Rashmi; Vitthal T. Barvkar; Altafhusain B. Nadaf; Narendra Y. Kadoo (Journal of Plant Biochemistry and Biotechnology, 2025)

Unlocking the molecular pathway of atopic dermatitis: journey so far and roads ahead - Sourabh Kumar; Rohit Sharma; Kumari Komal; Dinesh Kumar; Rashmi Ghosh; Manish Kumar (Inflammopharmacology, 2025)

Refining methods for attributing health impacts to climate change: a heat-mortality case study in Zürich - Rupert F. Stuart-Smith; Ana M. Vicedo-Cabrera; Sihan Li; Friederike E.L. Otto; Kristine Belesova; Andy Haines; Luke J. Harrington; Jeremy J. Hess; Rashmi Venkatraman; Thom Wetzer; Alistair Woodward; Kristie L. Ebi (Climatic Change, 2025)
Heat-related deaths occur throughout the summer months, peak during heatwaves, and are affected by temperature and exposed populations’ sensitivities to meteorological conditions. Previous studies found that climate change is increasing heat-related mortality worldwide. We build on existing epidemiological methods to shed light on the adverse effects of climate change on human health. We address limitations in existing methods and apply refined approaches to assess heat mortality attributable to human-induced climate change in Zürich, Switzerland, over 50 years (1969–2018) including a case study of summer 2018. Our methodological refinements affect how counterfactual climate scenarios are derived, and facilitate accounting for changing vulnerability, and assessing impacts during and outside heatwaves. We find nearly 1,700 heat-related deaths attributable to human-induced climate change between 1969 and 2018. Declining vulnerability to heat avoided at least 700 heat-related deaths. The approach described here could be applied elsewhere to quantify the effect of climate change on other health outcomes.

Active Fire Detection using Indian Geostationary Satellite INSAT-3DS - Nimisha Singh; Rohit Pradhan; Bipasha Paul Shukla; Mehul R. Pandya; Rashmi Sharma (Remote Sensing in Earth Systems Sciences, 2025)

Science and Applications from ISRO’s EOS-06/Oceansat-3 Mission - Mini Raman; Rashmi Sharma; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2025)

Rice transcriptomic analysis provides novel insights into T3SS-mediated modulation of plant defense responses by the most virulent Indian race 4 of Xanthomonas oryzae pv. oryzae - M. Amrutha Lakshmi; Aditya Kulshreshtha; Kalyan K. Mondal; N. S. Kalaivanan; Pratap J. Handique; Debashis Borbara; Yuvika Rajrana; Geeta Verma; Ankita Bhattacharya; Kishorekumar Reddy; Madhvi Soni; Thungri Ghoshal; et al. (Journal of Plant Diseases and Protection, 2025)

Chitosan nanoparticles of rutin mitigated histological changes induced in DNCB-induced colitis by enhanced modulation of inflammation and oxidative stress - Lokesh Nama; Rashmi Bhushan; Prakash Kumar; Somasundaram Arumugam; Om Prakash Ranjan; Prabhat Kumar; Nitesh Kumar (Journal of Molecular Histology, 2025)

Exploring Host Resistance in Oilseed Brassica species against Albugo candida [(Pers.) Kuntze] Isolates under Variable Agro-climatic Conditions in India - Ankita Kumari; Samridhi Mehta; Laxmi Awasthi; Mahesh Rao; Jameel Akhtar; Rashmi Yadav; Perumal Nallathambi; Vikas Sharma; Prabhu Dayal Meena; Pramod Kumar Rai; Ramcharan Bhattacharya; Mohd. Harun; et al. (Journal of Crop Health, 2025)

Genome-wide identification, in-silico analysis and expression profiling of regulatory genes involved in essential amino acid biosynthesis during different stages of germination in grain amaranth (Amaranthus hypochondriacus) - Kamal Singh Aswal; Sharat Prabhakaran; Rashmi Chauhan; Dinesh Joshi; Roopali Sharma; Dinesh Pandey (Genetic Resources and Crop Evolution, 2025)

Hybrid performance, combining ability and inheritance of quantitative and quality traits including shelf life in tomato (Solanum lycopersicum L.) - Rashmi Singh; Nagendra Rai; Prashant Kumar; Dhananjay K. Upadhyay; Neeraj Dwivedi; Ramesh K. Singh (Euphytica, 2025)

Advancing Circular Economy Through Green Human Capital: the Critical Role of Sustainability - Rashmi Kumari; Sujata Priyambada Dash; Rajeshwari Chatterjee (Circular Economy and Sustainability, 2025)

Agronomic Practices Affecting the Yield and Quality of Kiwifruit: A Comprehensive Review - Supreetha B. G.; Vishal B. Mhetre; W. H. Raja; M. K. Verma; Rashmi E. R.; Kavitha R.; Reena Prusty (Applied Fruit Science, 2025)

Cashew (Anacardium occidentale L.) nut meal could be a promising alternative protein feedstuff for lambs - K.M. Rashmi; T.M. Prabhu; N.M. Soren; H.M. Yathish; M.S. Mahesh (Small Ruminant Research, 2025)

Stable isotopic characterization and estimation of canal recharge to the groundwater in a part of the Ganga Plain, North India - Dinesh Rai; Rashmi Saini; Sudhir Kumar; Shwetank Arya; Jacob Noble; Dharmaveer Singh (Journal of Hydrology, 2025)

Biological and genomic characterization of a cypovirus isolated from golden muga silkworm, Antheraea assamensis Helfer (Lepidoptera: Saturniidae) - Iyyangar Deepika; Abhishek Singh; Indira Kumar; Gowtham K; Roja Gnanasekaran; Himanshu Dubey; Rajal Debnath; Pawan Shukla; Kangayam M. Ponnuvel; Vikram Kumar; K.P. Arunkumar; Hanamant Gadad; et al. (Journal of Invertebrate Pathology, 2025)

Molecular characterization of antimicrobial resistance in Escherichia coli from dairy farm environment - Namita Narwal; Monica Rose Amarlapudi; Ravikant V. Vinchurkar; Manisha Behera; Sachinandan De; Raghu Hirikyathanahalli Vishweswaraiah; Anil Kumar Puniya; Rashmi Hogarehalli Mallappa; Diwas Pradhan (International Journal of Hygiene and Environmental Health, 2025)

Encapsulation of piperine in metal organic frameworks and evaluation of its stability, characteristics, in-vitro digestion and product fortification - Thangboy R. Marak; C.T. Manoj Kumar; M.H. Sathish Kumar; N. Laxmana Naik; H.M. Rashmi; B. Ashritha (Food and Bioproducts Processing, 2025)

Distribution and probabilistic human health and ecological risk assessment of potentially toxic elements in water, sediments and aquatic plants: a comprehensive study to understand the impacts of active coal mine on the lentic ecosystem - Rashmi Ranjan Mandal; Deep Raj (Environmental Geochemistry and Health, 2025)

First results of polar mesospheric summer echoes: MARA radar observations from Maitri (70°S), Antarctica - Rashmi Rawat; Satheesan K.; Sourav Chatterjee; Rahul Rawat; Anand K. Singh; Sheila Kirkwood; Evgenia Belova; Shailendra Saini (Advances in Space Research, 2025)

Protein kinase G—a key regulator of pathogenesis in Mycobacterium tuberculosis infection - Anjali K. Mahato; Rupal Rai; Rashmi Chourasia; Anirudh K. Singh; Shivendra K. Chaurasiya (Archives of Microbiology, 2025)

Daily Analyzed Fields of Ocean Surface Chlorophyll for the Global Ocean: Integrating OCM-3 Chlorophyll Data with Coupled Physical-Biogeochemical Model Using Particle Filter Approach - Smitha Ratheesh; M. Jishad; Neeraj Agarwal; Shivani Shah; Ruchi Modi; Ghansham Sangar; Tushar Shukla; Rashmi Sharma (Journal of the Indian Society of Remote Sensing, 2025)

Fluorosis among wild fauna of India: assessing toxicity and its effects on the ecosystem - Shruti Shaurya; Debabrata Mondal; Manish Kumar; Rashmi Rekha Kumari; Prabhakar Sharma; Anup Das; Pankaj Kumar (Environmental Monitoring and Assessment, 2025)

Harnessing advances in mechanisms, detection, and strategies to combat antimicrobial resistance - Ritik Kumar Thakur; Kaushal Aggarwal; Nayan Sood; Aman Kumar; Sachin Joshi; Priya Jindal; Rashmi Maurya; Preeti Patel; Balak Das Kurmi (Science of The Total Environment, 2025)

Molecular cloning and characterization of CtCuZnSOD gene from Cyamopsis tetragonoloba under drought stress - Mamtesh Kumari; Rashmi Gangwar; Harry Kaur; Ramasare Prasad (Plant Gene, 2025)

Soft Computing Techniques for Rainfall-Runoff Modeling and Analysis in River Basin - Pradeep Kumar Mishra; Rashmi Dwivedi (Water Resources Management, 2025)

Impact of Dietary Probiotics on the Immune and Reproductive Physiology of Pubertal Male Japanese Quail (Coturnix coturnix japonica) Administered at the Onset of Pre-Puberty - Aamir Khan; Naveen Kango; Rashmi Srivastava (Probiotics and Antimicrobial Proteins, 2025)

A framework for the satellite-derived chlorophyll data assimilation into coupled physical-biogeochemical model: a case study for the Bay of Bengal - Smitha Ratheesh; M. Jishad; Suchandra Aich Bhowmick; Neeraj Agarwal; Rashmi Sharma (Modeling Earth Systems and Environment, 2025)

Phytonoses: A threat to immunocompromised humans? - Rashmi Aggarwal; Swagata Thakur; Bishnu M. Bashyal; Titiksha Aggarwal (Indian Phytopathology, 2025)

Protacs in cancer therapy: mechanisms, design, clinical trials, and future directions - Akash Vikal; Rashmi Maurya; Brij Bihari Patel; Rajeev Sharma; Preeti Patel; Umesh K. Patil; Balak Das Kurmi (Drug Delivery and Translational Research, 2025)

Pseudomonas aeruginosa biofilm: treatment strategies to combat infection - Rashmi Ramesh; N. D. Rekha; Shubha Gopal (Archives of Microbiology, 2025)

Salinity and phosphorus as key regulators of methane emissions in tropical aquaculture ponds - Latika Patel; Sarath C. Gowd; Rashmi Singh; Shoji D. Thottathil (Aquaculture International, 2025)

Transcriptomic insights into detoxification and mitochondrial responses of Tribolium castaneum (Coleoptera: Tenebrionidae) to carbonyl sulfide exposure - Na-Ri Shin; Rashmi Manohar Mahalle; Jun-Ran Kim; Bong-Su Kim; Keon Mook Seong (Journal of Stored Products Research, 2025)

Agriculture 4.0: The Indian narrative – Tracing its roots and growth - Bikram Barman; Rashmi Singh; Rabindra Nath Padaria (Food and Humanity, 2025)

Guar galactomannan ameliorates radiation-induced intestinal injury in mice - Darshini Shivamogga Mohan; Murali Badanthadka; Anushri Umesh; Bharath Basavapattana Rudresh; Manjunatha Bukkambudhi Krishnaswamy; Rashmi Kanugodu Vasappa; Sahayog Narayan Jamdar; Vidya Shimoga Muddappa (Bioactive Carbohydrates and Dietary Fibre, 2025)

High amylopectin in waxy maize synergistically affects seed germination and seedling vigour over traditional maize genotypes - Zahirul A. Talukder; Rashmi Chhabra; Sudipta Basu; Nisrita Gain; Subhra J. Mishra; Ashwani Kumar; Rajkumar U. Zunjare; Vignesh Muthusamy; Firoz Hossain (Journal of Applied Genetics, 2025)

Polyvinyl Chloride and Polypropylene Microplastics Impact Soil Total Antioxidant Capacity and Exoenzyme Secretions - Suryasikha Samal; Pratik Acharya; Rashmi Rekha Samal; Tanushree Moharana; C. S. K. Mishra; Priyadarshini Dash; Satyabrata Brahma; Binayak Prasad Behera; Pragyan Pallavini (Bulletin of Environmental Contamination and Toxicology, 2025)

Anthropogenic and climate driven risks of multi-species plant invasions in Sub-Himalayan grassland ecosystems - Jyotish Ranjan Deka; Umar Saeed; Rashmi Das; Sk. Zeeshan Ali; Rabindra Sharma; Ruchi Badola; Syed Ainul Hussain (Biological Invasions, 2025)

Bio-contaminated plastic micropipette tip sterilization stations: Environmentally, economically, and energetically viable solution - Arian Veyssi; Laxmicharan Samineni; Rashmi P. Mohanty (Waste Management, 2025)

Leveraging satellite imagery for comprehensive agro-economic health assessment in Indian villages: A case study of Karnataka's diverse agro-climatic zones - Kaustubh M. Mujumdar; Rashmi Singh; Anandakumar M. Ramiya; Satyam S. Sahay (Remote Sensing Applications: Society and Environment, 2025)

Impacts and mechanisms of emerging contaminants on biological manganese oxidation in algal-bacterial interaction system - Jing Qi; Changlu Zhang; Baiwen Ma; Lusen Li; Rashmi Koju; Hongwei Yu; Chengzhi Hu; Jiuhui Qu (Journal of Environmental Chemical Engineering, 2025)

Exploring the antineoplastic potential of novel NSAID derivatives in combatting mammary tumorigenesis: a comprehensive review - Rashmi Dewangan; Nidhi Agrawal; S. K. Lanjhiyana; Meenakshi Jaiswal (Medicinal Chemistry Research, 2025)

Development, validation and utility of conventional and real-time PCR based marker for the detection of Bipolaris oryzae causing brown spot disease of rice - Kartar Singh; Sapna Sharma; Aditya Tyagi; Sangeeta Gupta; Bishnu M. Bashyal; M. S. Gurjar; M. S. Saharan; Manoj Choudhary; Rashmi Aggarwal (Australasian Plant Pathology, 2025)

Molecular Epidemiology and Genotypic Diversity of Theileria annulata among Bovines Based Upon Tams1 Gene in India - Rashmi Malik; Biswa Ranjan Maharana; Anita Ganguly; Sukhdeep Vohra; Binod Kumar; Ankit Kumar; Harpreet Singh; Sandeep Potliya; Sujoy Khanna; Subhasish Sahu (Acta Parasitologica, 2025)

Harnessing computational methods for uncovering structural insights into Leishmania donovani 3-MST: implications for drug design and target specificity - Ravi Ranjan; Rashmi Kumari; Ashish Kumar; Saravanan Vijayakumar (In Silico Pharmacology, 2025)

Optimization of tissue culture and Cas9 transgene expression in tomato: A step towards CRISPR/Cas9-based genetic improvement - Rashmi Kaul; Arulprakash Thangaraj; Shivani Sharda; Tanushri Kaul (Plant Science, 2025)

Avenues of resources efficiency enhancement in iron and steel production - T.C. Alex; Rashmi Singla; D.P. Sahoo; K.D. Mehta; Sanjay Kumar (Minerals Engineering, 2025)

High-performance and short-process sulphur autotrophic denitrification from low-C/N wastewater using novel suspended bio-S0 filters - Rashmi Koju; Yu Cheng; Shujia Gao; Tista Prasai Joshi; Chengzhi Hu; Min Yang; Jiuhui Qu (Journal of Cleaner Production, 2025)

Molecular Diversity Studies and Core Development in Sesame Germplasm (Sesamum indicum L.) Using SSR Markers - Rasna Maurya; Shivani Singh; Yangala Sudheer Babu; Fatima Nazish Khan; Bhagwat Nawade; Harinder Vishwakarma; Ajay Kumar; Rashmi Yadav; Radhamani Jalli; Mahalingam Angamuthu; Mothilal Alagirisamy; Rajkumar Subramani; et al. (Plant Molecular Biology Reporter, 2025)

Advances in triploid plant production: techniques, benefits, and applications - Rashmi Ramakrishnan; Akshatha Banadka; Sakshi Dubey; Jameel M. Al-Khayri; Praveen Nagella (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Ascorbic acid - Sodium Borohydride coupled supersensitive gold nanoparticles for water quality assurance - Pradeepa; Rashmi Kanugodu Vasappa; Darshini Shivamogga Mohan; Manjunatha Bukkambudhi Krishnaswamy; Anil Kumar Honnali Srinivasalu; Venkatesh Kamath Halladi; Ganga Gamana; Vidya Shimoga Muddappa (Nanotechnology for Environmental Engineering, 2025)

Exploring Optimal Combinations of Green Manures, Composts, and Microbial Inoculums to Boost Soil Biological Properties, Nutrient Release, and Basmati Rice Yield - Anita Kumawat; Dinesh Kumar; Y. S. Shivay; Seema Sangwan; Devideen Yadav; Vijay Pooniya; Shakir Ali; M. Madhu; I. Rashmi; B. Bhargavi; Ashok Kumar (International Journal of Plant Production, 2025)

Nanostructured lipid carriers in Rheumatoid Arthritis: treatment, advancements and applications - Swarnika Sharma; Rashmi Ghosh; Arockia Babu Marianesan; Sumaya Hussain; Jai Deo Pandey; Manish Kumar (Inflammopharmacology, 2025)

Development and characterization of an EMS-mutagenized population of wheat (Triticum aestivum L.) for agronomic trait variation and increased micronutrients content - Naveen Kumar; Jajati Keshari Nayak; Neeraj Pal; Santvana Tyagi; Raju Ratan Yadav; Pooja Joshi; Rashmi Malik; Narendra Singh Dhaka; Vinay Kumar Singh; Sundip Kumar (Cereal Research Communications, 2025)

Variants of rubbly pahoehoe flows from Sylhet Traps, Shillong Plateau, northeast India: Implications on lava emplacement and evolution of the volcanic system - Jayanta Kumar Naik; Bibhas Sen; Tapos Kumar Goswami; Rashmi Rekha Naik; Ranjan Kumar Sarmah (Journal of Earth System Science, 2025)

Vegetables under siege: the hidden threat of metal contamination in Varanasi’s suburban soils - Rashmi Singh; Ashish Kumar Mishra; Ansuman Sahoo; Alok Kumar Khare; Supriya Tiwari (Vegetos, 2025)

Decrypting proteomics, transcriptomics, genomics, and integrated omics for augmenting the abiotic, biotic, and climate change stress resilience in plants - Rashmi Choudhary; Faheem Ahmad; Cengiz Kaya; Sudhir Kumar Upadhyay; Sowbiya Muneer; Vinod Kumar; Mukesh Meena; Haitao Liu; Hrishikesh Upadhyaya; Chandra Shekhar Seth (Journal of Plant Physiology, 2025)

Biolubricants from waste cooking oil: A review of extraction technologies, conversion techniques, and performance enhancement using natural antioxidants - Jia Leang Teh; Rashmi Walvekar; Kah Chun Ho; Mohammad Khalid (Journal of Environmental Management, 2025)

Microbe-assisted phytoremediation for sustainable management of heavy metal in wastewater - A green approach to escalate the remediation of heavy metals - Rashmi Ranjan Mandal; Zahid Bashir; Deep Raj (Journal of Environmental Management, 2025)

Biochar's multifaceted role in bioremediation of emerging contaminants and heavy metals in complex rhizospheric ecosystem - Shiv Vendra Singh; Shivangi Raghuvanshi; Yogeshwar Singh; Krishna Kumar Yadav; Amel Gacem; Tony Manoj K. Nandipamu; Mohammad Khalid; Rashida Hameed; Rashmi Sharma; Debarati Datta; Saurabh Ghosh; Arpna Kumari; et al. (International Biodeterioration & Biodegradation, 2025)

Mechanistic insight into anti-inflammatory potential, phytochemistry and ethnomedicinal status of Ilex species: a review - Acharya Balkrishna; Priyanka Rai; Rashmi Verma; Akansha Rohela; Ashwani Kumar; Vedpriya Arya; Nazam Khan; Ryszard Amarowicz; Dinesh Kumar; Rachna Verma (Phytochemistry Reviews, 2025)

Sodium Alginate Beads Containing Epalrestat for Effective Management of Diabetic Mellitus - Rashmi Madhariya; Alpana Ram; Akhlesh K. Jain (Journal of Pharmaceutical Innovation, 2025)

Advancements in nose-to-brain drug targeting for Alzheimer’s disease: a review of nanocarriers and clinical insights - Kumari Komal; Rashmi Ghosh; Debayan Sil; Rohit Sharma; Sourabh Kumar; Prachi pandey; Manish Kumar (Inflammopharmacology, 2025)

The cascade of cadmium toxicity: from cellular damage to pyroptotic responses in fish Channa punctatus - Vaishnavi Saxena; Jumman Bakhasha; Neeti Arya; Rashmi Singh; Raveena Singh; Rubina Khan; Ritu Singh; Sunil P. Trivedi; Manoj Kumar; Kamlesh K. Yadav; Abha Trivedi (Fish Physiology and Biochemistry, 2025)

Biochar application in constructed wetlands for wastewater treatment: A critical review - Diksha Pandey; Shiv Vendra Singh; Nikhil Savio; Javed Khan Bhutto; R.K. Srivastava; Krishna Kumar Yadav; Rashmi Sharma; Tony Manoj K. Nandipamu; Binoy Sarkar (Journal of Water Process Engineering, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Human milk fat globule delivers entrapped probiotics to the infant's gut and acts synergistically to ameliorate oxidative and pathogenic stress - Monica Yadav; Rashmi Hogarehalli Mallappa; Kiran Ambatipudi (Food Chemistry, 2025)

Membrane Distillation for Sustainable Water Desalination: A Review of Principles, Materials, and Applications - Rashmi Kakkar; Dilraj Preet Kaur; Seema Raj (Water, Air, & Soil Pollution, 2025)

Pixel interlacing network: a novel approach for multiclass and subcategories land cover change detection - Rashmi Bhattad; Vibha Patel; Usha Patel; Samir Patel (Earth Science Informatics, 2025)

Shatavarin-IV rescues the Di (2-ethylhexyl) phthalate (DEHP) induced oxidative stress in rat granulosa cells in vitro - Vivek Pandey; Alka Sharma; Sonal Tiwari; Yashvant Patel; Jayhind Kumar Chauhan; Safiya Ayesha; Alakh N. Sahu; Rashmi Gupta; Anima Tripathi; Pawan K. Dubey (Reproductive Toxicology, 2024)

Molecular and immunohistochemical alterations in fluoride-induced neurological impediment in adult rats - Sachindra Kumar; Ravindra Shantakumar Swamy; Rashmi Bhushan; Vishal Chhabra; Smita Shenoy; Krishna Murti; Shubhankar Kumar Singh; Nitesh Kumar (Journal of Trace Elements in Medicine and Biology, 2024)

Citral-thymol based synergistic shellac coatings enhanced shelf life of Kinnow fruit stored under low temperature conditions - Rashmi; Ritu Tandon; Anu Kalia; Rachana D. Bhardwaj; Bal Vipan Chander Mahajan (Journal of Stored Products Research, 2024)

Adsorption – Advanced oxidation process (AAOP) for the heavy metals and organic matter removal from leachate using combined filtration -Fenton's and Photo-Fenton's treatment - Bhaskar S; Rashmi Shree K N; Apoorva K V; Sreenivasa M Y (Journal of Environmental Management, 2024)

Phenotypic and genotypic characterization of antimicrobial resistance in Enterococcus species from dairy niches - Ravikant V. Vinchurkar; Heena Parveen; Monica Rose Amarlapudi; Rashmi Hogarehalli Mallappa; Diwas Pradhan (Food Bioscience, 2024)

Applications of HYDRUS Based CW2D Wetland Module: a Review - Rama Pal; Truptimayee Suna; N. L. Kushwaha; I. Rashmi; M. Madhu (Water, Air, & Soil Pollution, 2024)

Expression analysis of genes involved in teliospores germination of Tilletia indica inciting Karnal bunt of wheat - Haritha Mohan Manakkatt; Malkhan Singh Gurjar; Mahender Singh Saharan; Rashmi Aggarwal (Molecular Biology Reports, 2024)

Assessing sequence variation, haplotype analysis and molecular characterisation of aspartate kinase2 (ask2) gene regulating methionine biosynthesis in diverse maize inbreds - Hriipulou Duo; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Molecular Genetics and Genomics, 2024)

Characterization of Rainfall/Cloud Signature Using Fully Polarimetric X-Band SAR Data - Rashmi Malik; Shradha Mohanty; J. Indu; Onkar Dikshit; Virendra S. Rathore (Journal of the Indian Society of Remote Sensing, 2024)

Formulation Optimization of Metformin-Loaded Propyl Moringa Gum Beads - Atul Kaushik; Rimpy Pahwa; Rashmi Sharma; Vikramjeet Singh; Munish Ahuja (Journal of Pharmaceutical Innovation, 2024)

Morphological and Biochemical Profiles of Pollen Allergens from Asteraceae: a Pilot Study - Rashmi Shakya; Rekha Kumari; Deepali Verma; Elangbam Geetanjali (The Botanical Review, 2024)

Environmental determinants of aerobic methane oxidation in a tropical river network - Latika Patel; Rashmi Singh; Sarath C. Gowd; Shoji D. Thottathil (Water Research, 2024)

Exploring chemically and physically modified plant-based fiber biomass for biosorption in wastewater treatment: A concise review - N. Rashmi; S.A. Salmataj; P. Senthil Kumar; Pushpanjali Bhat (Journal of Water Process Engineering, 2024)

Treatment effects of conservation trenching on regulating and provisioning ecosystem services - Shakir Ali; B.K. Sethy; B.L. Mina; H.R. Meena; S. Kala; Ashok Kumar; I. Rashmi; G.L. Meena; G.K. Sharma (Journal of Environmental Management, 2024)

Utilization of cotton stalk waste for sustainable isopropanol production via hydrolysis and coculture fermentation - Barsha Samantaray; Sonali Mohapatra; Biswaranjan Pradhan; Bikash Chandra Behera; Rashmi Ranjan Mishra; Hrudayanath Thatoi (International Biodeterioration & Biodegradation, 2024)

Characteristics of isoniazid-induced psychosis: a systematic review of case reports and case series - Keerthanaa B; Rashmi Appaji; Levin Thomas; Tejaswini Baral; Skanda N; Chaithra; Sonal Sekhar M; Kavitha Saravu; Krishna Undela; Mahadev Rao (European Journal of Clinical Pharmacology, 2024)
Purpose Isoniazid, a first-line antitubercular drug, is associated with nervous system adverse drug reactions such as seizures, peripheral neuropathy, and psychosis. This systematic review of case reports and case series aimed to characterize the demographic, social, and clinical factors associated with isoniazid-induced psychosis in patients with active tuberculosis (TB) and those who received isoniazid for latent TB infection (LTBI). Methods We comprehensively searched the Embase, PubMed, and Scopus databases to identify relevant studies published between the date of inception of the database and June 2024. Results A total of 28 studies, including 21 case reports and 7 case series involved 37 patients who developed isoniazid-induced psychosis. A higher frequency of isoniazid-induced psychosis was observed during the first 2 months of treatment, with a relatively early onset observed among patients aged 18 years or less. Delusions and/or hallucinations are the common symptoms of isoniazid-induced psychosis. Psychomotor disturbances, disorganized speech or formal thought disorder, disorganized or abnormal behaviour, and neuropsychiatric symptoms (sleep disturbances, hostility or aggression, confusion, affective symptoms, anxiety symptoms, and cognitive difficulties) were the other symptoms observed in the included studies. More than 80% of cases rechallenged with isoniazid resulted in the recurrence of psychotic symptoms. Conclusion Patients with TB and LTBI should be assessed for psychotic and neuropsychiatric symptoms during isoniazid therapy, mainly in the first 2 months. Further research is required to understand the impact of underlying risk factors, such as genetic predisposition and isoniazid pharmacokinetics, as well as the clinical utility and dosage recommendations of pyridoxine for managing isoniazid-induced psychosis.

Harnessing bacterial metabolites for enhanced cancer chemotherapy: unveiling unique therapeutic potentials - Aroni Chatterjee; Rajni Khan; Triparna Mukherjee; Preity Pragnya Sahoo; Laxmi Narayan Tiwari; Basant Narain Singh; Rashmi Kumari; Anisha Kumari; Ankit Rai; Shashikant Ray (Archives of Microbiology, 2024)

Neoproterozoic crustal evolution of Indo-Australo-Antarctic Suture domain and Gamburtsev Subglacial Mountains, East Antarctica: Insights from offshore sediments - Rashmi Gupta; Mayuri Pandey; Devsamridhi Arora; Akash K. Pandey; Naresh C. Pant; K. Batuk Joshi; Pankaj Kumar; M. Satyanarayanan; Atul Singh (Gondwana Research, 2024)

Enhancing Proliferation of Stem Cells from Human Exfoliated Deciduous Teeth (SHED) through hTERT Expression while Preserving Stemness and Multipotency - Pooja Yadav; Ravina Vats; Sapna Wadhwa; Afsareen Bano; Ritu Namdev; Monika Gupta; Rashmi Bhardwaj (Stem Cell Reviews and Reports, 2024)

Correction to: Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Kavitha Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)

Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Joseph Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)
Dengue is an emerging, mosquito-borne viral disease of international public health concern. Dengue is endemic in more than 100 countries across the world. However, there are no clinically approved antivirals for its cure. Drug repurposing proves to be an efficient alternative to conventional drug discovery approaches in this regard, as approved drugs with an established safety profile are tested for new indications, which circumvents several time-consuming experiments. In the present study, eight approved RNA-dependent RNA polymerase inhibitors of Hepatitis C virus were virtually screened against the Dengue virus polymerase protein, and their antiviral activity was assessed in vitro. Schrödinger software was used for in silico screening, where the compounds were passed through several hierarchical filters. Among the eight compounds, dasabuvir was finally selected for in vitro cytotoxicity and antiviral screening. Cytotoxicity profiling of dasabuvir in Vero cells revealed changes in cellular morphology, cell aggregation, and detachment at 50 μM. Based on these results, four noncytotoxic concentrations of dasabuvir (0.1, 0.25, 0.5, and 1 µM) were selected for antiviral screening against DENV-2 under three experimental conditions: pre-infection, co-infection, and post-infection treatment, by plaque reduction assay. Viral plaques were reduced significantly ( p < 0.05) in the co-infection and post-infection treatment regimens; however, no reduction was observed in the pretreatment group. This indicated a possible interference of dasabuvir with NS5 RdRp, as seen from in silico interaction studies, translating into a reduction in virus plaques. Such studies reiterate the usefulness of drug repurposing as a viable strategy in antiviral drug discovery. Graphical Abstract In this drug repurposing study, dasabuvir, a known anti-hepatitis C drug, was selected through virtual screening and assessed for its anti-dengue activity.

RFGR: Repeat Finder for Complete and Assembled Whole Genomes and NGS Reads - Rashmi Sukumaran; K. Shahina; Achuthsankar S. Nair (Biochemical Genetics, 2024)

Biofilm-specific determinants of enterococci pathogen - Rohit Ruhal; Abhijeet Sahu; Tushar Koujalagi; Ankumoni Das; Hema Prasanth; Rashmi Kataria (Archives of Microbiology, 2024)

“Enhancing Oral Drug Absorption: Overcoming Physiological and Pharmaceutical Barriers for Improved Bioavailability” - Rashmi Maurya; Akash Vikal; Preeti Patel; Raj Kumar Narang; Balak Das Kurmi (AAPS PharmSciTech, 2024)

Adsorption parameters optimization of spent coffee ground biochar for methylene blue removal using response surface methodology - Thachnatharen Nagarajan; Nazifa Huda Binti Mohd Fekeri; Gunasunderi Raju; Subramani Shanmugan; Gautham Jeppu; Rashmi Walvekar; Sarvesh Rustagi; Mohammad Khalid (Chemosphere, 2024)

Unraveling molecular architecture, development and validation of Anthocyanin1 gene-based novel breeder-friendly markers for utilization in genomics-assisted breeding of blue maize - Gaurav Sharma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Govinda Rai Sarma; Deepak R. Sapkal; Firoz Hossain (South African Journal of Botany, 2024)

Integrative genetic and molecular delineation of indeterminate gametophyte1 (ig1) gene governing paternal haploid induction in maize - Amitkumar D. Kyada; Rashmi Chhabra; Vignesh Muthusamy; Ravindra K. Kasana; Gaurav Sharma; Nisrita Gain; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (South African Journal of Botany, 2024)

Microwave facilitated bacterial liquefaction of sago biomass for efficient biomethane production: Energy and cost assessment - Sudharsh S; Preethi; Rashmi Gondi; Insuvai S; Chitrali Laha Roy; Yukesh Kannah R; Gunasekaran M; Pugalenthi V; Meganathan Kannan; Rajesh Banu J (Process Safety and Environmental Protection, 2024)

High-throughput measurements of CO2 permeance and solubility in ionic liquid reveal a synergistic role of ionic interactions and void fractions - Rohit Chauhan; Rohan Sartape; Rashmi Mishra; Jindal K. Shah; Meenesh R. Singh (Chemical Engineering Journal, 2024)

Piriformospora indica improves water stress tolerance in watermelon (Citrullus lanatus (Thunb.) Matsum & Nakai) - C. P. Jyothymol; M. Sangeeta Kutty; T. Pradeepkumar; M. S. Parvathi; C. R. Rashmi (Plant Physiology Reports, 2024)

Delineating the response of antioxidant enzymes comparatively in four guar genotypes under drought stress - Mamtesh Kumari; Rashmi Gangwar; Ramasare Prasad (Journal of Plant Biochemistry and Biotechnology, 2024)

Enhancing crack pixel segmentation: comparative assessment of feature combinations and model interpretability - R. Rakshitha; S. Srinath; N. Vinay Kumar; S. Rashmi; B. V. Poornima (Innovative Infrastructure Solutions, 2024)

Comparative gene expression of OsSWEETs from various rice genotypes during the development of bacterial blight as induced by the most virulent Race 4 of Xanthomonas oryzae pv. oryzae - Rashmi E R; Kalyan K. Mondal; Thungri Ghoshal; M Amrutha Lakshmi (Australasian Plant Pathology, 2024)

A Versatile pH-Dependent Fluorometric, Colorimetric, and Electrochemical Sensor for H2S Monitoring in Water - Rashmi M. Kulkarni; M. Ranjana; Namratha Ullal; Dhanya Sunil (Journal of Fluorescence, 2024)

Can gypsum and organic amendments achieve sustainability, productivity and maintain soil health under soybean-mustard cropping in sodic soils of western India - I. Rashmi; Bharat Prakash Meena; S. Rajendiran; Somasundaram Jayaraman; C.G. Joshy; Shakir Ali; B.L. Mina; Kuldeep Kumar; Ashok Kumar; Anita Kumawat; S. Kala (Soil and Tillage Research, 2024)

Nano-welded carbon nanotube sponges for efficient oil spill remediation - Manoj Sehrawat; Vasundhara Singh; Mamta Rani; Chahek Kalra; Sony Bharadwaj; Rashmi Rani; Aarti Bisht; Bhanu Pratap Singh (Journal of Cleaner Production, 2024)

Enhancement in sugar extraction from Pistia stratiotes through statistical optimization of alkaline pre-treatment and enzymatic hydrolysis - Sweeti Mann; Jai Gopal Sharma; Rashmi Kataria (International Biodeterioration & Biodegradation, 2024)

Study of upwelling and mixing process in the Somali coastal region using satellite and numerical model observations: A Lagrangian approach - Jai Kumar; Smitha Ratheesh; Neeraj Agarwal; Rashmi Sharma (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

Deep learning fusion for dynamic cropland monitoring: integrating MUNet with Siamese networks and convolutional LSTM2D - Rashmi Bhattad; Vibha Patel; Usha Patel (Modeling Earth Systems and Environment, 2024)

Time for CHANGE: system-level interventions for bringing forward the date of effective use of NAMs in regulatory toxicology - Gro H. Mathisen; Angela Bearth; Lowenna B. Jones; Sebastian Hoffmann; Gunn E. Vist; Heather M. Ames; Trine Husøy; Camilla Svendsen; Katya Tsaioun; Takao Ashikaga; Denise Bloch; Aleksandra Cavoski; et al. (Archives of Toxicology, 2024)

Neuropathogenesis of SARS-CoV-2 in human neuronal, microglial and glial cells - Narendra Kumar; Rashmi Santhoshkumar; Ragini Agrawal; Amit Singh; Vijayalakshmi Kalyan; Anita Desai; Vasanthapuram Ravi; Manjunatha M. Venkataswamy (Archives of Microbiology, 2024)

Role of strong subsurface mode on the anomalous basin-wide surface warming of the Tropical Indian Ocean in 2019–2020 - C Gnanaseelan; Rashmi Kakatkar; Sebastian Anila; Sandeep Mohapatra; Anant Parekh; J S Chowdary (Journal of Earth System Science, 2024)

SEM–EDS-based rapid measurement and size-fractionated speciation of airborne particulate matter and associated metals utilizing plant leaves - Triratnesh Gajbhiye; Ankesh Tiwari; Tanzil Gaffar Malik; Rashmi Dubey; Sudhir Kumar Pandey; Hesham F. Alharby; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2024)

Host-specific endophytes of Momordica charantia: A promising source for affordable lung cancer therapeutics - Garima Sharma; Rashmi Bhardwaj; Jyoti; Vitthal T. Barvkar; Rucha C. Godbole; Vinay Kumar; Vartika Mathur (South African Journal of Botany, 2024)

In silico studies of fungal xylanase enzymes: structural and functional insight towards efficient biodegradation of lignocellulosic biomass - Barsha Samantaray; Rashmi Ranjan Behera; Rashmi Ranjan Mishra; Hrudayanath Thatoi (Systems Microbiology and Biomanufacturing, 2024)

Comprehensive journey from past to present to future about seed priming with hydrogen peroxide and hydrogen sulfide concerning drought, temperature, UV and ozone stresses- a review - Rashmi Choudhary; Vishnu Dayal Rajput; Gajanan Ghodake; Faheem Ahmad; Mukesh Meena; Reiaz ul Rehman; Ram Prasad; Rajesh Kumar Sharma; Rachana Singh; Chandra Shekhar Seth (Plant and Soil, 2024)

BHARAT: a MADM approach to prioritizing the best performing EPS in a semi-arid river basin - Rashmi Yadav; Sanjaykumar M Yadav (Natural Hazards, 2024)

Dissociated cerebellar contributions to feedforward gait adaptation - Karen L. Bunday; Toby J. Ellmers; M. Rashmi Wimalaratna; Luxme Nadarajah; Adolfo M. Bronstein (Experimental Brain Research, 2024)
The cerebellum is important for motor adaptation. Lesions to the vestibulo-cerebellum selectively cause gait ataxia. Here we investigate how such damage affects locomotor adaptation when performing the ‘broken escalator’ paradigm. Following an auditory cue, participants were required to step from the fixed surface onto a moving platform (akin to an airport travellator). The experiment included three conditions: 10 stationary (BEFORE), 15 moving (MOVING) and 10 stationary (AFTER) trials. We assessed both behavioural (gait approach velocity and trunk sway after stepping onto the moving platform) and neuromuscular outcomes (lower leg muscle activity, EMG). Unlike controls, cerebellar patients showed reduced after-effects (AFTER trials) with respect to gait approach velocity and leg EMG activity. However, patients with cerebellar damage maintain the ability to learn the trunk movement required to maximise stability after stepping onto the moving platform (i.e., reactive postural behaviours). Importantly, our findings reveal that these patients could even initiate these behaviours in a feedforward manner, leading to an after-effect. These findings reveal that the cerebellum is crucial for feedforward locomotor control, but that adaptive locomotor behaviours learned via feedback (i.e., reactive) mechanisms may be preserved following cerebellum damage.

Effects of temperature on the development of Aedes albopictus (Diptera: Culicidae) from desert and coastal regions of India - Souvik De; Gaurav Sharma; Rashmi Bhattacherjee; Dhriti Banerjee; Devi Shankar Suman (International Journal of Tropical Insect Science, 2024)

Biochemical and biophysical interaction of rare earth elements with biomacromolecules: A comprehensive review - Rashmi R. Samal; Umakanta Subudhi (Chemosphere, 2024)

Investigating the adsorption potential of char derived from waste latex for methylene blue removal - Thachnatharen Nagarajan; Khirthiga Vilosamy; Gunasunderi Raju; Subramani Shanmugan; Rashmi Walvekar; Sarvesh Rustagi; Mohammad Khalid (Chemosphere, 2024)

Unveiling the Health Benefits of Prebiotics: A Comprehensive Review - Anuradha Kumari; Rashmi K. G.; Aparna Sudhakaran. V.; Aswin S. Warrier; Niraj K. Singh (Indian Journal of Microbiology, 2024)

Potential strategies for phytoremediation of heavy metals from wastewater with circular bioeconomy approach - Rashmi Ranjan Mandal; Zahid Bashir; Jyoti Ranjan Mandal; Deep Raj (Environmental Monitoring and Assessment, 2024)

Diabetes Warriors from Heart Wood: Unveiling Dalbergin and Isoliquiritigenin from Dalbergia latifolia as Potential Antidiabetic Agents in-vitro and in-vivo - Srinivas Sutrapu; Rashmi Saxena Pal; Navneet Khurana; Harish Vancha; Sharfuddin Mohd; Krishna Mohan Chinnala; Bimlesh Kumar; Govindaiah Pilli (Cell Biochemistry and Biophysics, 2024)

Interaction between ectomycorrhizal and ericoid mycorrhizal plants decelerates stable soil organic matter decomposition - Sylwia Adamczyk; Rashmi Shrestha; Bartosz Adamczyk; Chao Liang; Christina Biasi; Jussi Heinonsalo; Kristiina Karhu (Applied Soil Ecology, 2024)

Comparative analyses of anti-inflammatory effects of Resveratrol, Pterostilbene and Curcumin: in-silico and in-vitro evidences - Rashmi Patil; Gaurang Telang; Urmila Aswar; Nishant Vyas (In Silico Pharmacology, 2024)

Synchronous in-situ sludge reduction and enhanced denitrification through improving electron transfer during endogenous metabolisms with Fe(Ⅱ) addition - Yu Cheng; Chenghai Lu; Shujia Gao; Rashmi Koju; Haiyan Li; Zongqiang Zhu; Chengzhi Hu; Jiuhui Qu (Water Research, 2024)

Evaluation of the potential of Delta-aminolevulinic acid for simultaneous detection of bioburden and anti-microbial photodynamic therapy of MRSA infected wounds in Swiss albino mice - Khageswar Sahu; Hemant Krishna; Rashmi Shrivastava; Anamitra Majumdar; Anupam Chowdhury; Sourabrata Chakraborty; Shovan Kumar Majumder (Journal of Photochemistry and Photobiology B: Biology, 2024)

Advancement in integrated ammonia synthesis, and its techno-economic analysis, emission index, and contribution to the hydrogen 2.0 economy - Rashmi Singh; Melvin S. Samuel; Selvarajan Ethiraj; J Ashwini John; Madhumita Ravikumar; S Joseph Sekhar; TTH Le; Thangavel Mathimani (Fuel, 2024)

Quantification of diffusion coefficients of commonly used high-intensity sweeteners through mucin - Farhad Javi; Hooman Torabi; Younas Dadmohammadi; Rashmi Tiwari; Indra Prakash; Alireza Abbaspourrad (Food Research International, 2024)

Nurturing health through millet derived nutraceuticals - Rashmi Rani; Chetan Pandey; Neha Kapoor (Food and Humanity, 2024)

Innovative strategies to manage polluted aquatic ecosystem and agri-food waste for circular economy - Rashmi Trivedi; Tarun Kumar Upadhyay; Fahad Khan; Pratibha Pandey; Radhey Shyam Kaushal; Madan Sonkar; Deepak Kumar; Mohd Saeed; Mayeen Uddin Khandaker; Talha Bin Emran; Md. Abu Bakar Siddique (Environmental Nanotechnology, Monitoring & Management, 2024)

Allelic variation and haplotype diversity of Matrilineal (MTL) gene governing in vivo maternal haploid induction in maize - Suman Dutta; Rashmi Chhabra; Vignesh Muthusamy; Nisrita Gain; Rajkumar Subramani; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (Physiology and Molecular Biology of Plants, 2024)

Physio-biochemical and nutritional alterations in faba bean due to bean yellow mosaic virus infection - Charanjeet Kaur; Ashish Srivastava; Rashmi Raj; Abhishek Niranjan; Alok Lahri; Susheel Kumar; Shri Krishna Raj (Acta Physiologiae Plantarum, 2024)

Third Generation Solid Dispersion-Based Formulation of Novel Anti-Tubercular Agent Exhibited Improvement in Solubility, Dissolution and Biological Activity - Gourav Paudwal; Rigzin Dolkar; Summaya Perveen; Rashmi Sharma; Parvinder Pal Singh; Prem N. Gupta (The AAPS Journal, 2024)

Development and validation of RP-HPLC method for estimation of quercetin present in hydro alcoholic extract of Erigeron bonariensis Linn. - Vishal B. Mahanur; Rahul R. Rajge; Sukriti Vishwas; M.V.N.L. Chaitanya; Salahuddin; Rashmi Mishra; Narendra Kumar Pandey; Saurabh Singh; Dileep Singh Baghel; Gaurav Gupta; Trudi Collet; Oluwafemi Omoniyi Oguntibeju; et al. (South African Journal of Botany, 2024)

Nickel engineered in-situ graphitization of carbon derived from bagasse: A robust and highly efficient catalyst for oxygen evolution reaction and water remediation - Akhila S; Sayali Ashok Patil; Sai Rashmi Manippady; Arvind H. Jadhav; Akshaya K. Samal; Rupesh S. Devan; Manav Saxena (Journal of Cleaner Production, 2024)

Sustainable basmati rice yield and quality enhancement through long-term organic nutrient management in the Indo-Gangetic Plains - Anita Kumawat; Dinesh Kumar; Y.S. Shivay; Devideen Yadav; Rahul Sadhukhan; Sandeep Gawdiya; Shakir Ali; M. Madhu; Kuldeep Kumar; I. Rashmi; R.A. Jat (Field Crops Research, 2024)

Reproductive factors, hormonal interventions, and gastric cancer risk in the Stomach cancer Pooling (StoP) Project - Minkyo Song; Harindra Jayasekara; Claudio Pelucchi; Charles S. Rabkin; Kenneth C. Johnson; Jinfu Hu; Domenico Palli; Monica Ferraroni; Linda M. Liao; Rossella Bonzi; David Zaridze; Dmitry Maximovitch; et al. (Cancer Causes & Control, 2024)

Integrating land use and traffic to spatial prediction of particulate matter - Vineet Gupta; Rashmi Choudhary; Amit Agarwal (Urban Climate, 2024)

Circulating levels of cytokines (IL-6, IL-10 and TGF- β) and CD4+CD25+FOXP3+Treg cell population in recurrent pregnancy loss - Sufaya Jameel; Rashmi Bhuwalka; Mahmooda Begum; Rajeshwari Bonu; Parveen Jahan (Reproductive Biology, 2024)

Heteroatom-doped MXenes as electrocatalysts for hydrogen evolution reaction: A review on the recent advances, mechanisms and prospects - Abdul Hanan; Muhammad Nazim Lakhan; Rashmi Walvekar; Mohammad Khalid; Chander Prakash (Chemical Engineering Journal, 2024)

Removal of Dimethyl Arsenic Acid from Aqueous Solution by Ferric Manganese Binary Oxide - Naina Byanjankar; Tista Prasai Joshi; Agni Dhakal; Dev Raj Joshi; Rashmi Koju; Zenglu Qi; Chengzhi Hu; Ruiping Liu (Water, Air, & Soil Pollution, 2024)

A comparative analysis of phytochemicals versus synthetic drugs/nanomedicines in the treatment of uterine fibroid: a systematic review - Sonal Upadhyay; Vivek Pandey; Anima Tripathi; Alakh N. Sahu; Anjali Rani; Amita Diwakar; Lavina Chaubey; Rashmi Gupta; Pawan K. Dubey (Toxicology and Environmental Health Sciences, 2024)

SNOOPI: Demonstrating Earth remote sensing using P-band signals of opportunity (SoOp) on a CubeSat - James L. Garrison; Manuel A. Vega; Rashmi Shah; Justin R. Mansell; Benjamin Nold; Juan Raymond; Roger Banting; Rajat Bindlish; Kameron Larsen; Seho Kim; Weihang Li; Mehmet Kurum; et al. (Advances in Space Research, 2024)

Finding identical sequence repeats in multiple protein sequences: An algorithm - Vikas Kumar Maurya; Madhumathi Sanjeevi; Chandrasekar Narayanan Rahul; Ajitha Mohan; Dhanalakshmi Ramachandran; Rashmi Siddalingappa; Roshan Rauniyar; Sekar Kanagaraj (Journal of Biosciences, 2024)

Human health risk assessment model associated with PM2.5 bound metals in paradip port township, India - Rashmi Ranjan Behera; Deepty Ranjan Satapathy; Arakshita Majhi (Chemosphere, 2024)

Microwave-assisted upcycling of plastic waste to high-performance carbon anode for lithium-ion batteries - Muhammad Amirul Aizat Mohd Abdah; Fathihah Nabila Mohammad Azlan; Weng Pin Wong; Muhammad Norhaffis Mustafa; Rashmi Walvekar; Mohammad Khalid (Chemosphere, 2024)

Route selection for real-time air quality monitoring to maximize spatiotemporal coverage - Rashmi Choudhary; Amit Agarwal (Journal of Transport Geography, 2024)

Structural and functional characterisation of Maillard reaction products from casein-acid hydrolysate-sugars model system using multi-spectroscopic approach - Harsha V. Sail; Ashwini D. Jagdale; Muskan R. Thakur; Rashmi S. Tupe (International Dairy Journal, 2024)

Graphene materials in pollution trace detection and environmental improvement - Rashmi Singh; Melvin S. Samuel; Madhumita Ravikumar; Selvarajan Ethiraj; Mohanraj Kumar (Environmental Research, 2024)

Effect of bacterial pretreatment on solid sago waste for enhanced biomethane generation - S. Sudharsh; V. Lavanya; Preethi; Rashmi Gondi; Chitrali Laha Roy; Meganathan Kannan; J. Rajesh Banu (Bioresource Technology Reports, 2024)

Insilico and invitro profiling of curcumin and its derivatives as a potent acetylcholinesterase inhibitor - Mukul Jain; Rupal Dhariwal; Krupanshi Bhardava; Sarvjeet Das; Mushtaque Shaikh; Reshma Tendulkar; Rashmi Wani; Meenakshi Sharma; Anil Kumar Delta; Prashant Kaushik (Biocatalysis and Agricultural Biotechnology, 2024)

Pollutant dispersion with an intermediate source in a semi-infinite aquifer - Rashmi Radha; Rakesh Kumar Singh; Mritunjay Kumar Singh (Modeling Earth Systems and Environment, 2024)

Lafora progressive myoclonus epilepsy: Disease mechanism and therapeutic attempts - Rashmi Parihar; Subramaniam Ganesh (Journal of Biosciences, 2024)

Variability in water quality of two meso-tidal estuaries of Odisha, East Coast of India - Asim Amitav Pattanayak; Sanhita Swain; Rashmi Ranjan Behera; Satyabrata Das Sharma; Chitta Ranjan Panda; Pratap Kumar Mohanty (Journal of Marine Systems, 2024)

Bio-based surfactants derived from pectin - Zarif Farhana Mohd Aris; Rashmi Sharma; Margery G.H. Pelletier; Anna M. Barbeau; Peter C.W. Gaines; Ramaswamy Nagarajan (Carbohydrate Polymers, 2024)

Temozolomide and flavonoids against glioma: from absorption and metabolism to exosomal delivery - Priyanka Verma; Hemant Joshi; Tejveer Singh; Bunty Sharma; Ujjawal Sharma; Seema Ramniwas; Rashmi Rana; Madhu Gupta; Ginpreet Kaur; Hardeep Singh Tuli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Drug target therapy and emerging clinical relevance of exosomes in meningeal tumors - Swati Sharma; Rashmi Rana; Prem Prakash; Nirmal Kumar Ganguly (Molecular and Cellular Biochemistry, 2024)

Trans situ conservation strategies to conserve the extinction risk species, Sesamum prostratum Retz., a crop wild relative of sesame being endemic to coastal strand habitat: a case study - Parimalan Rangan; Kanakasabapathi Pradheep; Mahalingam Angamuthu; Justin Mohan; Rashmi Yadav; Kuldeep Singh (Genetic Resources and Crop Evolution, 2024)

Multiple ocean parameter-based potential fishing zone (PFZ) location generation and validation in the Western Bay of Bengal - R. K. Sarangi; M. Jishad; Rashmi Sharma; Ansuman Das; Kiran Mali; L. Ramalingam; Shoba Joe Kizhakudan; A. Saravana Kumar; R.N. Samal; Chandra Prakash (Environmental Monitoring and Assessment, 2024)

Monosodium Glutamate Even at Low Dose May Affect Oxidative Stress, Inflammation and Neurodegeneration in Rats - Rashmi Kesherwani; Sukanya Bhoumik; Raushan Kumar; Syed Ibrahim Rizvi (Indian Journal of Clinical Biochemistry, 2024)

How useful are mispointing phase SARAL/AltiKa geophysical products for ocean applications? - Suchandra Aich Bhowmick; Aditya Chaudhary; M. Jishad; M. Seemanth; Utkarsh; Neeraj Agarwal; Rashmi Sharma; Honey Gupta; J.V. Thomas; Pascal Bonnefond; J. Verron (Advances in Space Research, 2024)

Evaluating the impact of sampling designs on the performance of machine learning techniques for land use land cover classification using Sentinel-2 data - Shivam Rawat; Rashmi Saini (International Journal of Remote Sensing, 2023)

Analgesic and Anti-inflammatory Potential of Ricinus communis Linn.: Evidence from Pharmacology to Clinical Studies - Rashmi Gupta; Anand K. Chaudhary; Rohit Sharma (Current Pharmacology Reports, 2023)

A novel approach to environmental pollution management/remediation techniques using derived advanced materials - Rashmi Singh; Melvin S. Samuel; Madhumita Ravikumar; Selvarajan Ethiraj; V.S. Kirankumar; Mohanraj Kumar; R. Arulvel; Sagadevan Suresh (Chemosphere, 2023)

Evidence of Paleoproterozoic metamorphism in Vestfold Hills, East Antarctica: Insights from phase equilibria modelling and monazite CHIME dating - Aditya Naik; Devsamridhi Arora; Mayuri Pandey; Naresh Chandra Pant; Rashmi Gupta (Polar Science, 2023)

Evaluation of different sugars for glycation modifications of chitosan to improve its functionality for food preservation - Chaitra R. Bandiwadekar; Ashwini D. Jagdale; Ankita S. Durge; Tejaswini A. Pachpor; Rashmi S. Tupe (Food Hydrocolloids, 2023)

Modification of sunnhemp (Crotalaria juncea) protein isolate by high intensity ultrasound: Impact on the molecular structure, amino acid composition and nutritional profiling - Rashmi Rawat; Charanjiv Singh Saini (Food Bioscience, 2023)

Prevalence of extended spectrum β-lactam, methicillin, and vancomycin resistant zoonotic bacterial pathogens in milk - Raghu Vishweswaraiah; Divya Sharma; Mehak Mehta; Avinash Jaswal; Kriti Dua; Rashmi Mallappa; Diwas Pradhan; A.S. Mariya Divanshi; Gurjinder Kaur; Naresh Kumar; Anil Kumar Puniya (Food and Humanity, 2023)

A modified multifractal detrended fluctuation analysis to study the precipitation across northeast India - Rashmi Rekha Devi; Surajit Chattopadhyay (Dynamics of Atmospheres and Oceans, 2023)

An observing system experiment framework for the tropical Indian Ocean salinity: A case study using a constellation of three satellites - Smitha Ratheesh; Neeraj Agarwal; Rashmi Sharma (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Detection of materially coherent eddies from satellite altimetry in the Bay of Bengal - Lijin Jayan; M. Jishad; Neeraj Agarwal; Rashmi Sharma; Manikandan Mathur (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Comparative secondary metabolite expression in callus cultures and mother plant in Barleria prionitis L. - Rashmi Ranade; Neelu Joshi; Subhash Kudale (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Curcumin and PCI-34051 combined treatment ameliorates inflammation and fibrosis by affecting MAP kinase pathway - Ramiya Islam; Rashmi Singh (Inflammopharmacology, 2023)

Evaluation of indigenous accessions of wheat for spot blotch resistance at the seedling and adult plant stage - Yaratha Nishith Reddy; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Mahender Singh Saharan; Sundeep Kumar; Mukesh Kumar Khokhar; Naresh Kumar; Rashmi Aggarwal (Indian Phytopathology, 2023)

Stacked ensemble model for reservoir characterisation to predict log properties from seismic signals - Pallabi Saikia; Rashmi Dutta Baruah (Computational Geosciences, 2023)

Identifying research practices toward achieving health equity principles within the Cancer Prevention and Control Research Network - Prajakta Adsul; Jessica Islam; Perla Chebli; Julie Kranick; Sarah Nash; Hannah Arem; Stephanie Wheeler; Melissa Lopez-Pentecost; Victoria Foster; Rashmi K. Sharma; Tisha Felder; Betsy Risendal; et al. (Cancer Causes & Control, 2023)
Purpose Although there is national recognition for health equity-oriented research, there is limited guidance for researchers to engage partnerships that promote health equity in cancer research. The Cancer Prevention and Control Research Network’s (CPCRN) Health Equity Work Group developed a toolkit to guide researchers in equitable collaborations. Methods The CPCRN’s Health Equity Work Group collectively outlined health and racial equity principles guiding research collaborations with partners that include communities, community-based organizations, implementing partners in the clinical setting including providers and health care organizations, and policy makers. Using a network-wide survey to crowdsource information around ongoing practices, we leveraged and integrated the network’s experience and collaborations. Results Data from the survey formed the preliminary basis for the toolkit, with a focus on sharing fiscal resources with partners, training and capacity building, collaborative decision-making, community-driven research agenda setting, and sustainability. The final toolkit provides reflection considerations for researchers and collated exemplary resources, supported by the contemporary research. Conclusions The toolkit provides a guide to researchers at all experience levels wanting to engage in equitable research collaborations. Future efforts are underway to evaluate whether and how researchers within and outside CPCRN are able to incorporate these principles in research collaborations.

Biodegradation of di-2-ethylhexyl phthalate by Bacillus firmus MP04 strain: parametric optimization using full factorial design - Madhavi Rashmi; Tanuja Singh; Nitesh Singh Rajput; Shweta Kulshreshtha (Biodegradation, 2023)

Functionalized graphene-based ultrafiltration and thin-film composite nanofiltration membranes for arsenic, chromium, and fluoride removal from simulated groundwater: Mechanism and effect of pH - Mitil Koli; Rashmi Ranjan; Swatantra P. Singh (Process Safety and Environmental Protection, 2023)

Zircon U-Pb and trace element constraints on the evolution of the Tonian (829–831 Ma) alkaline plutons within the Mercara Shear Zone, south India - Sarbartha Shankar Mishra; Chandan Kumar Boraiaha; Jiří Sláma; Rashmi Chandan (Geochemistry, 2023)

Impact of grid size on spatiotemporal prediction of fine particulate matter - Rashmi Choudhary; Amit Agarwal (Atmospheric Pollution Research, 2023)

Low expression of lipoxygenase 3 (LOX3) enhances the retention of kernel tocopherols in maize during storage - Shalma Maman; Vignesh Muthusamy; Ashvinkumar Katral; Rashmi Chhabra; Nisrita Gain; Shashidhar Bayappa Reddappa; Suman Dutta; Amolkumar Uddhaorao Solanke; Rajkumar Uttamrao Zunjare; Chirravuri Naga Neeraja; Devendra Kumar Yadava; Firoz Hossain (Molecular Biology Reports, 2023)

Dissecting the Relationship Between Neuropsychiatric and Neurodegenerative Disorders - Rohan Gupta; Dia Advani; Divya Yadav; Rashmi K Ambasta; Pravir Kumar (Molecular Neurobiology, 2023)

Fate and stabilization of labile carbon in a sandy boreal forest soil – A question of nitrogen availability? - Nele Meyer; Outi-Maaria Sietiö; Sylwia Adamczyk; Per Ambus; Christina Biasi; Bruno Glaser; Subin Kalu; Angela Martin; Kevin Z. Mganga; Miikka Olin; Aino Seppänen; Rashmi Shrestha; et al. (Applied Soil Ecology, 2023)

Evaluating the applicability of Brachiaria mutica (Forssk.) (Paragrass) and Cyperus rotundus L. (Nutgrass) as bioadsorbents to remove Cr(VI): isotherms, kinetics, and thermodynamic studies - Dinesh Arora; Amit Arora; Asha Singh; Rashmi Agarwal; Renu Bala; Sunil Kumar (Sustainable Water Resources Management, 2023)

Stable and fast oil recovery by environmentally friendly and easy to synthesize pristine graphitic carbon nitride - Pranay Gandharapu; Rashmi Chandrabhan Shende; Manoj K. Jangid; Amartya Mukhopadhyay (Clean Technologies and Environmental Policy, 2023)

Combining clinical and molecular characterization of CDH1: a multidisciplinary approach to reclassification of a splicing variant - Corrine Fillman; Arravinth Anantharajah; Briana Marmelstein; Monica Dillon; Carolyn Horton; Candace Peterson; Joseph Lopez; Rashmi Tondon; Terra Brannan; Bryson W Katona (Familial Cancer, 2023)

Biological approaches for E-waste management: A green-go to boost circular economy - Rashmi Dixit; Sunil Kumar; Govind Pandey (Chemosphere, 2023)

Practical use of smartphone cameras in rip current monitoring studies - V V Arun Kumar Surisetty; Ch Venkateswarlu; M Ramesh; B Gireesh; C V Naidu; L Sheela Nair; Rashmi Sharma (Ocean & Coastal Management, 2023)

Harnessing unexplored medicinal values of the red listed South African weed Erigeron bonariensis: From ethnobotany to biomedicine - Vishal B. Mahanur; Rahul R. Rajge; Rashmi Saxena Pal; M.V.N.L. Chaitanya; Sukriti Vishwas; Saurabh Gupta; Gaurav Gupta; Deepak Kumar; Oluwafemi Omoniyi Oguntibeju; Zia ur Rehman; Faris F. Aba Alkhayl; Vinay Thakur; et al. (South African Journal of Botany, 2023)

Adsorptive desulphurization of fuels by hypercrosslinked nanoporous polymers derived from polycyclic aromatic hydrocarbons - Anuj Rawat; Raeesh Muhammad; Raj K. Singh; Rashmi; Pratiksha Joshi; Om P. Khatri; Vimal Chandra Srivastava; Paritosh Mohanty (Journal of Cleaner Production, 2023)

Farm diversification strategies, dietary diversity and farm size: Results from a cross-country sample in South and Southeast Asia - Francesco Tacconi; Katharina Waha; Jonathan Jesus Ojeda; Peat Leith; Caroline Mohammed; William N. Venables; Jai C. Rana; Rakesh Bhardwaj; Rashmi Yadav; Sudhir Pal Ahlawat; James Hammond; Mark van Wijk (Global Food Security, 2023)

Techno-functional characterization of fecal lactobacilli isolates of Bos indicus calves for probiotic properties - Rakesh Chouraddi; Sachin Kumar; Brijesh Kumar; Manika Bhatia; Vinay Venkatesh Varada; Nitin Tyagi; Rashmi Hogarehalli Mallapa (Veterinary Research Communications, 2023)

Presence of Extracellular Alpha-Synuclein Aggregates Trigger Astrocytic Degeneration Through Enhanced Membrane Rigidity and Deregulation of Store-Operated Calcium Entry (SOCE) into the Endoplasmic Reticulum - Aishwarya Raj; Roon Banerjee; Rashmi Santhoshkumar; Chandrasekhar Sagar; Indrani Datta (Molecular Neurobiology, 2023)

Distinct Behavior of Biochar Modulating Biogeochemistry of Salt-Affected and Acidic Soil: a Review - Shivvendra Singh; Nidhi Luthra; Sandip Mandal; Daniel Prakash Kushwaha; Shakti Om Pathak; Debarati Datta; Rashmi Sharma; Biswajit Pramanick (Journal of Soil Science and Plant Nutrition, 2023)

Development of novel gene-based markers for waxy1 gene and their validation for exploitation in molecular breeding for enhancement of amylopectin in maize - Zahirul Alam Talukder; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2023)

A new approach for seasonal prediction using the coupled model CFSv2 with special emphasis on Indian Summer Monsoon - T. S. Fousiya; Chellappan Gnanaseelan; Subrota Halder; Rashmi Kakatkar; Jasti S. Chowdary; Patekar Darshana; Anant Parekh (International Journal of Climatology, 2023)
Predicting Indian Summer Monsoon (ISM) is a challenging task due to its complexity and nonlinear interactions. Any improvement in the seasonal prediction skill of models would highly benefit a large population and the economy. In this context, three sets of hindcast experiments are carried out for 9 months each, for the period 1993–2019, using the National Centers for Environmental Prediction‐Climate Forecast System version 2 (NCEP‐CFSv2). The experiments differ from each other in the way they are initialized: one is initialized in February (FebIC), and the second in May (MayIC), whereas in the third one (Exp), ocean is initialized in February and allowed to evolve but the atmosphere reinitialized every month up to May. So, hindcasts of Exp are from the pre‐evolved ocean with realistic atmospheric initial conditions of May. The representation of mean tropical Indo‐Pacific Sea surface temperature (SST), Walker circulation, mean monsoon circulation and moisture transport to Indian landmass are better represented in Exp. The ISM rainfall prediction (interannual) skill improved in Exp as compared to FebIC and MayIC over central India, Indian land mass and extended monsoon region. The initialization strategy adopted in Exp reduces the model initial shocks especially in the upper ocean heat content and SST over the Indo‐Pacific region, thereby offering a cost‐effective alternative approach for reduction of the initial shock. The well‐known cold tongue SST bias over the equatorial Pacific in MayIC is reduced significantly in Exp with improved monsoon teleconnections and the overdependence of ISM rainfall on El Niño Southern Oscillation in MayIC is also reduced in Exp.

Exploring the multifaceted potential of chlorogenic acid: Journey from nutraceutical to nanomedicine - Sachin Kumar Singh; Kiran Thakur; Vishal Sharma; Mamta Saini; Diksha Sharma; Sukriti Vishwas; Violina Kakoty; Rashmi Saxena Pal; M.V.N.L. Chaitanya; M.Ravindra Babu; Saurabh Gupta; Zia ur Rehman; et al. (South African Journal of Botany, 2023)

Safer and effective alternatives to perfluoroalkyl-based surfactants in etching solutions for the semiconductor industry - Rashmi Sharma; Shreyas Shelke; Mohammad Bagheri Kashani; Gregory Morose; Christopher Christuk; Ramaswamy Nagarajan (Journal of Cleaner Production, 2023)

Bioassay guided fractionation of anthelmintic bioactive compounds from surinam cherry (Eugenia uniflora L.) fruits - H.B. Rashmi; B.K. Bettadaiah; P.S. Negi (Food Bioscience, 2023)

Cost-effective bio-methanation via oxalic acid coupled sonication pretreatment of Gracilaria salicornia - Rashmi Gondi; Akila; Yukesh Kannah Ravi; S. Kavitha; Siham Y. Al-Qaradawi; Dinakar Challabathula; Gopalakrishnan Kumar; J. Rajesh Banu (Biomass and Bioenergy, 2023)

Efficacy of indole-3-acetic acid-producing PGPFs and their consortium on physiological and biochemical parameters of Trigonella foenum-graecum L - Rashmi Thakor; Harsh Mistry; Himanshu Bariya (Horticulture, Environment, and Biotechnology, 2023)

Understanding the multifaceted role of miRNAs in Alzheimer’s disease pathology - Sharanjot Kaur; Harkomal Verma; Sukhchain Kaur; Prabhakar Gangwar; Anuradha Yadav; Bharti Yadav; Rashmi Rao; Monisha Dhiman; Anil Kumar Mantha (Metabolic Brain Disease, 2023)

Statins mimic and free radical scavenging potential of phytoconstituents of methanolic pod extract of Prosopis cineraria (L.) Druce - Noopur Jaipal; Heera Ram; Pramod Kumar; Jaykaran Charan; Priya Kashyap; Suman Chowdhury; Rashmi Tripathi; Shivani Kumar; Bhim Pratap Singh; Anil Panwar (Vegetos, 2023)

Analysis of atmospheric and oceanic conditions during unusual occurrence of tropical cyclone Gulab and Shaheen in North Indian Ocean - Neeru Jaiswal; M Jishad; Sanjib K Deb; Atul K Varma; Neeraj Agarwal; Rashmi Sharma (Journal of Earth System Science, 2023)

Benzoxazine-grafted-chitosan biopolymer films with inherent disulfide linkage: Antimicrobial properties - Sangeeta Sahu; Rashmi Niranjan; Richa Priyadarshini; Bimlesh Lochab (Chemosphere, 2023)

Expression of Arabidopsis NPR1 (AtNPR1) in Brassica juncea var Varuna confers significant resistance against Sclerotinia sclerotiorum and Alternaria brassicae - Rashmi Verma; S. Hamsa; Sayanti Mandal; Jagreet Kaur (Physiological and Molecular Plant Pathology, 2023)

Allogenic bone marrow-derived mesenchymal stem cells and its conditioned media for repairing acute and sub-acute peripheral nerve injuries in a rabbit model - T.B. Sivanarayanan; Irfan Ahmad Bhat; Khan Sharun; Sangeetha Palakkara; Rashmi Singh; Remya; Mehtab Singh Parmar; Rahul Bhardwaj; Vikash Chandra; Palanivelu Munuswamy; Prakash Kinjavdekar; A.M. Pawde; et al. (Tissue and Cell, 2023)

Production of polyhydroxyalkanoate (PHA) copolymer from food waste using mixed culture for carboxylate production and Pseudomonas putida for PHA synthesis - Rashmi Chandra; Aranksha Thakor; Tizazu H. Mekonnen; Trevor C. Charles; Hyung-Sool Lee (Journal of Environmental Management, 2023)

Potential of waste stream in conversion into sustainable metabolites: An overview and update - Neha Kukreti; Sonika Kag; Pravir Kumar; Rashmi Kataria (Bioresource Technology Reports, 2023)

Diversity of naturalized and invasive plant species across land use types in an inner Tarai Valley of Central Nepal - Rashmi Paudel; Bharat Babu Shrestha; Lila Nath Sharma; Bhaskar Adhikari; Mohan Siwakoti (Tropical Ecology, 2023)

Biochemical responses in wheat due to Puccinia triticina infection - Rashmi D.; Shipra Sharma; Kavin K. Soni; S. I. Patel (Indian Phytopathology, 2023)

Growth potential and immunity of the Indian white shrimp, Penaeus indicus (H. Milne-Edwards, 1837), cultured in grow-out ponds at varying densities and salinities - Akshaya Panigrahi; Rashmi Ranjan Das; I. F. Biju; A. Saravanan; Soumyabrata Sarkar; P. S. S. Shyne Anand; L. Christina; J. Antony; K. P. Kumaraguru Vasagam; K. Ambasankar; M. Jayanthi; M. Kumaran; et al. (Aquaculture International, 2023)

Variation in the Eggplant (Solanum melongena) Genotypes for Health-Promoting Bioactive Compounds and Agro-Morphological Traits - Rashmi Kumari; Shirin Akhtar; Shashank Shekhar Solankey; Aakanksha (Agricultural Research, 2023)

A pathway for multi-stage cyclone-induced hazard tracking—case study for Yaas - Atul Kumar Varma; Neeru Jaiswal; Ayan Das; Mukesh Kumar; Nikhil V. Lele; Rojalin Tripathy; Saroj Maity; Mehul Pandya; Bimal Bhattacharya; Anup Kumar Mandal; M. Jishad; M. Seemanth; et al. (Natural Hazards, 2023)

Evaluation of Standardized MODIS-Terra Satellite-Derived Evapotranspiration Using Genetic Algorithm for Better Field Applicability in a Tropical River Basin - Utkarsh Kumar; Rashmi; Ankur Srivastava; Nikul Kumari; Chandranath Chatterjee; Narendra Singh Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2023)

Role of ions and their transporters in combating salt stress in Pandanus odorifer (Forssk.) Kuntze - Deo Rashmi; Waquar A. Ansari; Narendra Y. Kadoo; Vitthal T. Barvkar; Rupesh Deshmukh; Altafhusain B. Nadaf (Acta Physiologiae Plantarum, 2023)

High efficient removal of 4-aminophenylarsonic acid from aqueous solution via enhanced FeOOH using Mn(VII) - Tista Prasai Joshi; Rashmi Koju; Hanyang Cheng; Zenglu Qi; Ruiping Liu; Yaohui Bai; Chengzhi Hu; Jianfeng Peng; Dev Raj Joshi (Environmental Science and Pollution Research, 2023)

Geo-environmental factors’ influence on mining operation: an indirect effect of managerial factors - Padma Charan Mishra; Rashmi Ranjan Panigrahi; Avinash K. Shrivastava (Environment, Development and Sustainability, 2023)

Mutational analysis of a conserved positive charge in the c-ring of E. coli ATP synthase - Rashmi K. Shrestha; Michael W. Founds; Sam J. Shepard; Mallory M. Rothrock; Amy E. Defnet; P. Ryan Steed (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Synthesis, spectral analysis, DFT calculations, biological potential and molecular docking studies of indole appended pyrazolo-triazine - S. M. Basavarajaiah; G. Y. Nagesh; Mohammad Javeed; Rashmi Bhat; S. Nethravathi; Jeelan N. Basha; K. Ramakrishna Reddy; C. Nisarga; Pooja Srinivas (Molecular Diversity, 2023)

Circulating Cell-Free DNA Level in Prediction of COVID-19 Severity and Mortality: Correlation of with Haematology and Serum Biochemical Parameters - Sridhar Mishra; Devanshi B. Dubey; Krachi Agarwal; Deval B. Dubey; Shweta Verma; Nida Shabbir; Rashmi Kushwaha; D Himanshu Reddy; Uma Shankar Singh; Wahid Ali (Indian Journal of Clinical Biochemistry, 2023)

Biofloc-based farming of Indian white shrimp, Penaeus indicus, in recirculating aquaculture system (RAS) enriched with rotifers as feed supplement - A. Panigrahi; Rashmi R. Das; Soumyabrata Sarkar; R. Aravind; P. N. Rekha; K. P. Sandeep (Aquaculture International, 2023)

Halophilic CO2-fixing microbial community as biocatalyst improves the energy efficiency of the microbial electrosynthesis process - Rashmi Kiran; Ravineet Yadav; Devangi Sathe; Sunil A. Patil (Bioresource Technology, 2023)

Variation in anthocyanin pigmentation by R1-navajo gene, development and validation of breeder-friendly markers specific to C1-Inhibitor locus for in-vivo haploid production in maize - Nisrita Gain; Rashmi Chhabra; Shivani Chandra; Rajkumar U. Zunjare; Suman Dutta; Gulab Chand; Konsam Sarika; Elangbam L. Devi; Aruna Kumar; Jayanthi Madhavan; Vignesh Muthusamy; Firoz Hossain (Molecular Biology Reports, 2023)

Targeted next-generation sequencing identifies novel deleterious variants in ANK1 gene causing severe hereditary spherocytosis in Indian patients: expanding the molecular and clinical spectrum - Tejashree Anil More; Rati Devendra; Rashmi Dongerdiye; Prashant Warang; Prabhakar Kedar (Molecular Genetics and Genomics, 2023)

Molecular characterization and variability analyses of apple stem pitting virus and apple stem grooving virus isolates infecting apple in Kashmir, India - Rashmi Suman; Narayan Rishi; Sunny Dhir; Vipin Hallan; Vanita Chandel (Indian Phytopathology, 2023)

Nigrospora zimmermanii Crous: an addition to Indian Mycoflora - Rashmi Dubey (Indian Phytopathology, 2023)

Nuclear architecture and the structural basis of mitotic memory - Mamilla Soujanya; Ashish Bihani; Nikhil Hajirnis; Rashmi U. Pathak; Rakesh K. Mishra (Chromosome Research, 2023)

Quantification of excess Carbon-14 specific activity in terrestrial biota in the off-site locations of the PHWR nuclear power plant at Kaiga, India - N. Karunakara; Renita Shiny D'Souza; S. Rashmi Nayak; S. Bharath; K. Arya Krishnan; B.N. Dileep; P.M. Ravi (Science of The Total Environment, 2023)

Metallic ion layers in planetary atmosphere: Boundary conditions and IDP flux - Jayesh P. Pabari; Srirag N. Nambiar; Rashmi; Sonam Jitarwal (Planetary and Space Science, 2023)

A thermo-chemical and biotechnological approaches for bamboo waste recycling and conversion to value added product: Towards a zero-waste biorefinery and circular bioeconomy - Zheli Ding; Sanjeev Kumar Awasthi; Manish Kumar; Vinay Kumar; Andrei Mikhailovich Dregulo; Vivek Yadav; Raveendran Sindhu; Parameswaran Binod; Surendra Sarsaiya; Ashok Pandey; Mohammad J. Taherzadeh; Rashmi Rathour; et al. (Fuel, 2023)

Nitrate and phosphate uptake dynamics in two halotolerant strains of Chlorella vulgaris is differentially influenced by carbon, nitrogen and phosphorus supply - Faqih Shuhaili; Mariona Segura-Noguera; Mathumathy; Rashmi Vijayaraghavan; Sivasudha Thilagar; Uma Lakshmanan; Dharmar Prabaharan; Seetharaman Vaidyanathan (Chemical Engineering Journal, 2023)

A review on current advances in the energy and cost effective pretreatments of algal biomass: Enhancement in liquefaction and biofuel recovery - S. Kavitha; Rashmi Gondi; R. Yukesh Kannah; Gopalakrishnan Kumar; J. Rajesh Banu (Bioresource Technology, 2023)

Physiological race characterisation of Fusarium oxysporum strains infecting tomato employing candidate pathogenicity genes and host resistance - Govindan Pothiraj; Veerubommu Shanmugam; Aditya Tyagi; Zakir Hussain; Rashmi Aggarwal; Manakkatt Mohan Haritha; Karuppiah Manikandan; Awani Kumar Singh; Gopala Krishnan (World Journal of Microbiology and Biotechnology, 2023)

Satellite Oceanography: Revolutionizing the Blue Economy - Rashmi Sharma; Joaquim Goes; Jacques Verron (Journal of the Indian Society of Remote Sensing, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

A Study of Mixing and Biological Activity in the North Indian Ocean Using Finite Size Lyapunov Exponents - Jai Kumar; Ravi Kamal Choudhary; Manikandan Mathur; Neeraj Agarwal; Rashmi Sharma (Journal of the Indian Society of Remote Sensing, 2023)

Growth, survival, and immune potential of post larvae of Indian white shrimp, Penaeus indicus (H. Milne Edwards, 1937) in different salinities with biofloc system (BFT) during nursery phase - Rashmi Ranjan Das; Akshaya Panigrahi; Soumyabrata Sarkar; A. Saravanan; I. F. Biju; K. Ambikanandham; M. Jayanthi; S. Kannappan (Aquaculture International, 2023)

Land use drivers of riverine methane dynamics in a tropical river basin, India - Latika Patel; Rashmi Singh; Shoji D. Thottathil (Water Research, 2023)

Forest plantation species classification using Full-Pol-Time-Averaged SAR scattering powers - Priyanka; Rajat; Ram Avtar; Rashmi Malik; M. Musthafa; Virendra S. Rathore; Praveen Kumar; Gulab Singh (Remote Sensing Applications: Society and Environment, 2023)

Phytochemical screening, antibacterial, anti-biofilm and quorum sensing inhibiting activity of Alpinia nigra leaf extract against infectious pathogen Pseudomonas aeruginosa PAO1 - Manish Kumar Gupta; Rashmi Singh; Latha Rangan (Food Control, 2023)

Thermodynamics of benzoquinone-induced conformational changes in nucleic acids and human serum albumin - Atala B. Jena; Rashmi R. Samal; Jagneshwar Dandapat; Umakanta Subudhi (Chemico-Biological Interactions, 2023)

Earthworm stocking density regulates microbial community structure and fatty acid profiles during vermicomposting of lignocellulosic waste: Unraveling the microbe-metal and mineralization-humification interactions - Jinnashri Devi; Ratul Pegu; Himadri Mondal; Rashmi Roy; Satya Sundar Bhattacharya (Bioresource Technology, 2023)

Genetic analysis of a Fanconi anemia case revealed the presence of FANCF mutation (exon 1;469>C-T) with implications to develop acute myeloid leukemia - Chinmay Kumar Behera; Gummalla Gyandeep; Reshmi Mishra; Rashmi Priya Mohanty; Aditi Pal; Jyotika Behera; Sagnika Samal; Biswadeep Das (Molecular Biology Reports, 2023)

Association of underlying comorbidities and progression of COVID-19 infection amongst 2586 patients hospitalised in the National Capital Region of India: a retrospective cohort study - Rashmi Rana; Vivek Ranjan; Naveen Kumar; Parul Chugh; Kamini Khillan; Atul Gogia; Devinder Singh Rana; Nirmal Kumar Ganguly (Molecular and Cellular Biochemistry, 2023)

Monitoring the distribution pattern and invasion status of Ageratina adenophora across elevational gradients in Sikkim Himalaya, India - Anil Kumar Verma; Rashmi Nayak; N Manika; Kiran Bargali; Vashist Narayan Pandey; Lal Babu Chaudhary; Soumit Kumar Behera (Environmental Monitoring and Assessment, 2023)

Correction to: Pollen staining is a rapid and cost‑effective alternative to marker‑assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Effect of GNE Mutations on Cytoskeletal Network Proteins: Potential Gateway to Understand Pathomechanism of GNEM - Rashmi Yadav; Jyoti Oswalia; Anu Ghosh; Ranjana Arya (NeuroMolecular Medicine, 2022)

Transcriptomic analysis of bakanae disease resistant and susceptible rice genotypes in response to infection by Fusarium fujikuroi - Bishnu Maya Bashyal; Kirti Rawat; Pooja Parmar; Ashish Kumar Gupta; Sangeeta Gupta; S Gopala Krishnan; Ravish Choudhary; Sezai Ercisli; Antonija Kovacevic; Rashmi Aggarwal (Molecular Biology Reports, 2022)

Understanding cross-tolerance mechanism and effect of drought priming on individual heat stress and combinatorial heat and drought stress in chickpea - Renu Yadav; Sumandeep Juneja; Rashpal Kumar; Rashmi Saini; Sanjeev Kumar (Journal of Crop Science and Biotechnology, 2022)

Characterization of crtRB1- and vte4-based biofortified sweet corn inbreds for seed vigour and physico-biochemical traits - Hema S. Chauhan; Vignesh Muthusamy; Tuhin Rashmi; Sudipta Basu; Anjali Anand; Brijesh K. Mehta; Nisrita Gain; Rajkumar U. Zunjare; Ashok K. Singh; Hari S. Gupta; Firoz Hossain (Journal of Applied Genetics, 2022)

Alternate day fasting and time-restricted feeding may confer similar neuroprotective effects during aging in male rats - Sukanya Bhoumik; Rashmi Kesherwani; Raushan Kumar; Syed Ibrahim Rizvi (Biogerontology, 2022)

Defatted silkworm pupae meal as an alternative protein source for cattle - K. M. Rashmi; M. Chandrasekharaiah; N. M. Soren; K. S. Prasad; C. G. David; Y. Thirupathaiah; V. Shivaprasad (Tropical Animal Health and Production, 2022)

Protective efficacy of Coriandrum sativum seeds against arsenic induced toxicity in Swiss albino mice - Arun Kumar; Vikas Kumar; Vivek Akhouri; Ranjit Kumar; Mohammad Ali; Tuhin Rashmi; Gyanendra Bahadur Chand; Sushil Kumar Singh; Ashok Kumar Ghosh (Toxicological Research, 2022)

Usability of Brachiaria mutica (para grass) and Cyperus rotundus (nut grass) as bioadsorbents for the removal of methylene blue from aqueous solution: isotherms, kinetics, and thermodynamics studies - Dinesh Arora; Amit Arora; Asha Singh; Rashmi Agarwal; Sunil Kumar (Sustainable Water Resources Management, 2022)

Phytoplankton Population Dynamics in Relation to Environmental Variables at Paradip Port, East Coast of India - Sabnam Banoo; Chinmayee Acharya; Rashmi Ranjan Behera; Deepty Ranjan Satapathy; Chitta Ranjan Panda (Thalassas: An International Journal of Marine Sciences, 2022)

Next-generation Tumor-homing Induced Neural Stem Cells as an Adjuvant to Radiation for the Treatment of Metastatic Lung Cancer - Alison R. Mercer-Smith; Andrew Buckley; Alain Valdivia; Wulin Jiang; Morrent Thang; Noah Bell; Rashmi J. Kumar; Hunter N. Bomba; Alex S. Woodell; Jie Luo; Scott R. Floyd; Shawn D. Hingtgen (Stem Cell Reviews and Reports, 2022)

Drought priming induces chilling tolerance and improves reproductive functioning in chickpea (Cicer arietinum L.) - Rashmi Saini; Rangman Das; Arindam Adhikary; Rashpal Kumar; Inderjit Singh; Harsh Nayyar; Sanjeev Kumar (Plant Cell Reports, 2022)

Assessment of antibacterial and anti-biofilm effects of zinc ferrite nanoparticles against Klebsiella pneumoniae - Rashmi P. Sharma; Siddheshwar D. Raut; Vijaykumar V. Jadhav; Ramjan M. Mulani; Ambadas S. Kadam; Rajaram S. Mane (Folia Microbiologica, 2022)

A novel prognostic system based on clinical and laboratory parameters for childhood Guillain–Barre syndrome - Ishita Tiwari; Areesha Alam; Chandra kanta; Sciddhartha Koonwar; Ravindra Kumar Garg; Shweta Pandey; Amita Jain; Rashmi Kumar (Acta Neurologica Belgica, 2022)

Field and geochemical characteristics of the amphibolites from the Gadag greenstone belt, southern India: Implications for petrogenesis - Chandan Kumar Boraiaha; Annappa G Ugarkar; Rashmi Chandan (Journal of Earth System Science, 2022)

Autochthonous Limosilactobacillus reuteri BFE7 and Ligilactobacillus salivarius BF17 probiotics consortium supplementation improves performance, immunity, and selected gut health indices in Murrah buffalo calves - Vinay Venkatesh Varada; Amrish Kumar Tyagi; Praveen Sivakumara Banakar; Asit Das; Nitin Tyagi; Rashmi Hogarehalli Mallapa; Sachin Kumar (Veterinary Research Communications, 2022)

First report of apple stem grooving virus infection in loquat from India - Rashmi Suman; Asha Rani; Narayan Rishi; Sunny Dhir; Vipin Hallan; Vanita Chandel (VirusDisease, 2022)

Pollen staining is a rapid and cost-effective alternative to marker-assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Microbial Journey: Mount Everest to Mars - Utkarsh Sood; Gauri Garg Dhingra; Shailly Anand; Princy Hira; Roshan Kumar; Jasvinder Kaur; Mansi Verma; Nirjara Singhvi; Sukanya Lal; Charu Dogra Rawat; Vineet Kumar Singh; Jaspreet Kaur; et al. (Indian Journal of Microbiology, 2022)

Free radical biology in neurological manifestations: mechanisms to therapeutics interventions - Rahul Tripathi; Rohan Gupta; Mehar Sahu; Devesh Srivastava; Ankita Das; Rashmi K Ambasta; Pravir Kumar (Environmental Science and Pollution Research, 2022)

Unboxing the molecular modalities of mutagens in cancer - Smita Kumari; Sudhanshu Sharma; Dia Advani; Akanksha Khosla; Pravir Kumar; Rashmi K. Ambasta (Environmental Science and Pollution Research, 2022)

Multiple sequence alignment and phylogenetic analysis of wheat pathogens using conserved genes for identification and development of diagnostic markers - Sangeeta Gupta; Rashmi Aggarwal; Sapna Sharma; Malkhan S. Gurjar; Bishnu M. Bashyal; Mahender S. Saharan; Shweta Agarwal (Cereal Research Communications, 2022)

Biogenesis and characterization of proficient silver nanoparticles employing marine procured fungi Hamigera pallida and assessment of their antioxidative, antimicrobial and anticancer potency - Harsh Mistry; Rashmi Thakor; Himanshu Bariya (Biotechnology Letters, 2022)

Dewatering performance of sludge using coconut shell biochar modified with ferric chloride (Sludge dewatering using bio-waste) - H. R. Rashmi; C. P. Devatha (International Journal of Environmental Science and Technology, 2022)

Fish intake and risk of melanoma in the NIH-AARP diet and health study - Yufei Li; Linda M. Liao; Rashmi Sinha; Tongzhang Zheng; Terrence M. Vance; Abrar A. Qureshi; Eunyoung Cho (Cancer Causes & Control, 2022)

Electroantennography and behavioral studies of Eublemma amabilis [Moore] and Pseudohypatopa pulverea [Meyr] in relation to volatiles of lac insect (Kerria lacca Kerr.) and its associated products - Arumugam Mohanasundaram; Anees Kaprakkaden; Suresh M. Nebapure; Kewal Krishan Sharma; Naiyar Naaz; Rashmi Mishra; Upnit Shree (International Journal of Tropical Insect Science, 2022)

Prolonged effects of DPP-4 inhibitors on steato-hepatitic changes in Sprague–Dawley rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2022)

Inventory and data analysis of leaf inhabiting fungi of protected areas of Northern Maharashtra, India - Rashmi Dubey; Amit Diwakar Pandey (Indian Phytopathology, 2022)

Identification and validation of simple sequence repeats markers in Tilletia indica and compatibility assay of monosporidial lines - Malkhan Singh Gurjar; Prachi Jain; Shekhar Jain; Naresh Kumar; Mahender Singh Saharan; Rashmi Aggarwal (Indian Phytopathology, 2022)

Biocatalytic polymeric membranes to decrease biofilm fouling and remove organic contaminants in wastewater: a review - Jenet George; Srinidhi Sonai Anand; Ponnusamy Senthil Kumar; Priyanka Saravanan; Rashmi Lenin; Devi Sri Rajendran; Swethaa Venkataraman; Vinoth Kumar Vaidyanathan; Dai-Viet Nguyen Vo (Environmental Chemistry Letters, 2022)

Infection of human microglial cell line CHME-3 to study neuropathogenesis of chikungunya virus - Syed Wasifa Qadri; Narendra Kumar; Rashmi Santhoshkumar; Anita Desai; Vasanthapuram Ravi; Manjunatha M. Venkataswamy (Journal of NeuroVirology, 2022)

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

Communities of culturable yeasts and yeast-like fungi in oligotrophic hypersaline coastal waters of the Arabian Gulf surrounding Qatar - Rashmi Fotedar; Mark Chatting; Anna Kolecka; Aisha Zeyara; Amina Al Malki; Ridhima Kaul; Sayed J. Bukhari; Mohammed Abdul Moaiti; Eric J. Febbo; Teun Boekhout; Jack W. Fell (Antonie van Leeuwenhoek, 2022)

Strength and durability performance of geopolymer binder of ambient cured alkali-activated MSW rejected waste and GGBFS mixes - Rashmi Shrivas; Bala Ramudu Paramkusam; Shyam Bihari Dwivedi (Environmental Science and Pollution Research, 2022)

Effect of Telmisartan on Arsenic-Induced (Sub-chronic) Perturbations in Redox Homeostasis, Pro-inflammatory Cascade and Aortic Dysfunction in Wistar Rats - B. Rudresh Gowda; N. Prakash; C. R. Santhosh; B. H. Pavithra; Rashmi Rajashekaraiah; M. L. Sathyanarayana; Suguna Rao; Prashantkumar Waghe; K. R. Anjan Kumar; G. R. Shivaprasad; Y. Muralidhar (Biological Trace Element Research, 2022)

Integrated view of molecular diagnosis and prognosis of dengue viral infection: future prospect of exosomes biomarkers - Rashmi Rana; Ravi Kant; Dinesh Kaul; Anil Sachdev; Nirmal Kumar Ganguly (Molecular and Cellular Biochemistry, 2022)

NMR based CSF metabolomics in tuberculous meningitis: correlation with clinical and MRI findings - Rashmi Parihar; Ruchi Shukla; Bikash Baishya; Jayantee Kalita; Rudrashish Haldar; Usha Kant Misra (Metabolic Brain Disease, 2022)

High-pressure polymorphs of olivine and silica in Kamargaon (L6) chondrite by laser micro-Raman and XRD studies - Bhaskar J Saikia; G Parthasarathy; Rashmi R Borah (Journal of Earth System Science, 2022)

Functional analysis of SCD1 gene involved in pathogenicity of spot blotch disease of wheat causing fungus Bipolaris sorokiniana - Kartar Singh; Rashmi Aggarwal; Praveen Kumar Verma; Sandhya Verma; Sapna Sharma; C. Manjunatha; Manoj Choudhary; Deepika Kulshreshtha; Kirti Rawat (Indian Phytopathology, 2022)

Comparative evaluation of proliferative potential and replicative senescence associated changes in mesenchymal stem cells derived from dental pulp and umbilical cord - Monalisa Das; Ankita Das; Ananya Barui; Ranjan Rashmi Paul (Cell and Tissue Banking, 2022)

First report of dry rot of potato caused by Fusarium proliferatum in India - Rahul Kumar Tiwari; Bishnu Maya Bashyal; V. Shanmugam; Milan Kumar Lal; Ravinder Kumar; Sanjeev Sharma; Kailash Chandra Naga; Kumar Nishant Chourasia; Rashmi Aggarwal (Journal of Plant Diseases and Protection, 2022)

DNA ligase IV mutations confer shorter lifespan and increased sensitivity to nutrient stress in Drosophila melanogaster - Rashmi Joshi; Surya Jyoti Banerjee; Jennifer Curtiss; Amanda K. Ashley (Journal of Applied Genetics, 2022)
The nonhomologous end-joining pathway is a primary DNA double-strand break repair pathway in eukaryotes. DNA ligase IV (Lig4) catalyzes the final step of DNA end ligation in this pathway. Partial loss of Lig4 in mammals causes Lig4 syndrome, while complete loss is embryonically lethal. DNA ligase 4 ( DNAlig4 ) null Drosophila melanogaster is viable, but sensitive to ionizing radiation during early development. We proposed to explore if DNAlig4 loss induced other long-term sensitivities and defects in D. melanogaster. We demonstrated that DNAlig4 mutant strains had decreased lifespan and lower resistance to nutrient deprivation, indicating Lig4 is required for maintaining health and longevity in D. melanogaster .

Efficient biodegradation of Congo red dye using fungal consortium incorporated with Penicillium oxalicum and Aspergillus tubingensis - Rashmi Thakor; Harsh Mistry; Krunal Tapodhan; Himanshu Bariya (Folia Microbiologica, 2022)

The interplay of plant hormonal pathways and geminiviral proteins: partners in disease development - Kanika Gupta; Rashmi Rishishwar; Indranil Dasgupta (Virus Genes, 2022)

Emergence of two distinct variants of SARS-CoV-2 and an explosive second wave of COVID-19: the experience of a tertiary care hospital in Pune, India - Shubham Shrivastava; Suhas T. Mhaske; Meera S. Modak; Rashmi G. Virkar; Shamburaje S. Pisal; Akhilesh Chandra Mishra; Vidya A. Arankalle (Archives of Virology, 2022)

Role of Inflammatory Cytokines in Pathophysiology of Psoriasis - Ravi Kant Sharma; Manu Rashmi Sharma; Aneet Mahendra; Sunil Kumar (Current Pharmacology Reports, 2022)

Global DNA methylation profile at LINE-1 repeats and promoter methylation of genes involved in DNA damage response and repair pathways in human peripheral blood mononuclear cells in response to γ-radiation - Rashmi Priya; Birajalaxmi Das (Molecular and Cellular Biochemistry, 2022)

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Madhukar S. Said; Rohini Udavant; Amit Kumar Sahu; AbuJunaid Khan; Rashmi Nayak; Syed G. Dastager; Pradeep Kumar; Jayant Gajbhiye (Natural Product Research, 2021)

Comprehensive overview of extracellular vesicle proteomics in meningioma: future strategy - Rashmi Rana; Swati Sharma; Nirmal Kumar Ganguly (Molecular Biology Reports, 2021)

Generation and Characterization of a Skeletal Muscle Cell-Based Model Carrying One Single Gne Allele: Implications in Actin Dynamics - Shamulailatpam Shreedarshanee Devi; Rashmi Yadav; Fluencephila Mashangva; Priyanka Chaudhary; Shweta Sharma; Ranjana Arya (Molecular Neurobiology, 2021)

A Novel L1 Linker Mutation in DES Resulted in Total Absence of Protein - Rashmi Santhoshkumar; Veeramani Preethish-Kumar; Kiran Polavarapu; Dinesh Reghunathan; Sima Chaudhari; Kapaettu Satyamoorthy; Seena Vengalil; Saraswati Nashi; Muhammed Faruq; Aditi Joshi; Nalini Atchayaram; Gayathri Narayanappa (Journal of Molecular Neuroscience, 2021)

Molecular and phenotypic analysis reveals cross infection of Bipolaris species in wheat and rice - Kartar Singh; Rashmi Aggarwal; Sapna Sharma; Malkhan Singh Gurjar; C. Manjunatha; Manoj Choudhary (Indian Phytopathology, 2021)

Sub-Surface Ocean Structure from Satellite Surface Observations in the North Indian Ocean - Anup Kumar Mandal; Aditya Chaudhary; Neeraj Agarwal; Rashmi Sharma (Marine Geodesy, 2021)

Salt and drought stress tolerance with increased biomass in transgenic Pelargonium graveolens through heterologous expression of ACC deaminase gene from Achromobacter xylosoxidans - Pooja Singh; Shiv Shanker Pandey; Basant Kumar Dubey; Rashmi Raj; Deepti Barnawal; Ashish Chandran; Laiq ur Rahman (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Correction to: Efonidipine Exerts Cerebroprotective Effect by Down‑regulation of TGF‑β/SMAD‑2‑Dependent Signaling Pathway in Diabetic Rats - Rashmi Rajput; Vishal Chavda; Snehal S. Patel; George E. Barreto; Ghulam Md Ashraf (Journal of Molecular Neuroscience, 2021)

A Dominant C150Y Mutation in FHL1 Induces Structural Alterations in LIM2 Domain Causing Protein Aggregation In Human and Drosophila Indirect Flight Muscles - Rashmi Santhoshkumar; Veeramani Preethish-Kumar; Kiran K. Mangalaparthi; Sruthi Unni; Balasundaram Padmanabhan; Keshava Prasad T. S.; Upendra Nongthomba; Nalini Atchayaram; Gayathri Narayanappa (Journal of Molecular Neuroscience, 2021)

Evidence of Coronavirus (CoV) Pathogenesis and Emerging Pathogen SARS-CoV-2 in the Nervous System: A Review on Neurological Impairments and Manifestations - Niraj Kumar Jha; Shreesh Ojha; Saurabh Kumar Jha; Harish Dureja; Sachin Kumar Singh; Shakti D. Shukla; Dinesh Kumar Chellappan; Gaurav Gupta; Shanu Bhardwaj; Neeraj Kumar; Madhan Jeyaraman; Rashmi Jain; et al. (Journal of Molecular Neuroscience, 2021)

A Nitronaphthalimide Probe for Fluorescence Imaging of Hypoxia in Cancer Cells - Rashmi Kumari; Vasumathy R; Dhanya Sunil; Raghumani Singh Ningthoujam; Badri Narain Pandey; Suresh D. Kulkarni; Thivaharan Varadavenkatesan; Ganesh Venkatachalam; Anil Kumar N. V (Journal of Fluorescence, 2021)
The bioreductive enzymes typically upregulated in hypoxic tumor cells can be targeted for developing diagnostic and drug delivery applications. In this study, a new fluorescent probe 4−(6−nitro−1,3−dioxo−1 H −benzo[ de ]isoquinolin−2(3 H )−yl)benzaldehyde (NIB) based on a nitronaphthalimide skeleton that could respond to nitroreductase (NTR) overexpressed in hypoxic tumors is designed and its application in imaging tumor hypoxia is demonstrated. The docking studies revealed favourable interactions of NIB with the binding pocket of NTR- Escherichia coli . NIB, which is synthesized through a simple and single step imidation of 4−nitro−1,8−naphthalic anhydride displayed excellent reducible capacity under hypoxic conditions as evidenced from cyclic voltammetry investigations. The fluorescence measurements confirmed the formation of identical products (NIB-red) during chemical as well as NTR−aided enzymatic reduction in the presence of NADH. The potential fluorescence imaging of hypoxia based on NTR-mediated reduction of NIB is confirmed using in-vitro cell culture experiments using human breast cancer (MCF−7) cells, which displayed a significant change in the fluorescence colour and intensity at low NIB concentration within a short incubation period in hypoxic conditions. Graphical abstract

Synthesis, molecular modelling studies of indolyl chalcone derivatives and their antimalarial activity evaluation - Jyoti; Rashmi Gaur; Yogesh Kumar; Harveer Singh Cheema; Deepak Singh Kapkoti; Mahendra P. Darokar; Feroz Khan; Rajendra Singh Bhakuni (Natural Product Research, 2021)

Carbon and polymer-based magnetic nanocomposites for oil-spill remediation—a comprehensive review - Ahsan Mehmood; Fahad Saleem Ahmed Khan; Nabisab Mujawar Mubarak; Shaukat Ali Mazari; Abdul Sattar Jatoi; Mohammad Khalid; Yie Hua Tan; Rama Rao Karri; Rashmi Walvekar; Ezzat Chan Abdullah; Sabzoi Nizamuddin (Environmental Science and Pollution Research, 2021)

Centella asiatica L. callus mediated biosynthesis of silver nanoparticles, optimization using central composite design, and study on their antioxidant activity - Venkatasubbaiah Rashmi; Hema Bommanamane Prabhushankar; Konasur Rajesh Sanjay (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Allelic variation in sugary1 gene affecting kernel sweetness among diverse-mutant and -wild-type maize inbreds - Rashmi Chhabra; Vignesh Muthusamy; Nisrita Gain; Ashvinkumar Katral; Nitish R. Prakash; Rajkumar U. Zunjare; Firoz Hossain (Molecular Genetics and Genomics, 2021)

Information extraction for prognostic stage prediction from breast cancer medical records using NLP and ML - Pratiksha R. Deshmukh; Rashmi Phalnikar (Medical & Biological Engineering & Computing, 2021)

Efonidipine Exerts Cerebroprotective Effect by Down-regulation of TGF-β/SMAD-2-Dependent Signaling Pathway in Diabetic Rats - Rashmi Rajput; Vishal Chavda; Snehal S. Patel; George E. Barreto; Ghulam Md Ashraf (Journal of Molecular Neuroscience, 2021)

Petrogenesis of the Late Archean Kanara Batholith of the Western Dharwar Craton: Evidence for mid-deep crustal recycling of the Archean felsic crust - Jayant K Padhi; Chandan K Boraiaha; Rashmi Chandan (Journal of Earth System Science, 2021)

Development of multinutrient-rich biofortified sweet corn hybrids through genomics-assisted selection of shrunken2, opaque2, lcyE and crtRB1 genes - Aanchal Baveja; Vignesh Muthusamy; Kusuma Kumari Panda; Rajkumar Uttamrao Zunjare; Abhijit Kumar Das; Rashmi Chhabra; Subhra Jyotshna Mishra; Brijesh Kumar Mehta; Supradip Saha; Firoz Hossain (Journal of Applied Genetics, 2021)

Effects of ambient air pollution on emergency room visits of children for acute respiratory symptoms in Delhi, India - Rashmi Yadav; Aditya Nagori; Aparna Mukherjee; Varinder Singh; Rakesh Lodha; Sushil Kumar Kabra; Geetika Yadav; Jitendra Kumar Saini; Kamal Kumar Singhal; Kana Ram Jat; Karan Madan; Mohan P. George; et al. (Environmental Science and Pollution Research, 2021)

Assessment of arsenic exposure and its mitigation intervention in severely exposed population of Buxar district of Bihar, India - Arun Kumar; Md. Samiur Rahman; Mohammad Ali; Ranjit Kumar; Pintoo Kumar Niraj; Vivek Akhouri; Sushil Kumar Singh; Dhruv Kumar; Tuhin Rashmi; Akhouri Bishwapriya; Gyanendra Bahadur Chand; Maiko Sakamoto; et al. (Toxicology and Environmental Health Sciences, 2021)

Artificial intelligence to deep learning: machine intelligence approach for drug discovery - Rohan Gupta; Devesh Srivastava; Mehar Sahu; Swati Tiwari; Rashmi K. Ambasta; Pravir Kumar (Molecular Diversity, 2021)

Evaluation of Spatio-Temporal Evapotranspiration Using Satellite-Based Approach and Lysimeter in the Agriculture Dominated Catchment - Utkarsh Kumar; Ankur Srivastava; Nikul Kumari; Rashmi; Bhabagrahi Sahoo; Chandranath Chatterjee; Narendra Singh Raghuwanshi (Journal of the Indian Society of Remote Sensing, 2021)

Assessment of arsenic exposure in the population of Sabalpur village of Saran District of Bihar with mitigation approach - Arun Kumar; Rishav Kumar; Md. Samiur Rahman; Mohammad Ali; Ranjit Kumar; Neha Nupur; Aman Gaurav; Vikram Raj; Gautam Anand; Pintoo Kumar Niraj; Nirmal Kumar; Abhinav Srivastava; et al. (Environmental Science and Pollution Research, 2021)

Structural-genetic insight and optimization of protease production from a novel strain of Aeromonas veronii CMF, a gut isolate of Chrysomya megacephala - Rashmi Bhattacherjee; Subhrangshu Mandal; Sandipan Banerjee; Kunal Kumar Saha; Jagannath Sarkar; Dhriti Banerjee; Narayan Chandra Mandal (Archives of Microbiology, 2021)

Reclassification of Facklamia ignava, Facklamia sourekii and Facklamia tabacinasalis as Falseniella ignava gen. nov., comb. nov., Hutsoniella sourekii gen. nov., comb. nov., and Ruoffia tabacinasalis gen. nov., comb. nov., and description of Ruoffia halotolerans sp. nov., isolated from hypersaline Inland Sea of Qatar - Rashmi Fotedar; Krithivasan Sankaranarayanan; Matthew E. Caldwell; Aisha Zeyara; Amina Al Malki; Ridhima Kaul; Hamad Al Shamari; Mohammad Ali; Masoud Al Marri; Paul A. Lawson (Antonie van Leeuwenhoek, 2021)

Phenetic analysis of some medicinal plants of Asteraceae of Tripura, North-east India - Rashmi Rani; B. K. Datta (Vegetos, 2021)

Iron homeostasis regulates maturation of tomato (climacteric) and capsicum (non-climacteric) fruits - Rashmi Shakya; Neha Singh; Satish C. Bhatla (Journal of Plant Biochemistry and Biotechnology, 2021)

Development and validation of multiplex-PCR assay to simultaneously detect favourable alleles of shrunken2, opaque2, crtRB1 and lcyE genes in marker-assisted selection for maize biofortification - Aanchal Baveja; Rashmi Chhabra; Kusuma K. Panda; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Journal of Plant Biochemistry and Biotechnology, 2021)

Enhanced expression of Arabidopsis rubisco small subunit gene promoter regulated Cry1Ac gene in chickpea conferred complete resistance to Helicoverpa armigera - Nayana Hazarika; Sumita Acharjee; Rashmi R. Boruah; Kiran Babar; Srinivas Parimi; Bharat Char; Joel Armstrong; Andy Moore; Thomas J. V. Higgins; Bidyut Kumar Sarmah (Journal of Plant Biochemistry and Biotechnology, 2021)

Investigation of rip current processes along Visakhapatnam beaches, east coast of India: A study based on GNSS drifters and dye experiments - Surisetty V V Arun Kumar; B Sivaiah; Ch Venkateswarlu; B Gireesh; T Sridevi; K Venkateswara Rao; K V S R Prasad; Rashmi Sharma (Journal of Earth System Science, 2021)

Fusarium head blight of wheat in India‐variability in pathogens associated and sources of resistance: an overview - Mahender Singh Saharan; H. M. Akshay Kumar; Malkhan Singh Gurjar; Rashmi Aggarwal (Indian Phytopathology, 2021)

Rice SWEET proteins: the key targets by the bacterial blight pathogen, Xanthomonas oryzae pv. oryzae to ensure nutrition in the rice apoplast during infection - Kalyan K. Mondal; E. R. Rashmi; Thungri Ghoshal (Indian Phytopathology, 2021)

Antibiotic Resistance Crisis: An Update on Antagonistic Interactions between Probiotics and Methicillin-Resistant Staphylococcus aureus (MRSA) - Basavaprabhu H. Nataraj; Rashmi H. Mallappa (Current Microbiology, 2021)

Short-Term Effect of Resource Conservation Practices on Soil Loss, Productivity and Energy Budgeting of Soybean–Mustard System in Table Lands of Chambal Ravine - I. Rashmi; Shakir Ali; B. L. Mina; Kuldeep Kumar; Ashok Kumar; R. K. Singh (Agricultural Research, 2021)

Association of an isolate of papaya leaf curl virus and papaya leaf curl betasatellite with leaf curl disease of radish in India - Susheel Kumar; Rashmi Raj; Lalit Agrawal; Taruna Gupta; Shri Krishna Raj; Meraj Jaidi; Ashish Srivastava (Journal of Plant Pathology, 2021)

Characterization of Antibiotic Resistance and Virulence Traits Present in Clinical Methicillin-Resistant Staphylococcus aureus Isolates - Basavaprabhu Haranahalli Nataraj; Chette Ramesh; Rashmi Hogarehalli Mallappa (Current Microbiology, 2021)

Effect of PDGF-B Gene-Activated Acellular Matrix and Mesenchymal Stem Cell Transplantation on Full Thickness Skin Burn Wound in Rat Model - Tamilmahan Paramasivam; Swapan Kumar Maiti; Sangeetha Palakkara; Rashmi; Divya Mohan; H. V. Manjunthaachar; K. Karthik; Naveen Kumar (Tissue Engineering and Regenerative Medicine, 2021)

Molecular characterization of elite maize (Zea mays L.) inbreds using markers associated with iron and zinc transporter genes - Devender Sharma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Genetic Resources and Crop Evolution, 2021)

Magnetic nanocomposites for sustainable water purification—a comprehensive review - Ahsan Mehmood; Fahad Saleem Ahmed Khan; Nabisab Mujawar Mubarak; Yie Hua Tan; Rama Rao Karri; Mohammad Khalid; Rashmi Walvekar; Ezzat Chan Abdullah; Sabzoi Nizamuddin; Shaukat Ali Mazari (Environmental Science and Pollution Research, 2021)

Assessment of trace metal contamination in the core sediment of Ramsar wetland (Kabar Tal), Begusarai, Bihar (India) - Himanshu Kaushik; Rashmi Ranjan; Rakhshan Ahmad; Alok Kumar; Prashant; Nitish Kumar; Rajesh Kumar Ranjan (Environmental Science and Pollution Research, 2021)

Expression of barley oxalate oxidase confers resistance against Sclerotinia sclerotiorum in transgenic Brassica juncea cv Varuna - Rashmi Verma; Jagreet Kaur (Transgenic Research, 2021)

Conservation Tillage, Residue Management, and Crop Rotation Effects on Soil Major and Micro-nutrients in Semi-arid Vertisols of India - Somasundaram Jayaraman; N. K. Sinha; M. Mohanty; K. M. Hati; R. S. Chaudhary; A. K. Shukla; A. O. Shirale; S. Neenu; A. K. Naorem; I. Rashmi; A. K. Biswas; A. K. Patra; et al. (Journal of Soil Science and Plant Nutrition, 2021)

Tilletia indica: biology, variability, detection, genomics and future perspective - Malkhan Singh Gurjar; Haritha Mohan M; Jagmohan Singh; Mahender Singh Saharan; Rashmi Aggarwal (Indian Phytopathology, 2021)

Improved methodology for the isolation of false smut pathogen Ustilaginoidea virens of rice - B. M. Bashyal; Pooja Parmar; Najam Waris Zaidi; Sunil Kumar Sunani; G. Prakash; Rashmi Aggarwal (Indian Phytopathology, 2021)

Waste Cooking (Palm) Oil as an Economical Source of Biodiesel Production for Alternative Green Fuel and Efficient Lubricant - Suprakash Samanta; Rashmi R. Sahoo (BioEnergy Research, 2021)

Toxoplasma gondii in Chickens (Gallus domesticus) from North India - Rashmi Thakur; Rajnish Sharma; Rabinder Singh Aulakh; Balbir B. Singh (Acta Parasitologica, 2021)

Enhancing the safety of frontline healthcare workers during coronavirus disease: a novel real-time remote audiovisual aided doffing approach - Manju Dhandapani; Sukhpal Kaur; Karobi Das; Rashmi Ranjan Guru; Manisha Biswal; Pranay Mahajan; Vipin Koushal; Goverdhan D. Puri (Infectious Diseases, 2021)

Expatiating the molecular approaches of HMGB1 in diabetes mellitus: Highlighting signalling pathways via RAGE and TLRs - Tapan Behl; Eshita Sharma; Aayush Sehgal; Ishnoor Kaur; Arun Kumar; Rashmi Arora; Giridhari Pal; Munish Kakkar; Ravinder Kumar; Simona Bungau (Molecular Biology Reports, 2021)

Role of ACE2 receptor and the landscape of treatment options from convalescent plasma therapy to the drug repurposing in COVID-19 - Pravindra Kumar; Ashok Kumar Sah; Greesham Tripathi; Anjali Kashyap; Avantika Tripathi; Rashmi Rao; Prabhu C. Mishra; Koustav Mallick; Amjad Husain; Manoj Kumar Kashyap (Molecular and Cellular Biochemistry, 2021)

Euglena tuba extract provides protection against lipopolysaccharide-induced inflammatory response and oxidative stress in mice - Rashmi Kesherwani; Raushan Kumar; Ujla Minhas; Syed Ibrahim Rizvi (Biologia, 2021)

Low expression of carotenoids cleavage dioxygenase 1 (ccd1) gene improves the retention of provitamin-A in maize grains during storage - Suman Dutta; Vignesh Muthusamy; Rashmi Chhabra; Aanchal Baveja; Rajkumar U. Zunjare; Tapan K. Mondal; Devendra K. Yadava; Firoz Hossain (Molecular Genetics and Genomics, 2021)

Biogenically proficient synthesis and characterization of silver nanoparticles employing marine procured fungi Aspergillus brunneoviolaceus along with their antibacterial and antioxidative potency - Harsh Mistry; Rashmi Thakor; Chirag Patil; Jitendra Trivedi; Himanshu Bariya (Biotechnology Letters, 2021)

Expression of FOXP3 and GATA3 Transcription Factors Among Bronchial Asthmatics in Northern Population - Rashmi Pandey; Ved Prakash (Indian Journal of Clinical Biochemistry, 2021)

A comprehensive overview of proteomics approach for COVID 19: new perspectives in target therapy strategies - Rashmi Rana; Vaishnavi Rathi; Nirmal Kumar Ganguly (Journal of Proteins and Proteomics, 2020)

Field, petrographic and geochemical characteristics of Sullya alkaline complex in the Cauvery Shear Zone (CSZ), southern India: Implications for petrogenesis - Chandan Kumar Boraiaha; Kumar Batuk Joshi; Andrew C Kerr; Jayant Kumar Padhi; Sarbartha Shankar Mishra; Rashmi Chandan (Journal of Earth System Science, 2020)

Revisiting CRISPR/Cas-mediated crop improvement: Special focus on nutrition - Tanushri Kaul; Sonia Khan Sony; Rachana Verma; Khaled Fathy Abdel Motelb; Arul T Prakash; Murugesh Eswaran; Jyotsna Bharti; Mamta Nehra; Rashmi Kaul (Journal of Biosciences, 2020)

Comparative genome analysis of Tilletia indica inciting Karnal bunt of wheat reveals high genomic variation - Malkhan Singh Gurjar; Rashmi Aggarwal; Prachi Jain; Shweta Aggarwal; Sangeeta Gupta; Mahender Singh Saharan (Indian Phytopathology, 2020)

Magnetic nanoparticles incorporation into different substrates for dyes and heavy metals removal—A Review - Fahad Saleem Ahmed Khan; Nabisab Mujawar Mubarak; Yie Hua Tan; Rama Rao Karri; Mohammad Khalid; Rashmi Walvekar; Ezzat Chan Abdullah; Shaukat Ali Mazari; Sabzoi Nizamuddin (Environmental Science and Pollution Research, 2020)

Assessment of phytoremedial potential of invasive weeds Acalypha indica and Amaranthus viridis - Dharitri B. Ramanlal; Rita N. Kumar; J. I. Nirmal Kumar; Rashmi Thakkar (Environmental Sustainability, 2020)

A high-density SNP-based linkage map using genotyping-by-sequencing and its utilization for improved genome assembly of chickpea (Cicer arietinum L.) - Rashmi Gaur; Subodh Verma; Seema Pradhan; Heena Ambreen; Sabhyata Bhatia (Functional & Integrative Genomics, 2020)

Correction to: Statistical, time series and fractal analysis of full stretch of river Yamuna (India) for water quality management - Rashmi Bhardwaj; Kulwinder Singh Parmar (Environmental Science and Pollution Research, 2020)

Insulin growth factor-1 pathway in cervical carcinoma cancer stem cells - Shifa Javed; Shalmoli Bhattacharyya; Rashmi Bagga; Radhika Srinivasan (Molecular and Cellular Biochemistry, 2020)

Indigenous Preparations of Bryonia laciniosa, Quercus infectoria, Putranjiva roxburghii and Mesua ferrea Induce Developmental Toxicity in C. elegans - Pragya Rai; Sharika Rajasekharan; Abhijit Ganguli; Krishnaswamy Balamurugan; Sarala Balachandran; Rashmi Sharma; Rakesh Gupta; Sutapa Bandyopadhyay Neogi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Adsorption of Cu(II) and Ni(II) ions from wastewater onto bentonite and bentonite/GO composite - Yii Shiuan Chang; Pek Ing Au; Nabisab Mujawar Mubarak; Mohammad Khalid; Priyanka Jagadish; Rashmi Walvekar; Ezzat Chan Abdullah (Environmental Science and Pollution Research, 2020)

Phosphorus Sorption and Desorption in Soils Amended with Subabul Biochar - I. Rashmi; Pramod Jha; A. K. Biswas (Agricultural Research, 2020)

Thermodynamic Response of a High-Resolution Tropical Indian Ocean Model to TOGA COARE Bulk Air–Sea Flux Parameterization: Case Study for the Bay of Bengal (BoB) - Subrat Kumar Mallick; Neeraj Agarwal; Rashmi Sharma; K. V. S. R. Prasad; S. S. V. S. Ramakrishna (Pure and Applied Geophysics, 2020)

Degradation and detoxification of phenanthrene by actinobacterium Zhihengliuella sp. ISTPL4 - Arti Mishra; Rashmi Rathour; Rashmi Singh; Taruna Kumari; Indu Shekhar Thakur (Environmental Science and Pollution Research, 2020)

Crop yield prediction using aggregated rainfall-based modular artificial neural networks and support vector regression - Ekaansh Khosla; Ramesh Dharavath; Rashmi Priya (Environment, Development and Sustainability, 2020)

Investigation into the miRNA/5' isomiRNAs function and drought-mediated miRNA processing in rice - Sonia Balyan; Shaji V. Joseph; Rashmi Jain; Roseeta Devi Mutum; Saurabh Raghuvanshi (Functional & Integrative Genomics, 2020)

Magnetic nanoadsorbents’ potential route for heavy metals removal—a review - Fahad Saleem Ahmed Khan; Nabisab Mujawar Mubarak; Mohammad Khalid; Rashmi Walvekar; Ezzat Chan Abdullah; Shaukat A. Mazari; Sabzoi Nizamuddin; Rama Rao Karri (Environmental Science and Pollution Research, 2020)

Toward sustainable and eco-friendly production of coffee: abatement of wastewater and evaluation of its potential valorization - Bratin Sengupta; Rashmi Priyadarshinee; Abhishek Roy; Avishek Banerjee; Alok Malaviya; Subhajit Singha; Tamal Mandal; Anuj Kumar (Clean Technologies and Environmental Policy, 2020)

Stigma receptivity with pollen in sunflower accompanies novel histochemical and biochemical changes in both male and female reproductive structures - Rashmi Shakya (Vegetos, 2020)

Neuroprotective effect of Reinwardtia indica against scopolamine induced memory-impairment in rat by attenuating oxidative stress - Prabhat Upadhyay; Rashmi Shukla; Kavindra Nath Tiwari; G. P. Dubey; Sunil Kumar Mishra (Metabolic Brain Disease, 2020)

Characterization of Mimban maize landrace from North-Eastern Himalayan region using microsatellite markers - Nenavath Krishna Kumar Rathod; Jyoti Kumari; Firoz Hossain; Rashmi Chhabra; Somnath Roy; Ganjalagatta Dasaiah Harish; Rakesh Bhardwaj; Raveendra N. Gadag; Anup Kumar Misra (Journal of Plant Biochemistry and Biotechnology, 2020)

Arbuscular Mycorrhizal Fungi Status of Mango (Mangifera indica) Cultivars Grown in Typic Quartzipsamments Soil - M. Govindan; P. P. Rajeshkumar; C. K. Yamini Varma; M. Mohamed Anees; C. R. Rashmi; Asha B. Nair (Agricultural Research, 2020)

Trace elemental signatures and mineral chemistry of clays associated with the alteration halos of the Paleoproterozoic U mineralization in Bijawars of the Sonrai Basin, Central India - Surendra Kumar Jha; Rashmi Sharma; Jaya Prakash Shrivastava (Acta Geochimica, 2020)

Characterisation of recombinant thermostable manganese-superoxide dismutase (NeMnSOD) from Nerium oleander - Rashmi Gangwar; Poonam Kumari; Apurva Chatrath; Ramasare Prasad (Molecular Biology Reports, 2020)

A comprehensive analysis of e-waste legislation worldwide - Rashmi Anoop Patil; Seeram Ramakrishna (Environmental Science and Pollution Research, 2020)

Adsorption of heavy metal from industrial wastewater onto low-cost Malaysian kaolin clay–based adsorbent - Jia-Boon Chai; Pek-Ing Au; Nabisab Mujawar Mubarak; Mohammad Khalid; Wendy Pei-Qin Ng; Priyanka Jagadish; Rashmi Walvekar; Ezzat Chan Abdullah (Environmental Science and Pollution Research, 2020)

Experimental investigation on sludge dewatering using granulated blast furnace slag as skeleton material - Rashmi Hosurdoddi Ramachandra; Chella Purushothaman Devatha (Environmental Science and Pollution Research, 2020)

Earthquake source dynamics and kinematics of the Eastern Indian Shield and adjoining regions - Rashmi Singh; Prosanta Kumar Khan; A. P. Singh (Acta Geophysica, 2020)

Tree diversity and carbon stock in a subtropical broadleaved forest are greater than a subtropical pine forest occurring in similar elevation of Meghalaya, north-eastern India - Rashmi R. Gogoi; D. Adhikari; K. Upadhaya; S. K. Barik (Tropical Ecology, 2020)

Genotypes with enhanced expressions of acquired tolerance mechanisms showed improved growth under stress - Shashibhushan Nittur Basavaraju; Ramachandra Yerappa Lakshmikanth; Rashmi Kumaraswamy; Udayakumar Makarla (Plant Physiology Reports, 2020)

Phomopsis tersa as Inhibitor of Quorum Sensing System and Biofilm Forming Ability of Pseudomonas aeruginosa - Himani Meena; Rashmi Mishra; Sampathkumar Ranganathan; V. Venkateswara Sarma; Dinakara Rao Ampasala; Vipin Chandra Kalia; Jung-Kul Lee; Busi Siddhardha (Indian Journal of Microbiology, 2020)

Biocontrol activities of rhizobacteria associated with apple, apricot and kiwi rhizosphere against bacterial canker caused by Clavibacter michiganensis - Swati Gautam; Rashmi Sharma; Anjali Chauhan; C. K. Shirkot; Rajesh Kaushal (Indian Phytopathology, 2020)

A Simplified Assimilation Scheme for a Coastal Wave Model Using Concepts of Particle Filter - Suchandra Aich Bhowmick; Smitha Ratheesh; Rashmi Sharma; Sujit Basu; Raj Kumar (Pure and Applied Geophysics, 2020)

Soil and nutrients losses under different crop covers in vertisols of Central India - R. K. Singh; R. S. Chaudhary; J. Somasundaram; N. K. Sinha; M. Mohanty; K. M. Hati; I. Rashmi; A. K. Patra; S. K. Chaudhari; Rattan Lal (Journal of Soils and Sediments, 2020)

Identification of rice seed infection routes of Fusarium fujikuroi inciting bakanae disease of rice - Sunil Kumar Sunani; Bishnu Maya Bashyal; Bhupendra Singh Kharayat; Ganesan Prakash; S. Gopala Krishnan; Rashmi Aggarwal (Journal of Plant Pathology, 2020)

Biodegradation of pesticides using density-based clustering on cotton crop affected by Xanthomonas malvacearum - Rashmi Priya; Dharavath Ramesh; Ekaansh Khosla (Environment, Development and Sustainability, 2020)

Comparative study of different glycating agents on human plasma and vascular cells - Rashmi S. Tupe; Nilima Bangar; Arundhati Diwan; Dhanashri Changale; Shivani Choudhary; Shubhangi Chaware (Molecular Biology Reports, 2020)

Mapping of Coda-Wave Attenuation and Its Frequency Dependency Over Eastern Indian Shield - Rashmi Singh; Subham Sharma; Supriyo Mitra; Prosanta Kumar Khan (Pure and Applied Geophysics, 2019)

Understanding the secondary metabolite production of Gibberella fujikuroi species complex in genomic era - Bishnu Maya Bashyal; Jagdish Yadav; Ashish Kumar Gupta; Rashmi Aggarwal (Indian Phytopathology, 2019)

Fusarium graminearum microRNA-like RNAs and their interactions with wheat genome: a much-needed study - Lalit L. Kharbikar; Arti S. Shanware; M. S. Saharan; Shweta K. Nandanwar; P. N. Sivalingam; Malkhan S. Gurjar; Rashmi Aggarwal (Indian Phytopathology, 2019)

Magnetic palm kernel biochar potential route for phenol removal from wastewater - Muhammad Nazmi Hairuddin; Nabisab Mujawar Mubarak; Mohammad Khalid; Ezzat Chan Abdullah; Rashmi Walvekar; Rama Rao Karri (Environmental Science and Pollution Research, 2019)

Colonization of enzymatic bacterial flora in biofloc grown shrimp Penaeus vannamei and evaluation of their beneficial effect - Akshaya Panigrahi; Palanichamy Esakkiraj; Sundaresan Jayashree; Chakrapani Saranya; Rashmi Ranjan Das; Mani Sundaram (Aquaculture International, 2019)

Impact of Satellite-Derived Diffuse Attenuation Coefficient on Upper Ocean Simulation Using High-Resolution Numerical Ocean Model: Case Study for the Bay of Bengal - Subrat Kumar Mallick; Neeraj Agarwal; Rashmi Sharma; K.V.S.R. Prasad; Robert A. Weller (Marine Geodesy, 2019)

Cross-priming accentuates key biochemical and molecular indicators of defense and improves cold tolerance in chickpea (Cicer arietinum L.) - Rashmi Saini; Arindam Adhikary; Harsh Nayyar; Sanjeev Kumar (Acta Physiologiae Plantarum, 2019)

Coastal currents from Jason-2 and SARAL/AltiKa in the Indian region - Aditya Chaudhary; Neeraj Agarwal; Rashmi Sharma; B. K. Jena; Raj Kumar (International Journal of Remote Sensing, 2019)

Substitution of dietary protein sources in relation to colorectal cancer risk in the NIH-AARP cohort study - Linda M. Liao; Erikka Loftfield; Arash Etemadi; Barry I. Graubard; Rashmi Sinha (Cancer Causes & Control, 2019)

Purification and Characterization of α-Mannosidase from Moss Hyophilla nymaniana (Fleish.) Menzel - Rashmi Mishra; Ramesh Chandra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Assessing the Safety and Efficacy of Lactobacillus plantarum MTCC 5690 and Lactobacillus fermentum MTCC 5689 in Colitis Mouse Model - Diwas Pradhan; Rajbir Singh; Ashish Tyagi; Rashmi H.M.; Virender K. Batish; Sunita Grover (Probiotics and Antimicrobial Proteins, 2019)

Field performance of bacterial inoculants to alleviate water stress effects in wheat (Triticum aestivum L.) - Dinesh Chandra; Rashmi Srivastava; Vadakattu V. S. R. Gupta; Christopher M. M. Franco; Nishat Paasricha; Shabnam K. Saifi; Narendra Tuteja; Anil Kumar Sharma (Plant and Soil, 2019)

Intranasal curcumin protects against LPS-induced airway remodeling by modulating toll-like receptor-4 (TLR-4) and matrixmetalloproteinase-9 (MMP-9) expression via affecting MAP kinases in mouse model - Asha Kumari; D. K. Singh; D. Dash; Rashmi Singh (Inflammopharmacology, 2019)

Response of tropical cyclone Phailin (2013) in the Bay of Bengal to climate perturbations - Rashmi Mittal; Mukul Tewari; Chandrasekar Radhakrishnan; Pallav Ray; Tarkeshwar Singh; Alexander K. Nickerson (Climate Dynamics, 2019)

Requirements for a Coastal Hazards Observing System - Jérôme Benveniste; Anny Cazenave; Stefano Vignudelli; Luciana Fenoglio-Marc; Rashmi Shah; Rafael Almar; Ole Andersen; Florence Birol; Pascal Bonnefond; Jérôme Bouffard; Francisco Calafat; Estel Cardellach; et al. (Frontiers in Marine Science, 2019)

The incretin enhancer, sitagliptin, exacerbates expression of hepatic inflammatory markers in rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Laura A. Forney; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2019)

Development of PCR and loop mediated isothermal amplification assay for the detection of bakanae pathogen Fusarium fujikuroi - Sunil Kumar Sunani; Bishnu Maya Bashyal; Kirti Rawat; C. Manjunatha; Sapna Sharma; G. Prakash; S. Gopala Krishnan; A. K. Singh; Rashmi Aggarwal (European Journal of Plant Pathology, 2019)

Temporal expression of genes involved in folate metabolism and transport during placental development, preeclampsia and neural tube defects - Palani Selvam Mohanraj; Beenish Rahat; Aatish Mahajan; Rashmi Bagga; Jyotdeep Kaur (Molecular Biology Reports, 2019)

Groundwater vulnerability assessment using DRASTIC model: a comparative analysis of conventional, AHP, Fuzzy logic and Frequency ratio method - Smitarani Lad; Rashmi Ayachit; Ajaykumar Kadam; Bhavana Umrikar (Modeling Earth Systems and Environment, 2019)

Role of ocean heat content in boosting post-monsoon tropical storms over Bay of Bengal during La-Niña events - Suchandra Aich Bhowmick; N. Agarwal; M. M. Ali; C. M. Kishtawal; Rashmi Sharma (Climate Dynamics, 2019)

Biases in the Tropical Indian Ocean subsurface temperature variability in a coupled model - Rashmi Kakatkar; C. Gnanaseelan; Jasti S. Chowdary; J. S. Deepa; Anant Parekh (Climate Dynamics, 2019)

The Tropical Indian Ocean decadal sea level response to the Pacific Decadal Oscillation forcing - J. S. Deepa; C. Gnanaseelan; Sandeep Mohapatra; J. S. Chowdary; A. Karmakar; Rashmi Kakatkar; Anant Parekh (Climate Dynamics, 2019)

Heavy Metals in Indigenous Preparations Used for Sex Selection During Pregnancy in India - Abhijit Ganguli; Pragya Rai; Sarala Balachandran; Rakesh Gupta; Rashmi Sharma; Sutapa Bandyopadhyay Neogi (Biological Trace Element Research, 2019)

Suppressors of RNA silencing encoded by geminiviruses and associated DNA satellites - Rashmi Rishishwar; Indranil Dasgupta (VirusDisease, 2019)

Protein kinases orchestrate cell cycle regulators in differentiating BeWo choriocarcinoma cells - M. Naveen Kumar; R. L. Babu; Rajeshwari H. Patil; K. M. Kiran Kumar; Shubha M. Hegde; Rashmi Nagesh; K. Kavya; Govindarajan T. Ramesh; S. Chidananda Sharma; C. Srinivas (Molecular and Cellular Biochemistry, 2019)

Evaluation of the Urban Background Model (UBM) and AERMOD for Mumbai City - Awkash Kumar; Jørgen Brandt; Matthias Ketzel; Rashmi S. Patil; Anil Kumar Dikshit; Ole Hertel (Environmental Modeling & Assessment, 2019)

Linear Stability of Horizontal Throughflow in a Brinkman Porous Medium with Viscous Dissipation and Soret Effect - Rashmi Dubey; P. V. S. N. Murthy (Transport in Porous Media, 2019)

Understanding the Mechanism of Salt Tolerance in Pandanus odorifer L. - Deo Rashmi; Altafhusain Nadaf (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

The effects of PPR on the reproductive health of Black Bengal goats and the possible role played by oxidative stress - Pankaj Kumar; Amitava Dey; Abhay Kumar; Pradeep Kumar Ray; Poolangulam Chinnakkan Chandran; Rashmi Rekha Kumari; Manish Kumar (Tropical Animal Health and Production, 2018)

Soil Testing Indices for Phosphorus Leaching in Selected Vertisol and Inceptisol of India - I. Rashmi; A. K. Biswas; V. R. R. Parama; M. Athifa; Lalita Ramteke (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Determination of critical low light limit and adaptive physiological and biochemical traits regulating growth and yield of mustard (Brassica juncea Coss.) - Badre Alam; Rashmi Singh; Mayank Chaturvedi; Ram Newaj; O. P. Chaturvedi (Physiology and Molecular Biology of Plants, 2018)

Correction to: Interdependence of laforin and malin proteins for their stability and functions could underlie the molecular basis of locus heterogeneity in Lafora disease - Shuchi Mittal; Mamta Upadhyay; Pankaj Kumar Singh; Rashmi Parihar; Subramaniam Ganesh (Journal of Biosciences, 2018)

Functional expression of MAP kinase TiHOG1 gene in Tilletia indica inciting Karnal bunt of wheat - Malkhan Singh Gurjar; Abhimanyu Jogawat; Sapna Sharma; Rashmi Aggarwal (Indian Phytopathology, 2018)

Influence of IAA and ACC Deaminase Producing Fluorescent Pseudomonads in Alleviating Drought Stress in Wheat (Triticum aestivum) - Dinesh Chandra; Rashmi Srivastava; A. K. Sharma (Agricultural Research, 2018)

Endorsing cellular competitiveness in aberrant epithelium of oral submucous fibrosis progression: neighbourhood analysis of immunohistochemical attributes - Anji Anura; Anees Kazi; Mousumi Pal; Ranjan Rashmi Paul; Sanghamitra Sengupta; Jyotirmoy Chatterjee (Histochemistry and Cell Biology, 2018)

Carbon and nitrogen mineralization in Vertisol as mediated by type and placement method of residue - R L Jat; Pramod Jha; M L Dotaniya; B L Lakaria; I Rashmi; B P Meena; A O Shirale; A L Meena (Environmental Monitoring and Assessment, 2018)

Lafora disease: from genotype to phenotype - Rashmi Parihar; Anupama Rai; Subramaniam Ganesh (Journal of Genetics, 2018)

PknG supports mycobacterial adaptation in acidic environment - Ruchi Paroha; Rashmi Chourasia; Rajesh Mondal; Shivendra K. Chaurasiya (Molecular and Cellular Biochemistry, 2018)

Geology and geochemistry of metabasalts of Shimoga schist belt, Dharwar Craton: implications for the late Archean basin development - Chandan-Kumar Boraiaha; Annappa Ganpatrao Ugarkar; Andrew C. Kerr; Rashmi Chandan; Trivikram Manuvachari; Shivaprasad Rajanna (Arabian Journal of Geosciences, 2018)

Identification of resistance sources and expression level of defense-related genes in wheat against Bipolaris sorokiniana - Malkhan Singh Gurjar; Nitish Rattan Bhardwaj; Shekhar Jain; Sapna Sharma; Sangeeta Gupta; Rashmi Aggarwal (Indian Phytopathology, 2018)

Indian summer monsoon rainfall variability during 2014 and 2015 and associated Indo-Pacific upper ocean temperature patterns - Rashmi Kakatkar; C. Gnanaseelan; J. S. Chowdary; Anant Parekh; J. S. Deepa (Theoretical and Applied Climatology, 2018)

Assessing biodegradation of furfuryl alcohol using Pseudomonas putida MTCC 1194 and Pseudomonas aeruginosa MTCC 1034 and its kinetics - Rakesh Kumar; Divya Rashmi (World Journal of Microbiology and Biotechnology, 2018)

Peptides as drug delivery vehicles across biological barriers - Debadyuti Ghosh; Xiujuan Peng; Jasmim Leal; Rashmi P. Mohanty (Journal of Pharmaceutical Investigation, 2018)

Sequence analysis of six full-length bean yellow mosaic virus genomes reveals phylogenetic diversity in India strains, suggesting subdivision of phylogenetic group-IV - Charanjeet Kaur; Rashmi Raj; Ashish Srivastava; Susheel Kumar; Shri Krishna Raj (Archives of Virology, 2018)

In Situ Salification in Polar Solvents: a Paradigm for Enabling Drug Delivery of Weakly Ionic Drugs as Amorphous Solid Dispersion - Rashmi Nair; Ioorika Lamare; Nirbhay Kumar Tiwari; Punna Rao Ravi; Raviraj Pillai (AAPS PharmSciTech, 2018)

Plant growth promoting activities of rhizobacteria isolated from Podophyllum hexandrum growing in North-West regions of the Himalaya - Rashmi Sharma; Parul Sharma; Anjali Chauhan; Abhishek Walia; C. K. Shirkot (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Genetic Diversity Among Indigenous Germplasm of Brassica juncea (L.) Czern and Coss, Using Agro-Morphological and Phenological Traits - Rashmi Yadav; Ranbir Singh; Sandeep Kumar; T. V. Prasad; Rakesh Bharadwaj; Vikender Kaur; Anitha Petapadi; Ashok Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Bedaquiline: Fallible Hope Against Drug Resistant Tuberculosis - Priya Singh; Rashmi Kumari; Rup Lal (Indian Journal of Microbiology, 2017)

Economic and sustainable management of wastes from rice industry: combating the potential threats - Anuj Kumar; Abhishek Roy; Rashmi Priyadarshinee; Bratin Sengupta; Alok Malaviya; Dalia Dasguptamandal; Tamal Mandal (Environmental Science and Pollution Research, 2017)

Development and validation of multiplex-PCR assay for simultaneous detection of rare alleles of crtRB1 and lcyE governing higher accumulation of provitamin A in maize - Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Firoz Hossain; Vignesh Muthusamy; Aanchal Baveja; Hari Shanker Gupta (Journal of Plant Biochemistry and Biotechnology, 2017)

Ten gigahertz microwave radiation impairs spatial memory, enzymes activity, and histopathology of developing mice brain - Archana Sharma; Kavindra Kumar Kesari; Virender Kumar Saxena; Rashmi Sisodia (Molecular and Cellular Biochemistry, 2017)

Development and validation of loop mediated isothermal amplification based detection assay for Puccinia striiformis f. sp. tritici causing stripe rust of wheat - Rashmi Aggarwal; S. Sharma; C. Manjunatha; S. Gupta; V. K. Singh (Australasian Plant Pathology, 2017)

Properties and functional impact of termite sheetings - Ajay Harit; Rashmi Shanbhag; Ekta Chaudhary; Sougueh Cheik; Pascal Jouquet (Biology and Fertility of Soils, 2017)

Microbial taxonomy in the era of OMICS: application of DNA sequences, computational tools and techniques - Nitish Kumar Mahato; Vipin Gupta; Priya Singh; Rashmi Kumari; Helianthous Verma; Charu Tripathi; Pooja Rani; Anukriti Sharma; Nirjara Singhvi; Utkarsh Sood; Princy Hira; Puneet Kohli; et al. (Antonie van Leeuwenhoek, 2017)

Biology of B. sorokiniana (syn. Cochliobolus sativus) in genomics era - Pushpendra K. Gupta; Neeraj K. Vasistha; Rashmi Aggarwal; Arun K. Joshi (Journal of Plant Biochemistry and Biotechnology, 2017)

Differential expression of AP-1 transcription factors in human prostate LNCaP and PC-3 cells: role of Fra-1 in transition to CRPC status - K. Kavya; M. Naveen Kumar; Rajeshwari H. Patil; Shubha M. Hegde; K. M. Kiran Kumar; Rashmi Nagesh; R. L. Babu; Govindarajan T. Ramesh; S. Chidananda Sharma (Molecular and Cellular Biochemistry, 2017)

Synthesis of Naked-eye Detectable Fluorescent 2H-chromen-2-One 2, 6-Dicyanoanilines: Effect of Substituents and pH on Its Luminous Behavior - Rashmi C. Kulkarni; S. Samundeeswari; Farzanabi Shaikh; Nirmala S. Naik; Jyoti M. Madar; Lokesh A. Shastri; Vinay A. Sunagar (Journal of Fluorescence, 2017)

Biodegradation of pulp and paper mill effluent by co-culturing ascomycetous fungi in repeated batch process - Deepika Rajwar; Rashmi Paliwal; J. P. N. Rai (Environmental Monitoring and Assessment, 2017)

Application of AERMOD for short-term air quality prediction with forecasted meteorology using WRF model - Awkash Kumar; Rashmi S. Patil; Anil Kumar Dikshit; Rakesh Kumar (Clean Technologies and Environmental Policy, 2017)

ETS transcription factors Etv2 and Fli1b are required for tumor angiogenesis - Kristina Baltrunaite; Michael P. Craig; Sharina Palencia Desai; Praneet Chaturvedi; Ram Naresh Pandey; Rashmi S. Hegde; Saulius Sumanas (Angiogenesis, 2017)

Gene-based analysis of Puccinia species and development of PCR-based marker to detect Puccinia striiformis f. sp. tritici causing yellow rust of wheat - Rashmi Aggarwal; Sapna Sharma; Sangeeta Gupta; C. Manjunatha; Vaibhav K. Singh; Deepika Kulshreshtha (Journal of General Plant Pathology, 2017)

Validation of INSAT-3D temperature and moisture sounding retrievals using matched radiosonde measurements - Tarkeshwar Singh; Rashmi Mittal; Munn Vinayak Shukla (International Journal of Remote Sensing, 2017)

Curcumin inhibits lipopolysaccharide (LPS)-induced endotoxemia and airway inflammation through modulation of sequential release of inflammatory mediators (TNF-α and TGF-β1) in murine model - Asha Kumari; D. Dash; Rashmi Singh (Inflammopharmacology, 2017)

Evaluation of the ROS Inhibiting Activity and Mitochondrial Targeting of Phenolic Compounds in Fibroblast Cells Model System and Enhancement of Efficiency by Natural Deep Eutectic Solvent (NADES) Formulation - Erwann Durand; Jérôme Lecomte; Rashmi Upasani; Béatrice Chabi; Christelle Bayrasy; Bruno Baréa; Elodie Jublanc; Martyn J. Clarke; David J. Moore; Jonathan Crowther; Chantal Wrutniak-Cabello; Pierre Villeneuve (Pharmaceutical Research, 2017)

Rhizopalmoxylon nypoides – a new palm root from the Deccan Intertrappean beds of Sagar, Madhya Pradesh, India - P K Kathal; Rashmi Srivastava; R C Mehrotra; P O Alexander (Journal of Earth System Science, 2017)

Blyxa mangalensis, a new species of Hydrocharitaceae from India - K. Rashmi; G. Krishnakumar; Donald H. Les (Kew Bulletin, 2017)

An exploratory study on occurrence and impact of climate change on agriculture in Tamil Nadu, India - R. Jayakumara Varadan; Pramod Kumar; Girish Kumar Jha; Suresh Pal; Rashmi Singh (Theoretical and Applied Climatology, 2017)

Curcumin inhibits paraquat induced lung inflammation and fibrosis by extracellular matrix modifications in mouse model - Namitosh Tyagi; D. Dash; Rashmi Singh (Inflammopharmacology, 2016)

Unleashing the potential of ligninolytic bacterial contributions towards pulp and paper industry: key challenges and new insights - Rashmi Priyadarshinee; Anuj Kumar; Tamal Mandal; Dalia Dasguptamandal (Environmental Science and Pollution Research, 2016)

Rice husk ash-based silica-supported iron catalyst coupled with Fenton-like process for the abatement of rice mill wastewater - Anuj Kumar; Rashmi Priyadarshinee; Subhajit Singha; Dalia Dasgupta; Tamal Mandal (Clean Technologies and Environmental Policy, 2016)

Interplay of nuclear receptors (ER, PR, and GR) and their steroid hormones in MCF-7 cells - Shubha M. Hegde; M. Naveen Kumar; K. Kavya; K. M. Kiran Kumar; Rashmi Nagesh; Rajeshwari H. Patil; R. L. Babu; Govindarajan T. Ramesh; S. Chidananda Sharma (Molecular and Cellular Biochemistry, 2016)

Identification of new resistant sources for bacterial blight in pomegranate - B. Tanuja Priya; B. N. S. Murthy; C. Gopalakrishnan; Rashmi B. Artal; S. Jagannath (European Journal of Plant Pathology, 2016)

Carbon balance effects of U.S. biofuel production and use - John M. DeCicco; Danielle Yuqiao Liu; Joonghyeok Heo; Rashmi Krishnan; Angelika Kurthen; Louise Wang (Climatic Change, 2016)

Comparison of predicted vehicular pollution concentration with air quality standards for different time periods - Awkash Kumar; Rashmi S. Patil; Anil Kumar Dikshit; Rakesh Kumar (Clean Technologies and Environmental Policy, 2016)

Galectin-9: From cell biology to complex disease dynamics - Sebastian John; Rashmi Mishra (Journal of Biosciences, 2016)

Genetics and Genomics of the Genus Amycolatopsis - Rashmi Kumari; Priya Singh; Rup Lal (Indian Journal of Microbiology, 2016)

Autism genes: the continuum that connects us all - RASHMI PARIHAR; SUBRAMANIAM GANESH (Journal of Genetics, 2016)

Synthetic Biology: Applications in the Food Sector - Ashish Tyagi; Ashwani Kumar; S. V. Aparna; Rashmi H. Mallappa; Sunita Grover; Virender Kumar Batish (Critical Reviews in Food Science and Nutrition, 2016)

Tropical Indian Ocean response to the decay phase of El Niño in a coupled model and associated changes in south and east-Asian summer monsoon circulation and rainfall - Jasti S. Chowdary; Anant Parekh; Rashmi Kakatkar; C. Gnanaseelan; G. Srinivas; Prem Singh; M. K. Roxy (Climate Dynamics, 2016)

Synthesis and anticonvulsant activities of functionalized 5-(isoindole-1,3-dione)-pyrimidinones - Rashmi Sharma; Dinesh Y. Gawande; Chander Mohan; Rajesh Kumar Goel (Medicinal Chemistry Research, 2016)

Assessment of Morphological and Biochemical Diversity in Seabuckthorn (Hippophae salicifolia D. Don.) Populations of Indian Central Himalaya - V. K. Yadav; S. K. Sharma; V. K. Rao; Rashmi Yadav; A. Radhakrishna (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Vehicular pollution modeling using the operational street pollution model (OSPM) for Chembur, Mumbai (India) - Awkash Kumar; Matthias Ketzel; Rashmi S. Patil; Anil Kumar Dikshit; Ole Hertel (Environmental Monitoring and Assessment, 2016)

Isolation and Characterization of Fipronil Degrading Acinetobacter calcoaceticus and Acinetobacter oleivorans from Rhizospheric Zone of Zea mays - Shivani Uniyal; Rashmi Paliwal; Megha Verma; R. K. Sharma; J. P. N. Rai (Bulletin of Environmental Contamination and Toxicology, 2016)

Development and Evaluation of a Novel Delivery System Containing Phytophospholipid Complex for Skin Aging - Monica Damle; Rashmi Mallya (AAPS PharmSciTech, 2016)

Can an early phase clinical pharmacology study replace a thorough QT study? Experience with a novel H3-receptor antagonist/inverse agonist - Rashmi R. Shah; Pierre Maison-Blanche; Philippe Robert; Emmanuel Denis; Thierry Duvauchelle (European Journal of Clinical Pharmacology, 2016)

Genomic regions controlling components of resistance for pea rust caused by Uromyces fabae (Pers.) de-Bary - Rashmi Rai; Anil Kumar Singh; Ramesh Chand; Chandra Prakash Srivastava; Arun Kumar Joshi; Brahma Deo Singh (Journal of Plant Biochemistry and Biotechnology, 2016)

Concentration-QT analysis of the randomized, placebo- and moxifloxacin-controlled thorough QT study of umeclidinium monotherapy and umeclidinium/vilanterol combination in healthy subjects - Rashmi Mehta; Michelle Green; Bela Patel; Jonathan Wagg (Journal of Pharmacokinetics and Pharmacodynamics, 2016)

Insertion/Insertion Genotype of Angiotensin I-Converting-Enzyme Gene Predicts Risk of Myocardial Infarction in North East India - Sukanya Baruah; Mriganka S. Chaliha; Prasanta K. Borah; Rashmi Rajkakati; Prodeep K. Borua; Jagadish Mahanta (Biochemical Genetics, 2016)

An outbreak of encephalitis associated with echovirus 19 in Uttar Pradesh, India, in 2011 - Dharam Veer Singh; Arvind Kumar; Pramesh Kumar; Manjari Baluni; Sneha Ghildiyal; Rashmi Kumar; Usha Kant Misra; Tapan N Dhole (Archives of Virology, 2016)

Native Microbial Inoculants for the Management of Meloidogyne incognita in Withania somnifera cv. Poshita - Sudeep Tiwari; Shilpi K. Saikia; Rashmi Singh; Shivesh Pratap Singh; Rakesh Pandey (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Antiglycation and cell protective actions of metformin and glipizide in erythrocytes and monocytes - Krishna Adeshara; Rashmi Tupe (Molecular Biology Reports, 2016)

Occurrence, identification and pathogenicity of Fusarium species associated with bakanae disease of basmati rice in India - B. M. Bashyal; Rashmi Aggarwal; Sapna Sharma; Sangeeta Gupta; Kirti Rawat; Dhiraj Singh; A. K. Singh; S. Gopala Krishnan (European Journal of Plant Pathology, 2016)

Response of two cultivars of Phaseolus vulgaris L. (French beans) plants exposed to enhanced UV-B radiation under mountain ecosystem - Rashmi Raghuvanshi; Rajesh Kumar Sharma (Environmental Science and Pollution Research, 2016)

Cytogenetic and ITS-psbA-trnH Sequence Analysis for Phylogenetic Inference in Mucuna sp. of India - M. Jaheer; R. Chopra; K. R. Kunder; Deepika Bhat; K. V. Rashmi; N. Sathyanarayana (Tropical Plant Biology, 2015)

Emergence of Aggressive Population in the Bipolaris sorokiniana of Barley (Hordeum vulgare L.) Through Anastomosis - B. M. Bashyal; Ramesh Chand; Rashmi Aggarwal (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Interdependence of laforin and malin proteins for their stability and functions could underlie the molecular basis of locus heterogeneity in Lafora disease - Shuchi Mittal; Mamta Upadhyay; Pankaj Kumar Singh; Rashmi Parihar; Subramaniam Ganesh (Journal of Biosciences, 2015)

Establishing assay sensitivity in QT studies: experience with the use of moxifloxacin in an early phase clinical pharmacology study and comparison with its effect in a thorough QT study - Rashmi R. Shah; Pierre Maison-Blanche; Thierry Duvauchelle; Philippe Robert; Emmanuel Denis (European Journal of Clinical Pharmacology, 2015)

Utility of Duckweeds as Source of Biomass Energy: a Review - Rashmi Verma; Surindra Suthar (BioEnergy Research, 2015)

Removal of sulfadimethoxine in soil mediated by extracellular oxidoreductases - Rashmi Singh; Sudeep S Sidhu; Hao Zhang; Qingguo Huang (Environmental Science and Pollution Research, 2015)

Disarming smiles: irrelevant happy faces slow post-error responses - Rashmi Gupta; Gedeon O. Deák (Cognitive Processing, 2015)

Erratum to: Synthesis, antitubercular activity, and molecular modeling studies of analogues of isoliquiritigenin and liquiritigenin, bioactive components from Glycyrrhiza glabra - Rashmi Gaur; Jay Prakash Thakur; Dharmendra K. Yadav; Deepak Singh Kapkoti; Ram Kishor Verma; Namita Gupta; Feroz Khan; Dharmendra Saikia; Rajendra Singh Bhakuni (Medicinal Chemistry Research, 2015)

Diverse and recombinant begomoviruses and various satellites are associated with Bhendi yellow vein mosaic disease of okra in India - Rashmi Rishishwar; Biswanath Mazumdar; Indranil Dasgupta (Journal of Plant Biochemistry and Biotechnology, 2015)

Validation of SWH and SSHA from SARAL/AltiKa Using Jason-2 and In-Situ Observations - Suchandra Aich Bhowmick; Rashmi Sharma; K. N. Babu; A. K. Shukla; Raj Kumar; R. Venkatesan; R. M. Gairola; Pascal Bonnefond; Nicolas Picot (Marine Geodesy, 2015)

SARAL/AltiKa Waveform Analysis to Monitor Inland Water Levels: A Case Study of Maithon Reservoir, Jharkhand, India - Surajit Ghosh; Praveen Kumar Thakur; Vaibhav Garg; Subrata Nandy; Shivprasad Aggarwal; Sudip Kumar Saha; Rashmi Sharma; Soumya Bhattacharyya (Marine Geodesy, 2015)

Estimation of Sea Ice Freeboard from SARAL/AltiKa Data - Megha Maheshwari; C. Mahesh; Kamaljit Singh Rajkumar; J. Pallipad; D. Ram Rajak; Sandip R. Oza; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Analysis of SARAL/AltiKa Wind and Wave over Indian Ocean and its Real-time Application in Wave Forecasting System at ISRO - Suchandra Aich Bhowmick; Ruchi Modi; K. G. Sandhya; M. Seemanth; T. M. Balakrishnan Nair; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

The SARAL/AltiKa Altimetry Satellite Mission - Jacques Verron; Pierre Sengenes; Juliette Lambin; Jocelyne Noubel; Nathalie Steunou; Amandine Guillot; Nicolas Picot; Sophie Coutin-Faye; Rashmi Sharma; R. M. Gairola; D. V. A. Raghava Murthy; James G. Richman; et al. (Marine Geodesy, 2015)

Shape Classification of AltiKa 40-Hz Waveforms using Linear Discriminant Analysis and Bayes Decision Rule in the Gujarat Coastal Region - Aditya Chaudhary; Sujit Basu; Raj Kumar; C. Mahesh; Rashmi Sharma (Marine Geodesy, 2015)

Improving Ocean State by Assimilating SARAL/AltiKa Derived Sea Level and Other Satellite-Derived Data in MITGCM - Abhisek Chakraborty; Raj Kumar; Sujit Basu; Rashmi Sharma (Marine Geodesy, 2015)

Impact of SARAL/AltiKa-Derived Sea Level Anomaly in a Data Assimilative Ocean Prediction System for the Indian Ocean - Smitha Ratheesh; Rashmi Sharma; K. V. S. R. Prasad; Sujit Basu (Marine Geodesy, 2015)

Synthesis, antitubercular activity, and molecular modeling studies of analogues of isoliquiritigenin and liquiritigenin, bioactive components from Glycyrrhiza glabra - Rashmi Gaur; Jay Prakash Thakur; Dharmendra K. Yadav; Deepak Singh Kapkoti; Ram Kishor Verma; Namita Gupta; Feroz Khan; Dharmendra Saikia; Rajendra Singh Bhakuni (Medicinal Chemistry Research, 2015)

Phencyclidine Intoxication Case Series Study - Paul Dominici; Kathryn Kopec; Rashmi Manur; Abdullah Khalid; Kathia Damiron; Adam Rowden (Journal of Medical Toxicology, 2015)

Strain- and context-based 50 kHz ultrasonic vocalizations and anxiety behaviour in the Wistar-Kyoto rat - Rashmi Madhava Rao; Monika Sadananda (Journal of Biosciences, 2015)

Emerging applications of cyanobacterial ultraviolet protecting compound scytonemin - Arti Mishra; Richa Tandon; Sarika Kesarwani; Rashmi Singh; G. L. Tiwari (Journal of Applied Phycology, 2015)

Serum levels of IL-8, IFNγ, IL-10, and TGF β and their gene expression levels in severe and non-severe cases of dengue virus infection - Nidhi Pandey; Amita Jain; R. K. Garg; Rashmi Kumar; O. P. Agrawal; P. V. Lakshmana Rao (Archives of Virology, 2015)

Evaluating the potential of immobilized bacterial consortium for black liquor biodegradation - Rashmi Paliwal; Shivani Uniyal; J. P. N. Rai (Environmental Science and Pollution Research, 2015)

Validation of SSR markers associated with rust (Uromyces fabae) resistance in pea (Pisum sativum L.) - Anil Kumar Singh; Rashmi Rai; Brahma Deo Singh; Ramesh Chand; Chandra Prakash Srivastava (Physiology and Molecular Biology of Plants, 2015)

Crystal Morphology and Differential Meso–Micro Pore-Volume Distribution Patterns of Clinoptilolite Fractions - K. Ramesh; K. Sammi Reddy; I. Rashmi; A. K. Biswas; A. Subba Rao (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Changes in metabolic pathways of Desulfovibrio alaskensis G20 cells induced by molybdate excess - Rashmi R. Nair; Célia M. Silveira; Mário S. Diniz; Maria G. Almeida; Jose J. G. Moura; Maria G. Rivas (JBIC Journal of Biological Inorganic Chemistry, 2015)

River Water Prediction Modeling Using Neural Networks, Fuzzy and Wavelet Coupled Model - Kulwinder Singh Parmar; Rashmi Bhardwaj (Water Resources Management, 2015)

Exploitation of microbes for enhancing bacoside content and reduction of Meloidogyne incognita infestation in Bacopa monnieri L - Rupali Gupta; Sudeep Tiwari; Shilpi K. Saikia; Virendra Shukla; Rashmi Singh; S. P. Singh; P. V. Ajay Kumar; Rakesh Pandey (Protoplasma, 2015)

Statistical, time series, and fractal analysis of full stretch of river Yamuna (India) for water quality management - Kulwinder Singh Parmar; Rashmi Bhardwaj (Environmental Science and Pollution Research, 2015)

Cadmium Induced Lipid Peroxidation and Effects on Glutathione Dependent Enzymes in Tissues of Labeo rohita - Anurag Dabas; N. S. Nagpure; R. M. Mishra; Ravindra Kumar; Basdeo Kushwaha; Rashmi Srivastava; Pavan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Synthetic Biology in Action: Developing a Drug Against MDR-TB - Anjali Saxena; Udita Mukherjee; Rashmi Kumari; Priya Singh; Rup Lal (Indian Journal of Microbiology, 2014)

Mutational Consequences of Aberrant Ion Channels in Neurological Disorders - Dhiraj Kumar; Rashmi K. Ambasta; Pravir Kumar (The Journal of Membrane Biology, 2014)

Green synthesis and biological evaluation of some new benzothiazolo [2,3-b] quinazolin-1-ones as anticancer agents - Jaiprakash N. Sangshetti; Deepak K. Lokwani; Rashmi S. Chouthe; Ashok Ganure; Bhuvan Raval; Firoz A. Kalam Khan; Devanand B. Shinde (Medicinal Chemistry Research, 2014)

Effect of crude oil contamination on the chlorophyll content and morpho-anatomy of Cyperus brevifolius (Rottb.) Hassk - Plabita Baruah; Rashmi Rekha Saikia; Partha Pratim Baruah; Suresh Deka (Environmental Science and Pollution Research, 2014)

Forecasting quantitative rainfall over India using multi-model ensemble technique - V. R. Durai; Rashmi Bhardwaj (Meteorology and Atmospheric Physics, 2014)

Evaluation of statistical bias correction methods for numerical weather prediction model forecasts of maximum and minimum temperatures - V. R. Durai; Rashmi Bhradwaj (Natural Hazards, 2014)

Degradation of Di- Through Hepta-Chlorobiphenyls in Clophen Oil Using Microorganisms Isolated from Long Term PCBs Contaminated Soil - Jitendra K. Sharma; Ravindra K. Gautam; Rashmi R. Misra; Sanjay M. Kashyap; Sanjeev K. Singh; Asha A. Juwarkar (Indian Journal of Microbiology, 2014)

Assimilation of Doppler Weather Radar Data in WRF Model for Simulation of Tropical Cyclone Aila - Kuldeep Srivastava; Rashmi Bhardwaj (Pure and Applied Geophysics, 2014)

Impact of sub-daily wind forcing on mixed-layer depth and sea surface temperature: study using observations and a one-dimensional upper ocean model - Rashmi Sharma; Abhijit Sarkar (International Journal of Remote Sensing, 2014)

Generation of expressed sequence tags under cadmium stress for gene discovery and development of molecular markers in chickpea - Rashmi Gaur; Sabhyata Bhatia; Meetu Gupta (Protoplasma, 2014)

Protein mapping of Chaetomium globosum, a potential biological control agent through proteomics approach - Sapna Sharma; Rashmi Aggarwal; Anita Yadav; Sangeeta Gupta (Journal of Plant Biochemistry and Biotechnology, 2014)

Location specific forecasting of maximum and minimum temperatures over India by using the statistical bias corrected output of global forecasting system - V R Durai; Rashmi Bhardwaj (Journal of Earth System Science, 2014)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Yield characteristics and morphometric relationships of giant freshwater prawn, Macrobrachium rosenbergii (de Man, 1879) - P. L. Lalrinsanga; Bindu R. Pillai; Gunamaya Patra; Swagatika Mohanty; Namita Kumari Naik; Rashmi Ranjan Das; Sovan Sahu; Rajesh Nelliyoura (Aquaculture International, 2014)

A new class of bactericidal agents against S. aureus, MRSA and VRE derived from bisindolylmethane - Deepak K. Sharma; Anil K. Tripathi; Rashmi Sharma; Reena Chib; Reyaz ur Rasool; Altaf Hussain; Baldev Singh; Anindya Goswami; Inshad A. Khan; Debaraj Mukherjee (Medicinal Chemistry Research, 2014)

Analysis and very short range forecast of cyclone “AILA” with radar data assimilation with rapid intermittent cycle using ARPS 3DVAR and cloud analysis techniques - Kuldeep Srivastava; Rashmi Bhardwaj (Meteorology and Atmospheric Physics, 2014)

Association of the GRM4 gene variants with juvenile myoclonic epilepsy in an Indian population - RASHMI PARIHAR; ROHIT MISHRA; SANJEEV KUMAR SINGH; SITA JAYALAKSHMI; MAN MOHAN MEHNDIRATTA; SUBRAMANIAM GANESH (Journal of Genetics, 2014)

Protein Thiols and Butryrylcholinestrase in Saliva of Oral Cancer Patients - Yousef Rezaei Chianeh; Rashmi Manjunath; Krishnananda Prabhu; Donald Fernandes; M. Vidyasagar; Asha Kamath (Indian Journal of Clinical Biochemistry, 2014)

Bacteriocin Production and Different Strategies for Their Recovery and Purification - Anita Kumari Garsa; Rashmi Kumariya; S. K. Sood; Anil Kumar; Suman Kapila (Probiotics and Antimicrobial Proteins, 2014)

Biotransformation of artemisinin derivatives by Glycyrrhiza glabra, Lavandula officinalis, and Panax quinquefolium - Rashmi Gaur; Suman Patel; Ram Kishor Verma; Archana Mathur; Rajendra Singh Bhakuni (Medicinal Chemistry Research, 2014)

Prenatal music stimulation facilitates the postnatal functional development of the auditory as well as visual system in chicks (Gallus domesticus) - Saborni Roy; Tapas C Nag; Ashish Datt Upadhyay; Rashmi Mathur; Suman Jain (Journal of Biosciences, 2014)

An elephantine challenge: human–elephant conflict distribution in the largest Asian elephant population, southern India - Sanjay Gubbi; M. H. Swaminath; H. C. Poornesha; Rashmi Bhat; R. Raghunath (Biodiversity and Conservation, 2014)

Daunorubicin forms a specific complex with a secreted serine protease of Streptomyces peucetius - Rashmi Dubey; Karuppasamy Kattusamy; Kuppamuthu Dharmalingam; Ranjan Prasad (World Journal of Microbiology and Biotechnology, 2014)

Real-time nowcast of a cloudburst and a thunderstorm event with assimilation of Doppler weather radar data - Kuldeep Srivastava; Rashmi Bhardwaj (Natural Hazards, 2014)

Arsenic (III) adsorption on iron acetate coated activated alumina: thermodynamic, kinetics and equilibrium approach - Bodhaditya Das; Rashmi Rekha Devi; Iohborlang M Umlong; Kusum Borah; Saumen Banerjee; Anup Kr Talukdar (Journal of Environmental Health Science and Engineering, 2013)

Removal of hydrocarbon from refinery tank bottom sludge employing microbial culture - Rashmi Rekha Saikia; Suresh Deka (Environmental Science and Pollution Research, 2013)

Corresponding Properties of Fatty Oils of Cleome viscosa and Jatropha curcas as Resources of Biodiesel - Rashmi Kumari; Gopal Rao Mallavarapu; Vinod Kumar Jain; Sushil Kumar (Agricultural Research, 2013)

Molecular characterization of Alr1105 a novel arsenate reductase of the diazotrophic cyanobacterium Anabaena sp. PCC7120 and decoding its role in abiotic stress management in Escherichia coli - Sarita Pandey; Alok K. Shrivastava; Rashmi Rai; Lal Chand Rai (Plant Molecular Biology, 2013)

Genetic variation in salt tolerance at the seedling stage in an interspecific backcross inbred line population of cultivated tetraploid cotton - Rashmi Sharma Tiwari; Geno A. Picchioni; Robert L. Steiner; Don C. Jones; S. E. Hughs; Jinfa Zhang (Euphytica, 2013)

Synthesis and evaluation of antibacterial and antifungal activities of new (Z)-3-bromo-4-(1,3-diaryl-1H-pyrazol-4-yl)but-3-en-2-ones and 4-(3-methyl-1-phenyl-1H-pyrazol-5-yl)-1,3-diaryl-1H-pyrazoles - Rashmi Pundeer; Sushma; Vijay Kiran; Chetan Sharma; K. R. Aneja; Om Prakash (Medicinal Chemistry Research, 2013)

Polycyclic aromatic hydrocarbons in some grounded coffee brands - Inderpreet Singh Grover; Rashmi Sharma; Satnam Singh; Bonamali Pal (Environmental Monitoring and Assessment, 2013)

Coffee consumption and the risk of overall and fatal prostate cancer in the NIH-AARP Diet and Health Study - Claire Bosire; Meir J. Stampfer; Amy F. Subar; Kathryn M. Wilson; Yikyung Park; Rashmi Sinha (Cancer Causes & Control, 2013)

Erratum to: Establishment of dedifferentiated callus of haploid origin from unfertilized ovaries of tea (Camellia sinensis (L.) O. Kuntze) as a potential source of total phenolics and antioxidant activity - Rashmi Rekha Hazarika; Rakhi Chaturvedi (In Vitro Cellular & Developmental Biology - Plant, 2013)

Co-existence of wind seas and swells along the west coast of India during non-monsoon season - R. Rashmi; V. M. Aboobacker; P. Vethamony; M. P. John (Ocean Science, 2013)
An attempt has been made to understand the co-existence of wind seas and swells along the west coast of India during non-monsoon season. Wave data were collected in different years during non-monsoon season (off Goa during May 2005, off Ratnagiri during January–February 2008 and off Dwarka during December 2007–January 2008), which is fairly a calm weather season along these regions. Diurnal variation in wave parameters is noticeable along the central west coast of India (off Goa and Ratnagiri), which is due to the interaction of multidirectional waves (both wind seas and swells) of varying magnitudes and frequencies. Swells are predominantly mature (91%) and old (88%) during late pre-monsoon and post-monsoon seasons, respectively. Sea Swell Energy Ratio quantifies wind sea, swell and mixed seas prevailing in these regions during non-monsoon season. Intermodal distance (ID) between the energy peaks is moderately separated during non-monsoon season, whereas, during the shamal events, energy peaks are very close to each other (ID ∼ 0). However, pure wind seas (ID ∼ 1) are weakly present and found to co-exist with the swells almost all the time during non-monsoon season. Wind sea growth has been found while the swell propagates opposite to the direction of the wind and wind sea. Wind seas have minimum angular spreads in multimodal state. Under low winds, the interaction between wind sea and swell dominates and thereby the multimodal state reduces to unimodal state. The fetch available for the evolution of the wind sea spectrum has been estimated, and it is found to be less than 150 km. For the fetch limited condition, a non-dimensional empirical relation has been derived relating the significant wind sea height in terms of wind speed and peak wind sea period, and this relation fits for the west coast of India.

Highly Specific Culture-Independent Detection of YGNGV Motif-Containing Pediocin-Producing Strains - S. K. Sood; B. Vijay Simha; Rashmi Kumariya; Anita Kumari Garsa; Jitender Mehla; Sunita Meena; Puja Lather (Probiotics and Antimicrobial Proteins, 2013)

Evaluation of OSCAR ocean surface current product in the tropical Indian Ocean using in situ data - RAJESH SIKHAKOLLI; RASHMI SHARMA; SUJIT BASU; B S GOHIL; ABHIJIT SARKAR; K V S R PRASAD (Journal of Earth System Science, 2013)

Establishment of dedifferentiated callus of haploid origin from unfertilized ovaries of tea (Camellia sinensis (L.) O. Kuntze) as a potential source of total phenolics and antioxidant activity - Hazarika Rashmi Rekha; Chaturvedi Rakhi (In Vitro Cellular & Developmental Biology - Plant, 2013)

Molecular identification of enteroviruses associated with aseptic meningitis in children from India - Arvind Kumar; Deepti Shukla; Rashmi Kumar; Mohammad Z. Idris; Prashant Jauhari; Shalini Srivastava; Tapan N. Dhole (Archives of Virology, 2013)

α,α-Dibromoacetophenones mediated synthesis of some new 7H-7-alkoxy-3-alkyl/phenyl-6-aryl-s-triazolo[3,4-b][1,3,4]thiadiazines and their antimicrobial evaluation - Rashmi Pundeer; Vijay Kiran; Richa Prakash; Sushma; Subhash C. Bhatia; Chetan Sharma; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Effect of S-methylisothiourea in acetaminophen-induced hepatotoxicity in rat - Amar S. More; Rashmi R. Kumari; Gaurav Gupta; Kandasamy Kathirvel; Milindmitra K. Lonare; Rohini S. Dhayagude; Dhirendra Kumar; Dinesh Kumar; Anil K. Sharma; Surendra K. Tandan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Genetic Variation Among fruit flies of the Genus Bactrocera (Diptera: Tephritidae: Dacinae) - Rashmi Singh; R. R. Tewari (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2012)

Comparability and repeatability of methods for estimating the dietary intake of the heterocyclic amine contaminant 2-amino-1-methyl-6-phenylimidazo[4,5 b ]pyridine (PhIP) - Nicole C. Deziel; Timothy J. Buckley; Rashmi Sinha; Salahaddhin Abubaker; Elizabeth A. Platz; Paul T. Strickland (Food Additives & Contaminants: Part A, 2012)

Selenium treatment alters phytochemical and biochemical activity of in vitro-grown tissues and organs of Allium sativum L. - Rashmi Kapoor; Sekh Abdul Nasim; Bhupinder Dhir; Mahmooduzzafar; Abdul Mujib (In Vitro Cellular & Developmental Biology - Plant, 2012)

Socioeconomic status, healthcare density, and risk of prostate cancer among African American and Caucasian men in a large prospective study - Jacqueline M. Major; M. Norman Oliver; Chyke A. Doubeni; Albert R. Hollenbeck; Barry I. Graubard; Rashmi Sinha (Cancer Causes & Control, 2012)

Assessment of Cane Juice Deterioration by Conductivity Method - Vikesh Kumar; Rashmi Upadhyay; P. Sanyal (Sugar Tech, 2012)

EST-derived genic molecular markers: development and utilization for generating an advanced transcript map of chickpea - Shalu Choudhary; Rashmi Gaur; Shefali Gupta; Sabhyata Bhatia (Theoretical and Applied Genetics, 2012)

What is the Functional Role of N-terminal Transmembrane Helices in the Metabolism Mediated by Liver Microsomal Cytochrome P450 and its Reductase? - Daniel Andrew Gideon; Rashmi Kumari; Andrew M. Lynn; Kelath Murali Manoj (Cell Biochemistry and Biophysics, 2012)

Coffee, tea, soda, and caffeine intake in relation to risk of adult glioma in the NIH-AARP Diet and Health Study - Robert Dubrow; Amy S. Darefsky; Neal D. Freedman; Albert R. Hollenbeck; Rashmi Sinha (Cancer Causes & Control, 2012)

Projection-Based Assimilation of Satellite-Derived Surface Data in an Indian Ocean Circulation Model - Smitha Ratheesh; Rashmi Sharma; Sujit Basu (Marine Geodesy, 2012)

Effect of formulated root endophytic fungus Piriformospora indica and plant growth promoting rhizobacteria fluorescent pseudomonads R62 and R81 on Vigna mungo - Vinod Kumar; M. V. R. K. Sarma; Krishna Saharan; Rashmi Srivastava; Lalit Kumar; Vikram Sahai; V. S. Bisaria; A. K. Sharma (World Journal of Microbiology and Biotechnology, 2012)

A novel salt-inducible gene SbSI-1 from Salicornia brachiata confers salt and desiccation tolerance in E. coli - Narendra Singh Yadav; Deo Rashmi; Dinkar Singh; Pradeep K. Agarwal; Bhavanath Jha (Molecular Biology Reports, 2012)

Altimeter data assimilation in the tropical Indian Ocean using water property conserving scheme - BHASHA M MANKAD; RASHMI SHARMA; SUJIT BASU; P K PAL (Journal of Earth System Science, 2012)

Pterospermumocarpon, a new malvalean fruit from the Sindhudurg Formation (Miocene) of Maharashtra, India, and its phytogeographical significance - RASHMI SRIVASTAVA; R K SAXENA; GAURAV SRIVASTAVA (Journal of Earth System Science, 2012)

Simulated Heat Content Variability in the Upper Layers of the Tropical Indian Ocean - Imran M. Momin; Neeraj Agarwal; Rashmi Sharma; Neetu; Sujit Basu; Abhijit Sarkar; Vijay K. Agarwal (Marine Geodesy, 2012)

Picobirnavirus detection in bovine and buffalo calves from foothills of Himalaya and Central India - Yashpal Singh Malik; K. M. Chandrashekar; Kuldeep Sharma; Adil A. Haq; Nirupama Vaid; Somendu Chakravarti; Munish Batra; Rashmi Singh; A. B. Pandey (Tropical Animal Health and Production, 2011)

Assimilation of Indian Doppler Weather Radar observations for simulation of mesoscale features of a land-falling cyclone - Kuldeep Srivastava; Rashmi Bhardwaj; S. K. Roy Bhowmik (Natural Hazards, 2011)

Socioeconomic deprivation impact on meat intake and mortality: NIH-AARP Diet and Health Study - Jacqueline M. Major; Amanda J. Cross; Chyke A. Doubeni; Yikyung Park; Min Lian; Albert R. Hollenbeck; Arthur Schatzkin; Barry I. Graubard; Rashmi Sinha (Cancer Causes & Control, 2011)

Patterns of meat intake and risk of prostate cancer among African-Americans in a large prospective study - Jacqueline M. Major; Amanda J. Cross; Joanne L. Watters; Albert R. Hollenbeck; Barry I. Graubard; Rashmi Sinha (Cancer Causes & Control, 2011)

Fruit and vegetable consumption is inversely associated with having pancreatic cancer - Rick J. Jansen; Dennis P. Robinson; Rachael Z. Stolzenberg-Solomon; William R. Bamlet; Mariza de Andrade; Ann L. Oberg; Traci J. Hammer; Kari G. Rabe; Kristin E. Anderson; Janet E. Olson; Rashmi Sinha; Gloria M. Petersen (Cancer Causes & Control, 2011)

An identification guide to the wood destroying termites of south India - Rashmi R. Shanbhag; R. Sundararaj (Journal of the Indian Academy of Wood Science, 2011)

Arsenic-induced changes in morphological, physiological, and biochemical attributes and artemisinin biosynthesis in Artemisia annua, an antimalarial plant - Rashmi Rai; Sarita Pandey; Shashi Pandey Rai (Ecotoxicology, 2011)

Characterization and Phylogenetic Diversity of Carboxymethyl Cellulase Producing Bacillus Species from a Landfill Ecosystem - Suresh Korpole; Rashmi Sharma; Dipti Verma (Indian Journal of Microbiology, 2011)

Dynamic height anomaly from Argo profiles and sea-level anomaly from satellite altimetry: a comparative study in the Indian Ocean - Smitha George; Rashmi Sharma; Neeraj Agarwal; Sujit Basu; Abhijit Sarkar (International Journal of Remote Sensing, 2011)

Molecular mapping for resistance to pea rust caused by Uromyces fabae (Pers.) de-Bary - Rashmi Rai; Anil Kumar Singh; Brahma Deo Singh; Arun Kumar Joshi; Ramesh Chand; Chandra Prakash Srivastava (Theoretical and Applied Genetics, 2011)

Glycyrrhiza glabra (Linn.) and Lavandula officinalis (L.) cell suspension cultures-based biotransformation of β-artemether - Suman Patel; Rashmi Gaur; Mohita Upadhyaya; Archana Mathur; Ajay K. Mathur; Rajendra S. Bhakuni (Journal of Natural Medicines, 2011)

Conductometric Studies of Sugar Solution: An Additional Parameter to Assess Sugar Quality - Vikesh Kumar; P. Sanyal; Rashmi Upadhyay (Sugar Tech, 2011)

Clonal propagation and hydroxycitric acid production from in vitro shoot cultures of Garcinia indica using root suckers as explant - Rashmi P. Tembe; Manjushri A. Deodhar (In Vitro Cellular & Developmental Biology - Plant, 2011)

Ficus palaeoracemosa sp. nov. – A new fossil leaf from the Kasauli Formation of Himachal Pradesh and its palaeoclimatic significance - Gaurav Srivastava; Rashmi Srivastava; R C Mehrotra (Journal of Earth System Science, 2011)

Comparison of lung accumulation of cationic liposomes in normal rats and LPS-treated rats - Susanne Herber-Jonat; Rashmi Mittal; Stefan Gsinn; Hermann Bohnenkamp; Eric Guenzi; Andreas Schulze (Inflammation Research, 2011)

Mechanistic Clues in the Cardioprotective Effect of Terminalia Arjuna Bark Extract in Isoproterenol-Induced Chronic Heart Failure in Rats - Adila Parveen; Rashmi Babbar; Sarita Agarwal; Anita Kotwani; Mohammad Fahim (Cardiovascular Toxicology, 2011)

Characterization of basal pseudopod-like processes in ileal and colonic PYY cells - Diego V. Bohórquez; Rashmi Chandra; Leigh Ann Samsa; Steven R. Vigna; Rodger A. Liddle (Journal of Molecular Histology, 2011)

Persistence and Dissipation of Fluopicolide in/on Grape Berries and Soil Under Semi Arid Tropical Climatic Conditions of India - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; G. K. Jagdish; N. Rashmi; Sampath Kumar; G. S. Prakash (Bulletin of Environmental Contamination and Toxicology, 2011)

Erratum to: 2-Substituted-8-methyl-3,6-dihydroimidazo [4,5-c]pyrazolo[3,4-e]pyridazine as an anti-inflammatory agent - Ashish Kumar Tewari; Rashmi Dubey; Anil Mishra (Medicinal Chemistry Research, 2011)

2-Substituted-8-methyl-3,6-dihydroimidazo[4,5-c]pyrazolo[3,4-e]pyridazine as an anti-inflammatory agent - Ashish Kumar Tewari; Rashmi Dubey; Anil Mishra (Medicinal Chemistry Research, 2011)

Microbial detoxification of pathotoxin produced by spot blotch pathogen Bipolaris sorokiniana infecting wheat - Rashmi Aggarwal; Sangeeta Gupta; V. B. Singh; Sapna Sharma (Journal of Plant Biochemistry and Biotechnology, 2011)

Evidence for functional interaction of plasma membrane electron transport, voltage-dependent anion channel and volume-regulated anion channel in frog aorta - Rashmi P. Rao; J. Prakasa Rao (Journal of Biosciences, 2010)

Interaction of Zinc, Ascorbic Acid, and Folic Acid in Glycation with Albumin as Protein Model - Rashmi Tupe; Vaishali Agte (Biological Trace Element Research, 2010)

Production of mouse chimeras by injection of embryonic stem cells into the perivitelline space of one-cell stage embryos - Yves De Repentigny; Rashmi Kothary (Transgenic Research, 2010)

Pathogenic and genetic variability in Tilletia indica monosporidial culture lines using universal rice primer-PCR - Rashmi Aggarwal; Aradhika Tripathi; Anita Yadav (European Journal of Plant Pathology, 2010)

Cow dung extract: a medium for the growth of pseudomonads enhancing their efficiency as biofertilizer and biocontrol agent in rice - Rashmi Srivastava; Michel Aragno; A. K. Sharma (Indian Journal of Microbiology, 2010)

Contamination of Ground Water as a Consequence of Land Disposal of Dye Waste Mixed Sewage Effluents: A Case Study of Panipat District of Haryana, India - S. K. Dubey; Rashmi Yadav; R. K. Chaturvedi; R. K. Yadav; V. K. Sharma; P. S. Minhas (Bulletin of Environmental Contamination and Toxicology, 2010)

Persistence and Dissipation of Flubendiamide and Des-iodo Flubendiamide in Cabbage (Brassica oleracea Linne) and Soil - Soudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagadish; N. Rashmi (Bulletin of Environmental Contamination and Toxicology, 2010)

Quantitative determination of gibberellins by high performance liquid chromatography from various gibberellins producing Fusarium strains - Kirti Bhalla; Shashi Bala Singh; Rashmi Agarwal (Environmental Monitoring and Assessment, 2010)

Biotransformation of artemisinin using cell suspension cultures of Catharanthus roseus (L.) G.Don and Lavandula officinalis L. - Suman Patel; Rashmi Gaur; Priyanka Verma; Rajendra S. Bhakuni; Archana Mathur (Biotechnology Letters, 2010)

Pseudopod-like basal cell processes in intestinal cholecystokinin cells - Rashmi Chandra; Leigh Ann Samsa; Steven R. Vigna; Rodger A. Liddle (Cell and Tissue Research, 2010)

Mixed Layer Depth and its Variability in the Eastern Equatorial Indian Ocean as Revealed by Observations and Model Simulations - Rashmi Sharma; Neeraj Agarwal; Imran M. Momin; Vijay K. Agarwal (Marine Geodesy, 2010)

Immune evasive mechanisms contributing to persistent Leishmania donovani infection - Simona Stäger; Trupti Joshi; Rashmi Bankoti (Immunologic Research, 2010)

Erratum to: Ultrastructural immunogold localization of nitric oxide synthase isoforms in rat and human eosinophils - Rohit Saluja; Rashmi Saini; Kalyan Mitra; Virendra K. Bajpai; Madhu Dikshit (Cell and Tissue Research, 2010)

Fate of Fipronil and its Metabolites in/on Grape Leaves, Berries and Soil Under Semi Arid Tropical Climatic Conditions - Soudamini Mohapatra; M. Deepa; G. K. Jagdish; N. Rashmi; Sampath Kumar; G. S. Prakash (Bulletin of Environmental Contamination and Toxicology, 2010)

Ultrastructural immunogold localization of nitric oxide synthase isoforms in rat and human eosinophils - Rohit Saluja; Rashmi Saini; Kalyan Mitra; Virendra K. Bajpai; Madhu Dikshit (Cell and Tissue Research, 2010)

Alliin production in various tissues and organs of Allium sativum grown under normal and sulphur-supplemented in vitro conditions - Sekh Abdul Nasim; Bhupinder Dhir; Rashmi Kapoor; Samar Fatima; Mahmooduzzafar; Abdul Mujib (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Mice with podocyte-specific overexpression of wild type α-actinin-4 are healthy controls for K256E-α-actinin-4 mutant transgenic mice - Jean-Louis Michaud; Erin Stitt-Cavanaugh; Nicole Endlich; Karlhans Endlich; Yves De Repentigny; Rashmi Kothary; Chris R. J. Kennedy (Transgenic Research, 2010)

Spatial modeling and validation of forest cover change in Kanakapura region using GEOMOD - M. K. Rashmi; N. Lele (Journal of the Indian Society of Remote Sensing, 2010)

Endophytic Bacteria from Ocimum sanctum and Their Yield Enhancing Capabilities - Rashmi Tiwari; Alok Kalra; M. P. Darokar; Mahesh Chandra; Nitin Aggarwal; A. K. Singh; S. P. S. Khanuja (Current Microbiology, 2010)

Vanillin Phosphorescence as a Probe of Molecular Mobility in Amorphous Sucrose - Rashmi S. Tiwari; Richard D. Ludescher (Journal of Fluorescence, 2010)

Plasma membrane electron transport in frog blood vessels - Rashmi P. Rao; K. Nalini; J. Prakasa Rao (Journal of Biosciences, 2009)

Antioxidant, anti-inflammatory and analgesic potential of the Citrus decumana L. peel extract - Shailja Sood; Bhawna Arora; Stuti Bansal; Arunachalam Muthuraman; Naresh Singh Gill; Rashmi Arora; Manoj Bali; Pritam Dev Sharma (Inflammopharmacology, 2009)

Discriminating the invasive species, ‘Lantana’ using vegetation indices - Rashmi Kandwal; C. Jeganathan; Valentyn Tolpekin; S. P. S. Kushwaha (Journal of the Indian Society of Remote Sensing, 2009)

Screening of biofouling activity in marine bacterial isolate from ship hull - D. Dhanasekaran; N. Thajuddin; M. Rashmi; T. L. Deepika; M. Gunasekaran (International Journal of Environmental Science and Technology, 2009)

Identification of genetically diverse genotypes for photoperiod insensitivity in soybean using RAPD markers - R. K. Singh; V. S. Bhatia; Sanjeev Yadav; Rashmi Athale; N. Lakshmi; K. N. Guruprasad; G. S. Chauhan (Physiology and Molecular Biology of Plants, 2008)

Both Cell-Autonomous and Cell Non-Autonomous Functions of GAP-43 are Required for Normal Patterning of the Cerebellum In Vivo - Yiping Shen; Rashmi Mishra; Shyamala Mani; Karina F. Meiri (The Cerebellum, 2008)

Emission of isoprene from common Indian plant species and its implications for regional air quality - Rashmi Singh; Abhai Pratap Singh; M. P. Singh; Animesh Kumar; C. K. Varshney (Environmental Monitoring and Assessment, 2008)

Regulation of glycogen metabolism by anti-dyslipidemic action of gemfibrozil and cholestyramine in a dyslipidemic-diabetic hamster model - Mohd Mubin Khan; Rashmi Saxena; Anju Puri; Ashok Kumar Khanna; Ramesh Chander; Jitendra Kumar Saxena (Medicinal Chemistry Research, 2008)

Production, Partial Purification and Characterization of Extracelluar Xylanase from Chaetomium globosum - S. Khayum Ahammed; Rashmi Aggarwal; H. C. Kapoor (Journal of Plant Biochemistry and Biotechnology, 2008)

Xanthine oxidase as a marker of myocardial infarction - Rashmi Raghuvanshi; Aiki Kaul; Pushpa Bhakuni; Aparna Mishra; M. K. Misra (Indian Journal of Clinical Biochemistry, 2007)

Metal Fractionation Study on Bed Sediments of Lake Nainital, Uttaranchal, India - C. K. Jain; D. S. Malik; Rashmi Yadav (Environmental Monitoring and Assessment, 2007)

Growth Control by Ethylene: Adjusting Phenotypes to the Environment - Ronald Pierik; Rashmi Sasidharan; Laurentius A. C. J. Voesenek (Journal of Plant Growth Regulation, 2007)

Impact Assessment and Recommendation of Alternative Conjunctive Water Use Strategies for Salt Affected Agricultural Lands through a Field Scale Decision Support System – A Case Study - Ravinder Kaur; Madhumita Paul; Rashmi Malik (Environmental Monitoring and Assessment, 2007)

Smn Depletion Alters Profilin II Expression and Leads to Upregulation of the RhoA/ROCK Pathway and Defects in Neuronal Integrity - Mélissa Bowerman; Dina Shafey; Rashmi Kothary (Journal of Molecular Neuroscience, 2007)

Subtractive differential display: a modified differential display technique for isolating differentially expressed genes - Rashmi U. Pathak; M. S. Kanungo (Molecular Biology Reports, 2007)

Prevention of isoproterenol-induced cardiac hypertrophy by eugenol, an antioxidant - Rashmi Choudhary; K. P. Mishra; C. Subramanyam (Indian Journal of Clinical Biochemistry, 2006)

Comparing age-wise reference intervals for serum creatinine concentration in a “Reality check” of the recommended cut-off - Mascha Verma; Rashmi Khadapkar; Priyadarshi Soumyaranjan Sahu; Bibhu Ranjan Das (Indian Journal of Clinical Biochemistry, 2006)

Different population histories of the Mundari- and Mon-Khmer-speaking Austro-Asiatic tribes inferred from the mtDNA 9-bp deletion/insertion polymorphism in Indian populations - Kumarasamy Thangaraj; Vempati Sridhar; Toomas Kivisild; Alla G. Reddy; Gyaneshwer Chaubey; Vijay Kumar Singh; Suminder Kaur; Pooja Agarawal; Amit Rai; Jalaj Gupta; Chandana Basu Mallick; Niraj Kumar; et al. (Human Genetics, 2006)

Interrelations between oxidative stress and calcineurin in the attenuation of cardiac apoptosis by eugenol - Rashmi Choudhary; Kaushala Prasad Mishra; Chivukula Subramanyam (Molecular and Cellular Biochemistry, 2006)

Genetic alterations at the Bpag1 locus in dt mice and their impact on transcript expression - Madeline Pool; Céline Boudreau Larivière; Gilbert Bernier; Kevin G. Young; Rashmi Kothary (Mammalian Genome, 2005)

Different population histories of the Mundari- and Mon-Khmer-speaking Austro-Asiatic tribes inferred from the mtDNA 9-bp deletion/insertion polymorphism in Indian populations - Kumarasamy Thangaraj; Vempati Sridhar; Toomas Kivisild; Alla G. Reddy; Gyaneshwer Chaubey; Vijay Kumar Singh; Suminder Kaur; Pooja Agarawal; Amit Rai; Jalaj Gupta; Chandana Basu Mallick; Niraj Kumar; et al. (Human Genetics, 2005)

Environmental management plan for port and harbour projects - A. K. Gupta; S. K. Gupta; Rashmi S. Patil (Clean Technologies and Environmental Policy, 2005)

Statistical analyses of coastal water quality for a port and harbour region in India - A. K. Gupta; S. K. Gupta; Rashmi S. Patil (Environmental Monitoring and Assessment, 2005)

Effect of vitamin E on the platelet xanthine oxidase and lipid peroxidation in the patients of myocardial infarction - Rashmi Raghuvanshi; M. Chandra; P. C. Misra; M. K. Misra (Indian Journal of Clinical Biochemistry, 2005)

Response Surface Methodology to Investigate the Iontophoretic Delivery of Tacrine Hydrochloride - Rashmi S. Upasani; Ajay K. Banga (Pharmaceutical Research, 2004)

Protective Action of 24 Amino Acids on the Toxicity of Copper to a Freshwater Tubificid Worm Tubifex tubifex Muller - B. S. Khangarot; Rashmi S. Rathore (Water, Air, & Soil Pollution, 2004)

Antidyslipidemic and antioxidant activities of different fractions ofTerminalia arjuna stem bark - Ramesh Chander; Kavita Singh; A K Khanna; S M Kaul; Anju Puri; Rashmi Saxena; Gitika Bhatia; Farhan Rizvi; A K. Rastogi (Indian Journal of Clinical Biochemistry, 2004)

Role of antibiosis in the biological control of spot blotch (Cochliobolus sativus) of wheat by Chaetomium globosum - Rashmi Aggarwal; A.K. Tewari; K.D. Srivastava; D.V. Singh (Mycopathologia, 2004)

Cobalt-resistance in wall-less mutant (fz; sg; os-1) of Neurospora crassa - R.Sri Rajyalaxmi; J. Naveena Lavanya Latha; K. Rashmi; P. Maruthi Mohan (BioMetals, 2003)

Lubeluzole and conditioned learning after cerebral ischemia - Rashmi N. Mueller; Donald J. Deyo; David R. Brantley; John F. Disterhoft; Mark H. Zornow (Experimental Brain Research, 2003)

In vitro somatic embryogenesis and plant regeneration in Acacia arabica - Rashmi M. Nanda; G.R. Rout (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Biosorption of inorganic and methyl mercury by a biosorbent from Aspergillus niger - D. Karunasagar; J. Arunachalam; K. Rashmi; J. Naveena Lavanya Latha; P. Maruthi Mohan (World Journal of Microbiology and Biotechnology, 2003)

Iron and copper homeostasis and intestinal absorption using the Caco2 cell model - Maria C. Linder; Nora R. Zerounian; Mizue Moriya; Rashmi Malpe (BioMetals, 2003)

Effects of exogenous vitamin E supplementation on the levels of oxidants and antioxidants in chronic obstructive pulmonary disease - M. K. Daga; Rashmi Chhabra; Bhavneesh Sharma; T. K. Mishra (Journal of Biosciences, 2003)

Dietary carotenoids, vegetables, and lung cancer risk in women: the Missouri Women's Healty Study (United States) - Margaret E. Wright; Susan T. Mayne; Christine A. Swanson; Rashmi Sinha; Michael C.R. Alavanja (Cancer Causes & Control, 2003)

Effects of Water Hardness and Metal Concentration on a Freshwater Tubifex Tubifex Muller - Rashmi Singh Rathore; B. S. Khangarot (Water, Air, & Soil Pollution, 2003)

Serum creatine phosphokinase in thyroid disorders - Rashmi Ranka; Rati Mathur (Indian Journal of Clinical Biochemistry, 2003)

How many antibiotics are produced by the genus Streptomyces ? - Milind Watve; Rashmi Tickoo; Maithili Jog; Bhalachandra Bhole (Archives of Microbiology, 2001)

Analysis of ADP-ribose polymer sizes in intact cells - Jean-Philippe Gagné; Rashmi G. Shah; Guy G. Poirier (Molecular and Cellular Biochemistry, 2001)

Response to Dr. Bandera - Rosalind Breslow; Barry Graubard; Rashmi Sinha; Amy Subar (Cancer Causes & Control, 2001)

Monitoring of Ganga Water and Sediments Vis-à-Vis Tannery Pollution at Kanpur (India): A Case Study - A. R. Khwaja; Rashmi Singh; S. N. Tandon (Environmental Monitoring and Assessment, 2001)

Cadmium mobilisation and plant availability – the impact of organic acids commonly exuded from roots - Rashmi Nigam; Shalini Srivastava; Satya Prakash; M. M. Srivastava (Plant and Soil, 2001)

Comparison of heterocyclic amine levels in home-cooked meats with exposure indicators (United States) - Garrett A. Keating; Rashmi Sinha; David Layton; Cynthia P. Salmon; Mark G. Knize; Kenneth T. Bogen; Charles F. Lynch; Michael Alavanja (Cancer Causes & Control, 2000)

Diet and lung cancer mortality: a 1987 National Health Interview Survey cohort study - Rosalind A. Breslow; Barry I. Graubard; Rashmi Sinha; Amy F. Subar (Cancer Causes & Control, 2000)

Trans-acting factors that interact with the proximal promoter sequences of ovalbumin gene are tissue-specific and age-related - Rashmi Upadhyay; Sanjay Gupta; M.S. Kanungo (Molecular and Cellular Biochemistry, 1999)

High-resolution DNA fingerprinting of Indian rice (Oryza sativa L) varieties by amplified fragment length polymorphism - Kapildeo N. Singh; Rashmi Nandi; P. Shanmugasundram; S. Sadasivam; Ning Huang; D.S. Brar; G.S. Khush (Genetic Resources and Crop Evolution, 1999)

Lactoferrin in cervical mucus as a biochemical marker for inflammation - Jayanti Mania-Pramanik; B. N. Mali; Rashmi S. Shah; U. M. Donde (Indian Journal of Clinical Biochemistry, 1999)

Monitoring of Daily Integrated Exposure of Outdoor Workers to Respirable Particulate Matter in an Urban Region of India - Milind M. Kulkarni; Rashmi S. Patil (Environmental Monitoring and Assessment, 1999)

Fried, well-done red meat and riskof lung cancer in women (United States) - Rashmi Sinha; Martin Kulldorff; Jane Curtin; Charles C. Brown; Michael C.R. Alavanja; Christine A. Swanson (Cancer Causes & Control, 1998)

Activation of vitellogenin II gene expression by steroid hormones in the old Japanese quail - Sanjay Gupta; Rashmi Upadhyay; M.S. Kanungo (Molecular Biology Reports, 1998)

Dietary fats and lung cancer risk among women: the Missouri Women's Health Study (United States) - Christine A. Swanson; Charles C. Brown; Rashmi Sinha; Martin Kulldorff; Ross C. Brownson; Michael C.R. Alavanja (Cancer Causes & Control, 1997)

Microdialysis Studies of the Distribution of Stavudine into the Central Nervous System in the Freely-Moving Rat - Zheng Yang; Richard C. Brundage; Rashmi H. Barbhaiya; Ronald J. Sawchuk (Pharmaceutical Research, 1997)

Assessment of Dose Proportionality, Absolute Bioavailability, and Immunogenicity Response of CTLA4Ig (BMS-188667), a Novel Immunosuppressive Agent, Following Subcutaneous and Intravenous Administration to Rats - Nuggehally R. Srinivas; Wen Chyi Shyu; Russell S. Weiner; Garvin Warner; Charles Comereski; Lee K. Tay; Douglas S. Greene; Rashmi H. Barbhaiya (Pharmaceutical Research, 1997)

Photoactivation of NADP-Malate Dehydrogenase by a Heterogeneous Photochemical System in Zea mays - Rashmi Mishra; P. S. Bisen (Journal of Plant Biochemistry and Biotechnology, 1997)

Hawan—An effective method to reduce fungal load at small work places - Rashmi Tewary; Jitendra Kumar Mishra (Aerobiologia, 1997)

Determination of genotoxicity of the metabolites of the pesticides Guthion, Sencor, Lorox, Reglone, Daconil and Admire by 32P-postlabeling - Rashmi G. Shah; Jean Lagueux; Sanjay Kapur; Patrick Levallois; Pierre Ayotte; Martine Tremblay; John Zee; Guy G. Poirier (Molecular and Cellular Biochemistry, 1997)

Meat preparation and colorectal adenomas in a large sigmoidoscopy-based case-control study in California (United States) - Nicole M. Probst-Hensch; Rashmi Sinha; Matthew P. Longnecker; John S. Witte; Sue A. Ingles; Harold D. Frankl; Eric R. Lee; Robert W. Haile (Cancer Causes & Control, 1997)

Allergic potential of someAspergilli on saw mill workers in Lucknow, India - Rashmi Tewary; Jitendra Kumar Mishra (Aerobiologia, 1996)

Allergic potential of someAspergilli on saw mill workers in Lucknow, India - Rashmi Tewary; Jitendra Kumar Mishra (Aerobiologia, 1996)